Geostationary observations of air pollutants from biomass burning: A synergy of GIIRS and GEMS over Southeast Asia - Shan Han; Shangyi Liu; Mengya Sheng; Jhoon Kim; Ximin Cui; Minqiang Zhou; Wei Wang; Isamu Morino; Voltaire A. Velazco; Zhao-Cheng Zeng (Remote Sensing of Environment, 2026)

Synergistic effect of peptide KF3 and citronellal against F. graminearum ACCC 37687 and their application in maize preservation - Yingxin Wei; Zhanyi Yang; Xiangwan Wang; Baojing Cheng; Anshan Shan (International Journal of Food Microbiology, 2026)

Tuning sulfur fixation via conditioner–oxygen synergy during oxidative pyrolysis of sewage sludge under smouldering conditions - Shan Cheng; Linxi Guo; Hong Tian; Dangzhen Lv; Junjie Huang; Jiaxin Yu (Fuel, 2026)

Endogenous 6-phospho-β-glucosidase overexpression in Lactiplantibacillus plantarum modulates selective enrichment of bioactive and volatile metabolites in black tea extract - Yao-Zeng Zhang; Zhi-Peng Cheng; Pei-Yi Feng; Xin-Xin Liu; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Microbiology, 2026)

Integrative exome sequencing and multi-omics analysis elucidates the regulatory role of rare variants in metabolic syndrome - Cheng-Xi Wu; Jin Sang; Qian Xu; Ya Zhan; Shan-Juan Yuan; Yuan-Yuan Ge; Xiu-Juan Yu; Xiao Zheng; Xiao-Feng Wang; Xian-Mei He; Chao-Jie Liu; Yuan Luo; et al. (Functional & Integrative Genomics, 2026)

Single-cell transcriptomic profiling identifies TIMP1 as a diagnostic marker linked to macrophage ferroptosis in ulcerative colitis - Wen-Hao Xiong; Shuo Huang; Yan-Hong Liu; Guo-Shan Chen; Dan-Zhou Li; Yong-Cheng Di; Wen-Bin Song; Yong-Chao Zhang; Yi-Fan Wang; Feng Qi (Tissue and Cell, 2026)

Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

Research progress of carbon dioxide radical anions: Properties, generation, and environmental applications - Sheng Wang; Cheng-Xin Chen; Ping Fang; Tong Wu; Xuan-Yuan Pei; Jing Yang; Shan-Shan Yang; Jie Ding (Chemical Engineering Journal, 2026)

Indoor environmental quality of underground spaces: Multi-dimensional assessment and interaction effects in a renovated air-raid shelter bookstore in transition season - Ran Cheng; Ting Fu; Hong Hu; Shan Gao; Chi Feng (Building and Environment, 2026)

Nanoarchitectonics with synergistic optimization among various structural types in walnut green peel derived carbon materials for high-performance symmetric supercapacitors - Xiaoxue Liu; Hao Wu; Jun Zhang; Jinfeng Zheng; Duoliang Shan; Xiaoyang Cheng; Lingyan Li; Yilei Jing (Biomass and Bioenergy, 2026)

Molecular-level analysis of atmospheric particulate organic compounds using HPLC-Orbitrap MS/MS: effects of solvents - Shan Xu; Minghui Lu; Ping Zeng; Meng Chang; Haoqian Wang; Xuehui He; Baode Xue; Xinyu Ji; Kuai Yu; Jingkun Jiang; Hairong Cheng; Xiaoxiao Li (ENGINEERING Environment, 2026)

Decadal gelatinization and phenological advancement of small jellyfish in Laizhou Bay, Bohai Sea - Ping Fu; Shan Sun; Huichao Jiang; Jianlong He; Ling Cheng; Bo Su; Hongyan Xing; Yuanqing Ma; Lijuan Liu; Yuting Zhao; Juan Zhang; Xiaowen Zhang (Marine Pollution Bulletin, 2026)

Blue light effects on the synergistic degradation pathways of minocycline hydrochloride and catechin under basic conditions - Shiuh-Tsuen Huang; Shwu-Yuan Lee; Jeu-Ming P. Yuann; Hsien-Tsung Tsai; Hsuan-Han Huang; Yi-Cheng Hsieh; Pei-Shan Wang; Yu-Min Tzou; Ji-Yuan Liang (Journal of Environmental Chemical Engineering, 2026)

Cu+-doped Cu/CoO with modulated intrinsic and interfacial conductivity and −60 °C energy storage performance - Guanglei Zhang; Mingyue Du; Xinhua Xu; Xiumei Shan; Yijing Cheng; Yingyue Zhou; Jingyu Feng; Weifeng Liu; Yamin Feng (Chemical Engineering Journal, 2026)

HiMA-seq enables cost-effective spatiotemporal transcriptomics with high sensitivity and flexible multiplexity - Jiahe Liu; Zhidong Tang; Shan Jiang; Peiqing Miao; Shimei Yin; Ziwei Zhou; Li Lei; Dong Cheng; Xiru Liu; Liuyang Zhao; Ailong Huang (Chemical Engineering Journal, 2026)

Unveiling dynamic membrane functions in a high-rate anaerobic mesophilic co-digestion system treating cow manure and food waste: Performance, digestate characteristics, and microbial community - Hao-Cheng Zhang; Liguo Wan; Yule Han; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Bioresource Technology, 2026)

First ground-based FTIR observations of stratospheric ClONO2 at a mid-latitude China site and comparison with satellite data - Shiyi Wang; Wei Wang; Xiangyu Zeng; Changgong Shan; Cheng Liu (Atmospheric Environment, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

Effects of dietary yeast cell wall supplementation on growth performance, serum enzyme activity, and immune gene expression in Pacific white shrimp (Litopenaeus vannamei) - Chuan Chen; Xinhe Ruan; Jinhong Shan; Zijie Xuan; Huitao Cheng; Fengqi Huang; Lihua Li; Zongyang Li; Xiaoling Zuo; Jie Yu; Huihong Zhao (Animal Feed Science and Technology, 2026)

Metal ion-modulated KRAS conformational dynamics unraveled by ultraviolet photodissociation - Zhixiong Jin; Shirui Yang; Zheyi Liu; Haozhe Wu; Heng Zhao; Chen Dong; Shan Zhao; Cheng Luo; Fangjun Wang; Yuanjiang Pan (Analytica Chimica Acta, 2026)

Morphological saliency prior-guided band-aware multi-modal disease diagnostic fusion network for vibrational spectroscopy - Haitao Song; Xuguang Zhou; Hui Tang; Cheng Chen; Chao Dong; Yanyan Chen; Le Yang; Meihui Shan; Kunming Wang; Shenshen Yan; Haoyi Xu; Binlin Ma (Analytica Chimica Acta, 2026)

Membrane-regulated seawater electrolysis for sustainable hydrogen production - Zhongting Liu; Jingfen Yuan; Sunpeng Shan; Guangpu Li; Song Gu; Cheng Chen; Wei Yu; Mingzhu Zhou; Saleem Raza; Ying Liu; Hongjun Lin; Yang Jiao; et al. (Water Research, 2026)

Matrine ameliorated myocardial ischemia-reperfusion injury through lipid accumulation reduction by activating JAK2-STAT3-CPT1 signaling pathway - Mengyan Liu; Xin Cheng; Huan Jiang; Yuna Mao; Jianbin Li; Chuncan Qiao; Xiaoyu Wang; Wanrong Wang; Shan Gao; Kai Zhou (Toxicology and Applied Pharmacology, 2026)

Finite strain pattern inferred from magnetic fabrics across the southern portion of the Central Range, Taiwan - Ya-Chu Tseng; En-Chao Yeh; Ning-Shan Hui; Yu-Min Chou; Jian-Cheng Lee; Ching-Chou Fu (Tectonophysics, 2026)

Biotransformation of Cimetidine by Chlamydomonas sp. SI-16: CYP450-Driven Detoxification and Immobilized Photobioreactor Validation - Kang Li; Jun Liu; Yongtao Cheng; Chenxi Zhou; Kang Shan; Chuanyue Peng; Wenjing Yan; Ying Liu; An Xu; Min Zuo (Journal of Hazardous Materials, 2026)

Submicron-scale mineral weathering and organo-mineral association in the rhizosphere of iron ore tailings - Zhen Li; Songlin Wu; Ting-Shan Chan; Cheng-Wei Kao; Jian Wang; Gordon Southam; Longbin Huang (Geochimica et Cosmochimica Acta, 2026)

Emerging plasma-activated technologies for future food preservation: principles, mechanisms and potential large-scale applications - Shan Tang; Guangsheng Yang; Jun-Hu Cheng; Xiao Yang; Kevin M. Keener (Food Research International, 2026)

Screening of immune adjuvants for an attenuated live vaccine derived from the Aeromonas veronii TH0426 strain with a hisJ gene deletion and evaluation of its immune protection in crucian carp - Qixing Huang; Ruitong Li; Shuoyu Wang; Ruiqi Liang; Peiqi Lu; Bingmei Du; Yan Cheng; Xiaochen Ren; Jinhong Li; Xu Dong; Jiaojiao Yang; Luyao Chu; et al. (Fish & Shellfish Immunology, 2026)

Evaluation of Local Tolerance of Structurally Different Olaflur Compounds - Junzhuang Chang; Shasha Wang; Jiaqi Shan; Xuejiao Chen; Aolu Liu; Yun Ding; Nan Liu; Shujun Cheng (Food and Chemical Toxicology, 2026)

Associations of single and mixed air pollution exposure with lung function and incident pulmonary fibrosis: The mediation effect of low-grade inflammation - Yue Fei; Zengxu Shen; Mengxin Tian; Hanrui Liu; Ziruo Cheng; Xueshan Jin; Shan Bao; Zhenzhong Ge; Haotian Xu; Jian Feng; Xiaoyu Zhou; Xinyuan Zhao (Environmental Pollution, 2026)

Incipient damage localization in thick-walled hollow cylinders based on nonlinear elastic wave scattering features - Yuanman Zhang; Shengbo Shan; Li Cheng (Engineering Structures, 2026)

High-permeability nanophotosensitizer eliminates biofilm-associated infection through concurrent lipid peroxidation and extracellular DNA degradation - Xiaochun Xie; Ziming Huo; Shaowen Wang; Jiying Liu; Chenyang Guo; Huantai Luo; Chuanxu Cheng; Wen Sun; Shan Guan; Panpan Chang; Dan Shao; Ronghua Yang (Chemical Engineering Journal, 2026)

See and destroy bacterial spores: Visual detection and in situ inactivation using a terbium-porphyrin nanoplatform - Shan Sun; Ke Cheng; Jiayi Feng; Hongbo Juan; Kefeng Zhou; Mingyan Zhao; Heng Zhang; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2026)

Mango peel pectin as a high-ester emulsifier for carotenoid delivery: Structural characterization and application in low-fat ice cream - Teng-Gen Hu; Huan Zhang; Lu Li; Yu-Qing Hu; Jing Wen; Bo Zou; Jian Peng; Li-Na Cheng; Ji-Jun Wu; Geng-Sheng Xiao; Yu-Juan Xu; Yuan-Shan Yu (Carbohydrate Polymers, 2026)

Photocatalytic degradation of diclofenac using iron-doped hydrothermal carbonation carbon coupled with peroxydisulfate: Insights into reactive species contributions and degradation pathways via density functional theory - Chao Zhang; Yutong Zhang; Yueyao Cheng; Meifang Li; Yuanhao Peng; Hao Xu; Siwei Kang; Yuan Ouyang; Zhihang Yuan; Shan Xie; Chuansheng Chen (Bioresource Technology, 2026)

Experimental study of photonuclear transmutation driven by laser-wakefield acceleration - Yongsheng Xu; Di Wu; Chuangye He; Hao Cheng; Shan Ye; Bingkun Dong; Muyang Lu; Fulong Liu; Haoyang Lan; Meizhi Wang; Yuhui Xia; Zhenan Wang; et al. (Annals of Nuclear Energy, 2026)

Unsaturated lactones from Aspergillus ochraceopetaliformis - Jing-Jie Bai; Hong-Qian Pan; Qiong Liu; Duo-Xiu Li; Bai-Chuan Zhu; Ying-Ming Zhang; Ai-Hong Zhao; Cheng-Shan Yuan (Natural Product Research, 2026)

A preliminary design method for jacket support structures of high-capacity offshore wind turbines - Renqiang Xi; Haipeng Shan; Meiling Cheng; M. Hesham El Naggar; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Differential thermal sensitivity among shallow-water octocorals and its association with holobiont composition - Hsien-Yu Cheng; Yu-Chien Wang; Yan-Zhen Meng; Chien-Yi Wu; An-Chi Liu; Yen-Chih Lin; Jui-Hsun Hung; Shan-Hua Yang (Marine Environmental Research, 2026)

Accelerated degradation of antiviral ribavirin by microalgae fuel cell (MFC), electricity generation and key metabolic process - Junhao Wang; Xinrui Qin; Jiajia Ge; Yongtao Cheng; Kang Li; Jun Liu; Kang Shan; Chuanyue Peng; Wenjing Yan; Juan Wang; Min Zuo; Ying Liu (Journal of Environmental Chemical Engineering, 2026)

Electron-networking Cu single atom-spurred Ru clusters for anion exchange membrane water electrolysis - Zihao Zhou; Rui Qin; Tingjie Mao; Pinlin Wang; Zhongliang Huang; Ting-shan Chan; Yu-cheng Huang; Zhiwei Hu; Xiaoqing Huang; Nanjun Chen; Yunhua Li (Chemical Engineering Journal, 2026)

Synchronously enhanced methanogenesis performance and reduced antibiotic resistance genes of cattle manure anaerobic digestion by air nanobubble water - Jiabei Shan; Tianfeng Wang; Cheng Peng; Peilin Guo; Hong Zhu; Dan Luo; Yonggang Wang; Jixiang Chen (Bioresource Technology, 2026)

Solution to non-limit state active earth pressure onto retaining wall with narrow backfills for unsaturated cohesive-frictional soils: effect of transient infiltration and steady seepage - Ya-cheng Dong; Yao Shan; Yu Zhao; Tong Zhou; Dong Liu (Transportation Geotechnics, 2026)

Out-of-plane flexural behaviors of curved steel-plate composite walls with small curvature radius-to-section thickness ratio - Cheng Liu; Shan Gao; Sumei Zhang; Lanhui Guo (Engineering Structures, 2026)

Enhancing NH₃-SCR Denitrification Performance by Regulating the B/L Acid Balance on the Surface of Municipal Solid Waste Incineration Fly ash-Derived Zeolite - Wei Zhang; Tao Liu; Zhihao Yao; Kaikai Zhang; Dancong Li; Zhaoyi Zhou; Yanshan Yin; Yanni Xuan; Min Ruan; Shan Cheng; Shouan Cheng; Wenkai Hu; et al. (Water, Air, & Soil Pollution, 2026)

Short-term organic fertilizer substitution: effects on crop yield and soil phosphorus dynamics in a rice-rapeseed rotation system - Hui Wang; Wenlong Cheng; Shang Han; Shan Tang; Fahui Jiang; Rongyan Bu; Min Li; Rui Zhu; Mengmeng Tang; Zhenghua Xu; Ji Wu (Journal of Soils and Sediments, 2026)

n ‐Alkane Gradients Reshape Soil Microbial Networks and Functions at Petroleum Refinery Sites - Youru Zhang; Shixuan Cui; Yu Zhang; Jizhuang Chu; Kaiyue Liu; Xinjie Shan; Na Wang; Shudi Yao; Qiang Kong; Cheng Dong; Huanxin Zhang (Environmental Microbiology, 2026)
Petroleum refining activities exert substantial contamination pressure on soil ecosystems, yet the corresponding microbial response mechanisms remain insufficiently understood. This study integrates source apportionment, high‐throughput sequencing and co‐occurrence network analysis to elucidate microbial adaptations along a petroleum exposure gradient. Source analysis confirmed that all soils were predominantly influenced by petroleum‐derived inputs, with hydrocarbon concentrations increasing significantly across gradients. Under contamination levels of 422.35–621.21 mg/kg, petroleum pollution not only reduced soil total organic carbon (TOC) but also induced coupled C–N interactions and altered soil physicochemical properties, resulting in complex environmental effects. The soil quality index (SQI) exhibited a nonlinear trend, first decreasing and then increasing, with moderate overall levels (0.40–0.45). Functional diversity analyses indicated functional convergence rather than loss under contamination stress. At the metabolic level, low exposure primarily stimulated naphthalene degradation and detoxification pathways, whereas high exposure shifted microbial functions towards oxidative stress resistance and membrane structural remodelling. Meanwhile, microbial networks transitioned from densely connected but disturbance‐sensitive structures at low exposure to simplified yet more stable and robust configurations at high exposure. These findings provide mechanistic insights into microbial adaptation in petroleum‐contaminated soils and offer theoretical support for bioremediation strategies.

Multidimensional chemoprofiling of hybrid and wild Broussonetia papyrifera : sustainable utilization analysis of wild resource substitutes - Yue Ren; Ziye Cheng; Chunmei Yang; Long Han; Xianjun He; Yuqi Liu; Lin Ma; Chuhan Wang; Ziyi Shan; Wen Qin; Xiaofan Yuan (Natural Product Research, 2026)

Fipronil and its transformation products in the Pearl River Estuary: Spatial distribution, bioaccumulation, trophic transfer and risk assessment - Lisha Ma; Can Huo; Yuhan Xie; Yi Yin; Qi Shan; Cheng Zhao; Shugui Liu (Marine Pollution Bulletin, 2026)

Sex-specific metabolic reprogramming in Trachinotus blochii under short- and long-term hypoxia - Yue Gu; Yue Chen; Ze Xin Zhong; Fu Cheng Yao; Chun Xiu Jin; Shan Ying Han; Fei Biao Song; Jian Luo; Jun Long Sun (Aquaculture, 2026)

Immune efficacy evaluation of a PEDV spike protein-derived multi-epitope subunit vaccine candidate in mice - Yihong Luo; Miaozhan Wei; Bin Wang; Huaping Yin; Xiaojiang Guo; Taotao Ji; Fei Xu; Junjun Ban; Zehong Cen; Bijun Zhou; Chunlan Shan; Anchun Cheng; et al. (Veterinary Immunology and Immunopathology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Trace elements in surface sediments along the Shenzhen coast, South China: Spatial-seasonal patterns, ecological risk, and PMF-based source apportionment - Cheng Chen; Ziliang Chen; Pujiang Huang; Liangming Wang; Binbin Shan; Yan Liu; Yingbang Huang; Zaiwang Zhang; Qijian Xie; Manting Liu; Dianrong Sun; Changping Yang (Regional Studies in Marine Science, 2026)

Seven undescribed metabolites from Ganoderma lucidum-derived endophytic Talaromyces sp. GLQ04 and their anti-DLBCL (diffuse large B-cell lymphoma) activities - Shan Liu; Hao Sun; Pei-Ting Li; Pei-Shan Li; Xia Cheng; Feng Wang; Qi Luo (Phytochemistry, 2026)

Reshaping global energy security: Implications of embodied energy transfers in global supply chains - Yannan Zhou; Ying Lu; Yu Yang; Yan Cheng; Ze He; Yuxin Wang; Yuli Shan (Energy Policy, 2026)

Multifunctional hydrogel with dynamic phase-adaptive regulation for expediting infected diabetic wound repair - Yong-Shan Hu; Shi-Cheng Tian; Cheng-Lei Li; Jing-Wei Shao (Chemical Engineering Journal, 2026)

Glucose-sensitive and 3D-printable dynamic chitosan hydrogels from boronic acid-functionalized chitosan and gallol-functionalized chitosan - Ting-Yu Chang; Tsai-Yu Chen; Qian-Pu Cheng; Shan-hui Hsu (Carbohydrate Polymers, 2026)

Synergistic enhancement of selenium accumulation in rice: elucidating the role of biochar and selenobacteria in reshaping root microbiome assembly - Yan-Shan Wang; Zhi-Jiang Wang; Yan Wang; Zhan-Tong Ma; Chen-Wei He; Wei-Kang Wang; Jin-Yu Sun; Su-Tao Shi; Cheng-Xi Lu; An-Yong Hu; Hong Mei; Xi-En Long (Plant and Soil, 2026)

Biochar reshapes phosphorus distribution in soil aggregates and improves rice phosphorus uptake - Jiajun Wu; Bin Zhou; Zhehao Huang; Zichuan Li; Jingyuan Pan; Kaihao Zhang; Cheng Liu; Yanjun Chai; Yan Li; Muhammad Azeem; Nicholas Clarke; Shengdao Shan (Soil Ecology Letters, 2026)

Methods for correcting mud-logging lithology profile using well logging data based on neural networks - Li-zuan Jin; Yu-hong Sun; Hui Li; Zi-shan Dai; Cheng-fang Wang (Applied Geophysics, 2026)

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Analysis of the morphological structure and metabolic characteristics of Moniezia in sheep - Qian Mu; Wan-Ling Yao; Bao-Shan Wang; Wen-Zhu Chai; Fu-Hua Liu; Zhen Huang; Yong-Cheng Meng; Jing Pan; Xi-Ping Fan; Wan-Hong He; Wang-Dong Zhang (Veterinary Parasitology, 2026)

Non-radical PMS activation for simultaneous nitrite and sulfamethoxazole removal with inhibited nitrobyproduct formation - Jiawei Lin; Wenjun Zhou; Jiaqi Peng; Yongyou Hu; Hongfeng Zhang; Cheng Zhao; Qi Shan; Hao Zhou; Yi Yin (Journal of Water Process Engineering, 2026)

Cold exposure impairs the muscle growth-promoting effect of nighttime-restricted feeding by desynchronizing mitochondrial energy supply rhythm in rabbits - Yuan-Yuan Tan; Xiao-Han Ma; Chun-Hua Shan; Shuai He; Quan-Gang Wang; Meng-Qi Zhu; Jian-Xiang Cheng; Ke-Hao Zhang; Lei Zhang; Zhong-Ying Liu; Yao Guo; Zhong-Hong Wu (Journal of Thermal Biology, 2026)

Tracking high-field-strength-element enrichment pathways in alkaline granites: Insights from potassium and barium isotopes - Hao-Cheng Yu; Zheng-Yu Long; A.E. Williams-Jones; Ralf Halama; Frédéric Moynier; Shan-Shan Li; Ming-Qian Wu; Hao-Ran Duan; Jia-Dong Ma; Nan Ju; Ze-Zhou Wang; Kun-Feng Qiu (Geochimica et Cosmochimica Acta, 2026)

Atrazine increases hepatic inflammation and injury via endoplasmic reticulum (ER) stress mediated excessive formation of mitochondria-associated membranes (MAMs) and activation of the cGAS-STING pathway - Zi-Jun Sun; Guan-Yue Shan; Hui Wan; Yu-Xin Zhang; Zhi-Cheng Gao; Wen-Na Shi; Lei Lv; Wei-Qun Yan; Hai-Jun Li (Environmental Pollution, 2026)

Regulating ion mobility for intelligent “on-off” switchable electromagnetic wave absorption of ionogels in both GHz and THz band - Ruochu Lei; Zheng Cheng; Haolin Lu; Jianbin Wang; Zhiwen Zhou; Fei Fan; Bo Shan; Yi Huang (Chemical Engineering Journal, 2026)

Resveratrol-Eu-layered double hydroxide nanocomposite alleviates radiation-induced lung injury through antioxidant and IL-17/NF-κB-associated anti-inflammatory effects - Fangxiao Cao; Junzhe Yang; Xiaoyi Cai; Xin Zuo; Yiming Wang; Li Du; Yuxin Lu; Xiaochen Cheng; Tingting Liu; Shan Ma; Feiyu Zhao; Shanyue Guan; et al. (Chemical Engineering Journal, 2026)

Fe-Ni-MOF-derived NiFe2O4/NiO heterostructure for detection of 2-CEES at ppb level - Duo Zhang; Ying-Nan Dou; Rui Gao; Xian-Fa Zhang; Hui Zhao; Xiao-Li Cheng; Shan Gao; Ying-Ming Xu; Li-Hua Huo (Chemical Engineering Journal, 2026)

Shape-dependent magnetic-driven microrobots for biofilm-eradicating medical device disinfection through mechanical and chemical bactericidal action - Ke Cheng; Tongfang Fu; Shan Sun; Wenhao Zheng; Jiaming Gong; Jingxin Ma; Yazhou Zhou; Feili Lai; Martin Pumera; Hengwei Lin (Chemical Engineering Journal, 2026)

Perfusion process-oriented metabolic engineering enhances 1,3-dihydroxyacetone production efficiency in Gluconobacter thailandicus - Yang Sun; Zilong Hu; Yuwei Shan; Rui Wang; Tang Liu; Kuiqi Jin; Qingxuan Miao; Cheng Ye; Jianqi Nie; Daiyin Zuo; Yinbiao Xu; Hua Li; et al. (Chemical Engineering Journal, 2026)

Shoot apical meristem-dependent adventitious bud induction from embryo axes of castor bean (Ricinus communis L.) via optimized cytokinin-auxin ratio - Liang Bai; Liying Shan; Jian Song; Mengchen Xu; Yue Wang; Ruiyan Guo; Yanli Jin; Yangguang Duan; Yuling Zhang; Zhimin Jiang; Jilong Zhong; Yan Cheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Biosynthesis of active small molecule prenylsalidroside a and its anti-inflammatory activity - Jia-Hao Xue; Hua-Jin Yu; Long-Jun Li; Gui-Hu Lu; Pei-Shan Li; Xia Cheng; Qi Luo; Wei Wu; Zhong-Sheng Bi (Natural Product Research, 2026)

Two new sesquiterpene eudesmanolides from the Croton cascarilloides Raeusch - Tian-Yi Liu; Hong-Li Liu; Xi Jiang; Qiong Liu; Jing-Jie Bai; Ze-Ying Guo; Zheng Zhang; Ji-Hai Shang; Cheng-Shan Yuan (Natural Product Research, 2026)

Seasonal variations in the abundance and distribution of small-sized microplastics in Hong Kong's marine waters - Kai Zhang; Michael C.Y. Cheng; Mengyang Liu; Shaopeng Xu; Yue Ma; Hoi Shan Chau; Yaru Cao; Meng Yan; Wai Thoe; Sunny W.C. Sun; Ron R. Yang; Kenneth M.Y. Leung; et al. (Marine Pollution Bulletin, 2026)

Operationalizing nuclear safety: A remote α/β detection system integrating CNN and radioluminescence for emergency response - Zeqian Wu; Mei Xu; Qingbo Wang; Biao Yuan; Sheng Qi; Weiqi Huang; Jiangfeng Wu; Yonghong Wang; Kun Shan; Zhiling Hou; Jinxing Cheng (Journal of Hazardous Materials, 2026)

Scalable upcycling of medical plastic waste using metals-doped hierarchically porous biocarbon for tunable fuel-grade hydrocarbons or H2-enriched fuel gas - Guanyu Zhang; Qing Cheng; Ge Kong; Yuan Jiang; Xin Zhang; Tianqi Cao; Jingyou Bi; Jin Wang; Fangqi Liu; Chun Shan; Xuesong Zhang; Lujia Han (Fuel, 2026)

Distinguishing the contributions of organic matter and iron (oxyhydr)oxides to zinc availability in paddy soils surrounding lead-zinc mines - Yecheng Li; Zebin Hong; Yan Ru; Guojun Chen; Xiaomin Li; Shiwen Hu; Yang Yang; Chao Guo; Shan Wang; Pengfei Cheng; Qi Wang; Tongxu Liu (Environmental Pollution, 2026)

Chronoregulatory and neuroprotective effects of yeast β-glucan against systemic inflammation - Wai-Yin Cheng; Pak-Hei Chan; Po-Lam Chan; Ka-Lung Lam; Nathanael Chun-Him Lai; Yuen-Shan Ho; Wing-Fai Yeung; Ka-Hing Wong; Peter Chi-Keung Cheung; Raymond Chuen-Chung Chang (Carbohydrate Polymers, 2026)

Pharmacological effects of cardamonin in metabolic diseases: a review on preclinical studies - Aizhi Zhang; AbdulRahman Muthanna; Yu Zhao Lee; Xuan Xin Yew; Rieyshmondraj Selvanathan; Zuo Shan Reuel Gan; Ji Wei Tan; Yu-Cheng Ho; Ming Tatt Lee; Chau Ling Tham (Inflammopharmacology, 2026)

Contrasting fine root-induced rhizosphere priming effects between coniferous and broadleaved trees - Weijun Zhang; Junjie Lin; Qitai Cheng; Liming Yin; Wenling Zhang; Amit Kumar; Xiali Mao; Hongxin Dong; Dafeng Hui; Mengguang Han; Lei Tao; Dingxin Su; et al. (Biology and Fertility of Soils, 2026)

Associations of Sleep Timing and Regularity With Diabetes and Interactions With Diet Quality Among Adults - Tianzhu Qin; Hongkun Di; Sibo Liu; Boyang Chen; Qi Wu; Wen Hu; Xiang Cheng; Liegang Liu; Zhilei Shan (Journal of the Academy of Nutrition and Dietetics, 2026)

System-dependent effects and mechanisms of microplastics/nanoplastics on nitrogen and phosphorus removal from wastewater treatment and N2O emission - Tong Wu; Shuai-Hang Wang; Ping Fang; Cheng-Xin Chen; Jie Ding; Ying He; Han-Jun Sun; Meng-Qi Ding; Ji-Wei Pang; Nan-Qi Ren; Shan-Shan Yang (Journal of Hazardous Materials, 2026)

Depolymerization mechanism of α-O-4 type lignin in pyrolysis through a cyclohexadienone intermediate - Jiaxue Zhu; Quan Tang; Xun Gong; Erwei Leng; Yuanwang Deng; Hong Tian; Shan Cheng; Jiaqiang E (Fuel, 2026)

Impacts of a water-sediment regulation scheme on fish community assembly in the Yellow River Estuary and adjacent neritic waters - Yunlong Chen; Xiaomin Zhang; Xiangyu Cheng; Shuai Cai; Fan Li; Harry Gorfine; Yongqiang Shi; Yanyan Yang; Xianshi Jin; Xiujuan Shan (Estuarine, Coastal and Shelf Science, 2026)

From participation to partnership: A systematic review of public engagement in sustainable urban planning - Ping He; Qian-Cheng Wang; Han Wang; Jin Xue; Helen Xiaohui Bao; Geoffrey Qiping Shen; Shan Guo; Meng Ni; Shengwei Wang (Environmental Impact Assessment Review, 2026)

Interpenetrating network hydrogels based on soy protein isolate and sanxan: Structure, mechanical properties, and freeze-thaw stability - Yue Zhao; Yuehan Shan; Hongjuan Wang; Zhao Zhang; Caili Wang; Lei Dai; Yanfei Wang; Qingjie Sun; David Julian McClements; Yongqiang Cheng; Xingfeng Xu (Carbohydrate Polymers, 2026)

Ecological roles of lactic acid bacteria biodiversity and cross-feeding in shaping the flavor landscape of traditional Huangjiu fermentation - Chao-Jie Zhu; Yi-Ling Zhong; Yong-Zhu Zhang; Zhi-Chu Shan; Hong-Yan Qu; Fei Cheng; Wei Feng; Peng Wang; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Bioresource Technology, 2026)

Volumetric Path Planning and Visualization for ROV-Based Forward-Looking Sonar Scanning of 3D Water Areas - Yu-Cheng Chou; Wei-Shan Chang (Journal of Marine Science and Engineering, 2026)
Remotely operated vehicles (ROVs) equipped with multibeam forward-looking sonar are widely used for underwater object search in environments where visibility is limited. Ensuring complete three-dimensional (3D) scan coverage within a bounded mission duration remains a challenging planning problem due to sonar beam geometry and vehicle motion constraints. This study presents a deterministic, geometry-driven framework for volumetric path planning of ROV-based forward-looking sonar scanning in predefined circular and rectangular underwater volumes. The proposed approach constructs layered planar scan trajectories by explicitly incorporating sonar detection range, horizontal and vertical beamwidths, and scan volume geometry. Mission duration is analytically estimated from path length and vehicle kinematic parameters, enabling systematic comparison among multiple planning strategies. To support qualitative interpretation of scan effectiveness, a distance-based target position certainty metric is introduced and combined with the active sonar equation to estimate likely target locations within the scanned volume. Simulation results under idealized sensing and motion assumptions demonstrate that the corrected zigzag pattern for rectangular scan areas, as well as the corrected zigzag-II and corrected arithmetic spiral-III patterns for circular scan areas, achieve complete volumetric coverage with bounded mission duration and consistent localization performance. The proposed framework provides a transparent analytical baseline for evaluating volumetric scan path planning strategies for forward-looking sonar–equipped ROVs.

Distinct Role of Specialized Cutaneous Schwann Cell Network in Acute and Chronic Pain Sensation - Shan-Xin Zhang; Jing Yang; Yao Lou; Song-Cheng Xu; Ran Guo; Zhen-Zhong Xu (Neuroscience Bulletin, 2026)

Dramatic triacylglycerol improvement through quadri-knockout of type-2 acyl-CoA-dependent diacylglyceryl acyltransferases in a bait microalga, Nannochloropsis oceanica - Tao Xu; Xiang Jiang; Xitao Chen; Zheng Li; Congcong Miao; Shan Wu; Yuhui Cheng; Chengcheng Li; Yi Xin; Yandu Lu (Aquaculture, 2026)

Seasonal harvest dictates insecticidal efficacy of Hedychium longipetalum essential oil against stored product pests - Yuan Zhang; Cheng-Fang Wang; Jia-Zhu Wang; Han-Yu He; Yu-Chen Zhang; Wang-Yu Zheng; Xiao-Yi Shi; Shu-Shan Du (Pesticide Biochemistry and Physiology, 2026)

Synergistic Cu-Mn bimetallic sites on MCM-41 for high-efficiency H2S capture from blast furnace gas - Shan Nie; Cheng Zhao; Han Zheng; Xin Feng; Junge Yun; Ninghan Wei; Zhangfa Tong; Zhihang Chen (Journal of Environmental Chemical Engineering, 2026)

Montmorillonite-enhanced nitrogen fixation and emission reduction during food wast pyrolysis - Hongyuan Chen; Danni Li; Yazhuo Wang; Yaoxin Xiao; Dong Liang; Gangqi Cheng; Rui Shan; Haorang Yuan; Yong Chen (Fuel, 2026)

Comprehensive review on the impact of building envelopes on indoor thermal comfort in office buildings: Balancing occupant comfort and energy efficiency - Duqin Hong; Ran Cheng; Hao Lei; Xiaohui Zhou; Liu Yang; Chi Feng; Shan Gao (Building and Environment, 2026)

Correction to: Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2026)

An electrocatalytic dual molecularly imprinted polymer-based biosensor enables femtomolar detection of CD44 without antibodies - Ping Xia; Cheng Chen; Ruifang Bai; Weige Dong; Yuchun Fu; Chungu Zhang; Lianhai Shan; Shun Feng (Analytica Chimica Acta, 2026)

A new chromone from the roots of Stellera chamaejasme L. - Liu Qiong; Hong-Qian Pan; Bai Jing-Jie; Duo-Xiu Li; Zhi-Chao Feng; Cheng-Shan Yuan (Natural Product Research, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Incomplete lineage sorting, hybridization and polyploidization blurred phylogenetic relationships of gentians from the Qinghai-Tibetan Plateau - Shan-Shan Sun; Shu-Han Xu; Wen-Jie Yi; Shi-Long Chen; Pan Li; Daiki Takahashi; Harue Abe; Xiao-Lei Ma; Peng-Cheng Fu (Molecular Phylogenetics and Evolution, 2026)

Insight in the role of organic nitrogen compounds in organic sulfur release during sewage sludge pyrolysis: A experimental and theoretical study - Shan Cheng; Kehui Yao; Linxi Guo; Wen Chen; Zihui Xu; Hong Tian (Fuel, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Urban waterlogging depth prediction model combining transformer and graph neural convolutional network - Fengchang Xue; Jing Shan; Yao Cheng (Environmental Modelling & Software, 2026)

Ecological characteristics and carrying capacity analysis of marine ranching ecosystem in Beibu Gulf based on Ecopath model - Cheng Cheng; Haolin Yu; Jie Feng; Yan Li; Qingxian Cao; Li Liu; Cheng Yang; Shan Zhao; Shuo Li; Zhen Zhang; Haiyan Wang; Tao Zhang (Journal of Oceanology and Limnology, 2026)

Thinning altered the response of GPP to environmental factors in a coniferous plantation in Southern China - Shengtong Li; Mingjie Xu; Fengting Yang; Yuting Wang; Jiaxin Song; Baoxin Shan; Ziyi Wang; Huimin Wang; Xianjin Zhu; Chuanpeng Cheng; Jianlei Wang; Tao Zhang (International Journal of Biometeorology, 2026)

Spatial aggregation trends of cultivated land quality and landscape patterns: A remote sensing analysis - Mengmeng Tang; Wenlong Cheng; Zhengbao Gao; Fahui Jiang; Shang Han; Danyang Xu; Rongyan Bu; Shan Tang; Rui Zhu; Min Li; Hui Wang; Changai Lu; et al. (Applied Soil Ecology, 2026)

Deep learning for optimizing urban governance by "sensing-processing-responding" cycle: Recent advances, future prospects and challenges - Mingjun Cheng; Hong Jin; Qinfeng Zhao; Yurun Wang; Yanxi Wu; Shan Huang; Wenze Yue (Sustainable Cities and Society, 2025)

Biochar promoted soil organic carbon accumulation and aggregate stability by increasing the content of organic complex metal oxides in paddy soil - Jiajun Wu; Bin Zhou; Zichuan Li; Cheng Liu; Yan Li; Yulin Wang; Ning Zhao; Zhuozhe Wang; Yanjun Chai; Antonio Scopa; Marios Drosos; Vishnu D. Rajput; et al. (Soil and Tillage Research, 2025)

FuHsi regulates rDNA transcription and promotes tumor progression - Xiaohui Yang; Ao Ding; Songzhe Wu; Ziyue Jiang; Yifei Li; Xianting Huang; Liqiang Duan; Shuwen Cheng; Shizhong Zheng; Shan Gao (Science Bulletin, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Toonasinetins A and B, two new compounds from the branches and leaves of Toona sinensis - Nai-Dong Li; Cheng-Shan Wei; Chun-Xia Song; Chun-Jiang Du; Juan Xu (Phytochemistry Letters, 2025)

A review of flexible fluid-structure interactions in the ocean: Progress, challenges, and future directions - Sasan Tavakoli; Mansi Singh; Saeed Hosseinzadeh; Zhengyu Hu; Yaniln Shao; Shan Wang; Luofeng Huang; Apostolos Grammatikopoulos; Yuzhu Pearl Li; Danial Khojasteh; Jin Liu; Azam Dolatshah; et al. (Ocean Engineering, 2025)

Application of microbial electrolysis cells in enrichment of anammox bacteria - Qi Gao; Liang Fu; Jing Wei; Xiao-Chun Wang; Xiang Xiao; Yang-Yang Yu; Liang Cheng; Yu-Hao Qiu; Shan-Wei Li (Journal of Environmental Chemical Engineering, 2025)

New insights into the mechanism of quick-freezing reducing blueberry flavor loss: Coupling cellular microstructure maintenance and fatty acid metabolism regulation - Haiying Yang; Jia Guo; Shuhua Lin; Lvhong Huang; Xiaomei Cheng; Wenzhi Yi; Rongrong Wang; Yang Shan; Ning Jiang; Shenghua Ding (Food Research International, 2025)

Improvement of low-oil emulsion gel performance using interfacial engineering: Impact of pea protein-curdlan interfacial structure on freeze-thaw stability and in vitro digestion - Yuehan Shan; Yue Zhao; Hongjuan Wang; Lei Dai; Yanfei Wang; Qingjie Sun; David Julian McClements; Yongqiang Cheng; Xingfeng Xu (Food Chemistry, 2025)

Molecular insights into the flavor chemistry of Kava (Piper methysticum): Integrating sensory evaluation, chemical analysis, and computational docking - Jingtao Wang; Shan Wang; Zhongrong Jiang; Mengyang Liang; Dongliang Li; Jiabao Zhang; Chen Cheng; Wu Fan; Qingzhao Shi; Qidong Zhang; Guobi Chai (Food Bioscience, 2025)

Lipid metabolism and immune crosstalk in fish gut-liver axis: Insights from SOCS8 knockout and dietary stress models - Fatima Altaf; Nan Wu; Mijuan Shi; Jialin Li; Junwei Shan; Lian Su; Guangxin Wang; Qingsong Zhu; Yuhang Hu; Yinying Cheng; Wanting Zhang; Bruno Hamish Unger; et al. (Fish & Shellfish Immunology, 2025)

DNMT1 inhibition improves the activity of memory-like natural killer cells by enhancing the level of autophagy - Yixun Li; Chong Guo; Fujia Zhang; Shenju Cheng; Yanhong Li; Shan Luo; Yun Zeng; Yaling Zhao; Kun Wu (Molecular Biology Reports, 2025)

Prevalence and spectrum of STRC variants in 1015 sensorineural hearing loss patients: insights from the Chinese population - Luo Guo; Sha Yu; Wenrui Zhao; Liheng Chen; Guiqing Cheng; Weitao Li; Wei Li; Haiting Ji; Shan Sun; Huiqian Yu; Haiying Liu; Chunyi Gui; et al. (Molecular Genetics and Genomics, 2025)

A standard for geological evaluation of urban underground space resources in the Beijing plain - Han-han He; Cheng-shan Wang; Jing He; Yuan-xin Zhou; Lei Wang; Stuart Marsh; Chao Li; Tong-ming Fang; Fang-zhen Li; Sheng-li Cao; Jing Liu; Yi-ting Zhao (Bulletin of Engineering Geology and the Environment, 2025)

Partially empirical model-based water depth retrieval in shallow sea using GF5-AHSI hyperspectral remote sensing data: a case study on Meizhou Bay in Fujian Province, China - Xiaoai Dai; Yunfeng Shan; Cheng Li; Hao Chen; Tangrui Dai; Ge Qu; Tianyi Xie; Chengbo Tong; Htun Naing; Min Zhang (Frontiers of Earth Science, 2025)

Preparation of Nitrogen-Doped Fluorescent Carbon Quantum Dots and Detection Study of Tetracycline - Li Han; Hui Wang; Jiajia Ye; Fengcui Shi; Wen He; Xing Gao; Yan Gao; Chaoyue Shan; Haidi Cheng (Journal of Fluorescence, 2025)

Bioactive secondary metabolites from an endophytic fungus Chloridium virescens GLQ05 and structural revision of alteamide - Shan Liu; Pei-Ting Li; Peishan Li; Xinhuan Qiu; Xia Cheng; Qi Luo; Feng Wang (Natural Product Research, 2025)

Analytical and numerical investigations of the interaction between nonlinear guided wave mixing and micro-cracks in pipe-like structures - Maoxun Sun; Miaohong Tan; Cheng Shan; Yue Zhang; Hongye Liu (Wave Motion, 2025)

Above-ground natural gas riser leak dispersion and leakage rate prediction based on CFD and BPNN approaches - Xinmeng Jiang; Hongfang Lu; Zhiheng Xia; Zhi-Wei Shan; Yaqin Xiang; Y. Frank Cheng (Process Safety and Environmental Protection, 2025)

Outbreeding of isofemale lines as a candidate approach to improve the quality of thelytokous Wolbachia-infected line of the egg parasitoid, Trichogramma dendrolimi Matsumura (Hymenoptera: Trichogrammatidae - Hong-Yu Liang; Ying Shan; Qian-Jin Dong; Jin-Cheng Zhou; Xiao-Hui Ma; Li-Sheng Zhang; Wu-Nan Che; Hui Dong (Journal of Invertebrate Pathology, 2025)

Preparation of stir bars coated with N-modified COFs and application to estrogen detection in dairy products - Xixi Lian; Lianzhi Wang; Jianing Sun; Yingying Fu; Zhengchao Duan; Yazhuo Wang; Che Zhao; Gangqi Cheng; Rui Shan (Food Chemistry, 2025)

Topography-engineered cobalt-based microparticles for biofilm-eradicating medical device disinfection: Overcoming antibacterial resistance through mechano-bactericidal action - Ke Cheng; Shan Sun; Wenhao Zheng; Heng Zhang; Henggang Wang; Shang Gao; Si Li; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2025)

Enhanced infrared radiation of zirconate ceramics via doping engineering for high-efficiency heat transfer - Xin-Yan Li; Hui Zhang; Jun Ma; Guo-Shan Zhang; Bao-Hua Liu; Cheng-Yu He; Zhong-Wei Lu; Xiang-Hu Gao (Chemical Engineering Journal, 2025)

A Li-ion permeable poly(phenylene ether-ether-sulfone) interphase to address interfacial instability and structural degradation of Ni-rich NCM cathodes in poly(ethylene oxide)-based all-solid-state Li-ion batteries - Cheng-Hung Liao; Yu-Ting Weng; Senthil-Kumar Parthasarathi; Hsi Chen; Shu-Jui Chang; Guan-Yi Liu; Tsung-Yu Yu; Chih-Wen Pao; Ting-Shan Chan; Wei-Tsung Chuang; Chun-Chieh Wang; Ru-Jong Jeng; et al. (Chemical Engineering Journal, 2025)

Dynamic in situ counting of farmed Holothurians based on improved YOLOv8s-ByteTrack - Ke-Xin Liu; Fang Wang; Sheng-Cheng Hong; Jun-Yi Wang; Xin-Yu Zheng; Yuan-Shan Lin (Aquaculture International, 2025)

Latitudinal and Biome‐Specific Declines in Ecosystem Respiration Temperature Sensitivity Under Climate Change - Weiwei Lü; Baohua Zhang; Xia Jiang; Xin Yao; Fangang Meng; Yanlong Liu; Jinye Wang; Jianhang Sun; Yanxuan Shan; Guiqing Li; Shucong Cheng (Journal of Biogeography, 2025)
Aim This study aims to systematically analyse global variations in ecosystem respiration (ER) and its temperature sensitivity ( S T ) from 1983 to 2100; overcome the geographical bias in traditional research; and refine global carbon models to prioritise conservation efforts for high‐sensitivity ecosystems. Location World‐wide. Time Period From 1983 to 2100. Major Taxa Studies The research examines various biomes, with specific emphasis on wetlands, savannas, and the analysis of latitudinal gradients across mid–high latitudes to understand ecosystem adaptations to temperature extremes. Methods The study integrates flux‐tower measurements, satellite remote sensing and CMIP6 climate model projections. Mixed‐effects models and Boltzmann–Arrhenius function fitting are used for ER‐ST analysis. Results Global ER generally shows an upward trend, while ER‐ S T declines due to adaptive ecosystem changes and different emission scenarios. Under SSP1–2.6, S T stabilises until 2030 before decreasing (−0.0009 eV/year), while SSP2–4.5 and SSP5–8.5 show consistent declines (−0.0003 and −0.0009 eV/year, respectively). Wetlands exhibit the highest S T (0.58 eV flux‐tower; 0.57 eV satellite), contrasting sharply with savannas (0.08 eV). Satellite‐derived data resolve spatial biases in ground networks, uncovering tropical and polar dynamics critical for carbon‐cycle accuracy. Main Conclusions The biome‐specific and latitudinal disparities challenge assumptions of uniform temperature responses, urging regionally tailored mitigation strategies. The findings underscore the necessity of integrating multi‐source data to refine global carbon models and prioritise conservation efforts for high‐sensitivity ecosystems like wetlands. This study advances predictive frameworks for climate resilience, emphasising adaptive management to stabilise carbon fluxes under warming scenarios.

DeepMice: a novel protein–ligand molecular docking model based on multilevel mapping modules - Jiawei Liu; Qi Wang; Yanzhao Jin; Shuke Zhang; Ruiqiang Guo; Bo Shan; Zhaoxing Wang; Xueli Liu; Xifu Liu; Yu Cheng (Molecular Diversity, 2025)

Effects of rice straw biochar application rates on soil aggregate biogeochemistry and linkages to microbial community structure and enzyme activities - Jiajun Wu; Zichuan Li; Yong Li; Jiawen Liu; Cheng Liu; Yanjun Chai; Chao Ai; Qaiser Hussain; Marios Drosos; Shengdao Shan (Soil and Tillage Research, 2025)

Degradation-catalysis of polypropylene into liquid fuel-range iso-olefins using Zn and Ni-incorporated microporous carbon - Qing Cheng; Guanyu Zhang; Wei Li; Yuan Jiang; Ge Kong; Xin Zhang; Jin Wang; Fangqi Liu; Chun Shan; Xuesong Zhang; Lujia Han (Journal of Hazardous Materials, 2025)

Metagenomic insights into the synergistic properties and mechanisms of sludge microbial communities degrading polystyrene and polypropylene - Ying Zhou; Wei-hua Gu; Jian-feng Bai; Rui-xue Wang; Cheng-long Zhang; Yao-guang Guo; Cong Lu; Shan-ping Chen (Journal of Hazardous Materials, 2025)

Using microplastic-carbon to reassess pollution level of microplastics in urban rivers - Yifan Fan; Xiao Chen; Hongbo Su; Qi Liu; Wanlu Xu; Shunzhe Wei; Mingrui Ma; Wenlin Wang; Song Cheng; Xin Qian; Nan Shan (Journal of Hazardous Materials, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Organic matter from spent paper cooking liquor promotes the growth and quality of Chinese chives - Yan Liu; Yuechao Yang; Guiwei Wang; Xiaoqi Wang; Ping Wang; Shan Li; Jiahui Liu; Songyuan Wang; Yijie Bai; Yao Cheng (Journal of Environmental Chemical Engineering, 2025)

Biofilm-enhanced PFAS removal in constructed wetlands: Sewage sludge biochar drives adsorption and microbial synergy - Fuhao Zhang; Cheng Shen; Yaqian Zhao; Lingwei Kong; Feng Ju; Bin Ji; Yu Bon Man; Shengdao Shan; Yuliang Li; Jin Zhang (Chemical Engineering Journal, 2025)

Self-assembled g-C3N4/ZnO quantum dots Z-scheme heterojunction for effective photocatalytic methane oxidation to C1 oxygenates under mild conditions - Dingzhou Xiang; Shiqi Zhang; Guanghui Cheng; Lu Li; Xing Wang; Chenghuan Zhong; Shan Gao (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

HFIP-driven Schmidt-type reaction enables chromone-3-carbonitriles and its applications - Jia Xu; Jie Lei; Li-Xin Zhang; Shan Yu; Cheng-He Zhou; Zhi-Gang Xu; Hong-Wei Du; Zhong-Zhu Chen (Molecular Diversity, 2025)

Spatiotemporal evolution and influencing factors of Resource-Environment pressure: a case of the new Western Land-Sea corridor in China - Yan Tang; Shan Gao; Yunpei Cheng; Man Xiao; Tian Hao; Xinzhi Wang (Environment, Development and Sustainability, 2025)

Antitumor effects of Cypaliuruside F from Cyclocarya paliurus on HepG2 cells - Shan-Bin Li; Jian Zou; Tong-Shi-Yao Zhao; Bin Liang; Li-Sheng Wang; Lan-Zhen Huang; Cheng-Qin Liang; Xian-Li Zhou (Natural Product Research, 2025)

The impact of carbon trading policy on embodied carbon emission in China's construction Industry:Evidence from a quasi-natural experiment - Yi-Cheng Zhang; Jia-Bao Liu; Shan-Yong Wang (Journal of Cleaner Production, 2025)

Realizing practical use of LiNiO2 cathode in halide-based all-solid-state lithium metal batteries - Hsi Chen; Hao-Wen Liu; Yu-Cheng Lu; Pei-Jane Yu; Cheng-Hung Liao; Chun-Chieh Wang; Ting-Shan Chan; Hwo-Shuenn Sheu; Po-Ya Chang; Jeng-Lung Chen; Shu-Chih Haw; Gung-Chian Yin; et al. (Chemical Engineering Journal, 2025)

Revolutionizing plasma sprayed LSCF cathodes: Fe-induced phase restoration and enhanced electrochemical performance for high-efficiency SOFCs - Zi-Yang Chen; Xin Zhang; Yan-Neng Liang; Jiu-Tao Gao; Shan-Lin Zhang; Chang-jiu Li; Cheng-Xin Li (Chemical Engineering Journal, 2025)

Nitrate addition in different anoxic stages of acid paddy soil and the impacts on cadmium immobilization - Hanbing Meng; Shan Wang; Yang Yang; Zebin Hong; Shiwen Hu; Guojun Chen; Kuan Cheng; Tongxu Liu (Chemical Geology, 2025)

The total column of CO2 and CH4 observed in Nyingchi, Tibet, based on the ground-based portable FTIR - Changgong Shan; Wei Wang; Xiangyu Zeng; Yu Xie; Qihou Hu; Zhengwei Qian; Cheng Liu (Atmospheric Environment, 2025)

Oil and gas basin analysis based on airborne gravity and magnetic data - Yan-Xu Liu; Wen-Yong Li; Guo-Qing Ma; An-Qi Cao; Shan Gao; Ning Wang; Wen-Fen Lu; Li-Jie Wang; Cheng Yang (Applied Geophysics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Feldspar dissolution controlled by coal-measure fluids and the impacts on pore structure of tight sandstone reservoirs: The case of the Jurassic Badaowan Formation in the Junggar Basin, Northwestern China - Zhi-Cheng Cui; Ke-Lai Xi; Ying-Chang Cao; Xiang Shan; Wei-Kai Huang; Hua-Jun Guo; Bo Peng; Nian-Ming Zan (Marine and Petroleum Geology, 2025)

Screening and discovery of volatile allergenic components from artemisia ordosica in Yulin region of Northern China - Xiaoxue Mo; Cheng Wang; Yi Shan; Siqi Wang; Wen Yang; Zhaomin Xia; Zhanguo Qiao; Tao Zhang; Yuanyuan Ding; Rui Liu; Huaizhen He; Langchong He (Journal of Hazardous Materials, 2025)

3D visibility analysis of urban parks using LIDAR for enhanced accuracy - Huishan Cheng; Quanquan Rui; Kunyong Yu; Liang Shan; Yu Chen; Yu Chen; Guochang Ding; Jian Liu (Journal of Environmental Management, 2025)

Influence of galvanic interactions on heavy metal(loid) contaminated soil in karst polymetallic mining area: A review - Lu Cheng; Weiyi Xia; Xiaoyan Gong; Wei Zheng; Junyong Liu; Lishan Zhang; Shan Zhong; Bin Liu; Yuanyuan Liu (Journal of Environmental Chemical Engineering, 2025)

Seawater intrusion causes substantial release of dissolved organic carbon in coastal paddy soils - Wenting Chi; Yang Yang; Pei Wang; Chao Guo; Zebin Hong; Shiwen Hu; Kuan Cheng; Shan Wang; Han Li; Qi Wang; Ying Li; Yang Wu; et al. (Geochimica et Cosmochimica Acta, 2025)

Inorganic amendment can delay the degradation of organic amendment by enhancing its resistance and mitigating microbial activities in saline–alkali soils - Shan Li; Yuanyuan Yao; Congling Zhou; Songyuan Wang; Zihan Liu; Yan Liu; Junyin Li; Guiwei Wang; Bin Gao; Dongdong Cheng; Yuechao Yang (Applied Soil Ecology, 2025)

Polycyclic aromatic hydrocarbon-aryl hydrocarbon receptor signaling regulates chronic inflammation in lung-gut axis - Tzu-Yu Cheng; Ching-Shan Luo; Po-Hao Feng; Kuan-Yuan Chen; Chih-Cheng Chang; Nguyen Van Hiep; Yueh-His Chen; Yun-Kai Yeh; Sheng-Ming Wu (Toxicology and Applied Pharmacology, 2025)

Current status and research progress of sugarcane stem borers management - Jin-Da Wang; Huan-Tai Lin; Xian-Kun Shang; Hong-Li Shan; Ji-Hu Li; Xue-Hong Pan; Jiong Yin; Cheng-Wu Zou; Bao-Shan Chen; San-Ji Gao (European Journal of Agronomy, 2025)

Self-sourced nitrogen doping hierarchical porous carbon materials from algae-derived bio-oil distillation residues for high-performance supercapacitors - Chuan Yuan; Xiaoxue Cheng; Sherif A. El-khodary; Mao Chen; Bin Cao; Guosong Ni; Shan Zhong; Pietro Bartocci; Shuang Wang (Chemical Engineering Journal, 2025)

Algae-based biotransformation of COVID-19 antiviral ribavirin: Insight on metabolic effect, wastewater application and biological toxicity - Yongtao Cheng; Chenxi Zhou; Kang Shan; Yong Liu; Chuanyue Peng; Yuanyuan Wu; Jun Liu; An Xu; Ying Liu (Bioresource Technology, 2025)

Predation of Macaca cyclopis on flying bees - Ai-Ching Meng; Tien Hsieh; Sheng-Shan Lu; Hsi-Cheng Ho (Primates, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Short-term PS-NP exposure in early adulthood induces neuronal damage in middle-aged mice via microglia-mediated neuroinflammation - Shan Shan; Dong Cheng; Hui Li; Wenhuan Yao; Ruirui Kou; Jing Ji; Na Liu; Tao Zeng; Xiulan Zhao (Journal of Hazardous Materials, 2025)

Investigation on reaction kinetics and thermodynamic performances of methanol steam reforming hydrogen production directly driven by solar radiation - Ziying Cheng; Shiquan Shan; Guijia Zhang; Haojin Wu; Jialu Tian; Zhijun Zhou; Zhihua Wang; Kefa Cen (Fuel, 2025)

Fabrication of sesamin-loaded sodium caseinate nanoparticles: Insight to characterization, in vitro digestion, and molecular docking analysis - Wan-Yi Liu; Tzu-Yu Chen; Yun-Shan Hsieh; Yung-Yi Cheng; Shiou-Ling Li; Li-Ching Chang; Yu-Tse Wu (Food Bioscience, 2025)

Enhanced thermotolerance via overexpression of a stromal ascorbate peroxidase in Nannochloropsis oceanica - Shan Wu; Yiting She; Xitao Chen; Xingwei Huang; Tao Xu; Congcong Miao; Qianyi Wu; Zheng Li; Chengcheng Li; Yuhui Cheng; Yi Xin (Plant Cell Reports, 2025)

Association Between the Uric Acid to High-Density Lipoprotein Cholesterol Ratio and Residual Risk for Coronary Artery Disease - Shan Zhong; Siqi Wang; Peng Zhao; Minghui Piao; Cheng Jin; Jinwei Tian (Cardiovascular Toxicology, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Overexpression of FvGCN5 enhances the resistance of woodland strawberry against Botrytis cinerea - Miao Yu; Jiaqi Zhang; Feifei Bai; Yihan Gao; Shan Jiang; Hui Liu; Aisheng Xiong; Zongming Cheng; Jinsong Xiong (Journal of Plant Physiology, 2025)

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Metabolic profiling and evaluation of antioxidant and anti-inflammatory properties of Apis cerana cerana Honey from Sansha City, Hainan Province, China - Jiao Wu; Xiang-Tan Xu; Cheng Xing; Xin-Bao Hao; Xing-Yue Fang; Zhi-Hao Xie; Shan Zhao; Jing-Lin Gao; Lu Xu; Shi-Jie Wang (Food Chemistry, 2025)

Mycoplasma ovipnuemoniae impairs the immune response of sheep and suppresses neutrophil function by inhibiting S100A9 - Chenbo Yan; Tianning Dong; Yiyi Shan; Bingru Zhao; Hua Yang; Yu Cai; Shanglai Li; Qiuyue Liu; Yuefeng Chu; Huafang Hao; Zilong Cheng; Maojun Liu; et al. (Veterinary Microbiology, 2025)

Promotional role of Ru in bimetallic catalysts for selective transfer hydrogenation of bio-based furfural - Yaoxin Xiao; Yazhuo Wang; Jun Zhang; Gangqi Cheng; Dong Liang; Rui Shan; Haoran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Selective preparation of aromatic compounds from catalytic pyrolysis polyester coating over Ni, Mo and Co metal modified ZSM-5 - Zhen-Qiang Yu; Yao-Xin Xiao; Dong Liang; Che Zhao; Zhen Huang; Gang-Qi Cheng; Rui Shan; Hao-Ran Yuan; Yong Chen (Journal of Environmental Chemical Engineering, 2025)

Quantitative analysis of β-carotene and unsaturated fatty acids in blended olive oil via Raman spectroscopy combined with model prediction - Yulong Chen; Zhihan Yang; Shan Zeng; Hui Tian; QingZhou Cheng; Site Lv; Hao Li (Food Chemistry, 2025)

Lactic acid bacteria-mediated transformation of black tea extract: Insights into metabolite profile and sensory characteristics - Zhi-Peng Cheng; Yao-Zeng Zhang; Zhong-Zheng Guan; Rui-shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2025)

The investigation of the mechanism underlying variations in oxidative stress tolerance of Lacticaseibacillus paracasei resulting from fermentation methods through endogenous CRISPR-Cas9 editing methodology - Pengyu Wu; Yutian Zhang; Qiantong Shan; Ziyang Wang; Shuang Cheng; Laiyou Wang; Bingbing Liu; Wenhuan Li; Zhenmin Chen; Jiancheng Luo; Yunxiang Liang (Food Microbiology, 2025)

Estimating wastewater emissions and environmental levels of typical organic contaminants based on regionalized modelling - Rui-Xin Qin; Cheng-Zhong Fu; Li Zhuo; Shi-Yi Zhang; Feng-Shan Cai; Kai-Yi Wu; Xiao Yan; Wei-Keng Luo; Min Li; Yun-Gang Shi; Bin Tang (Environmental Research, 2025)

Characterization of intestinal bacteria for the production of quercetin and isoquercitrin from rutin - Narantsetseg Byambaakhuu; Shen Duan; Ren Sa; Qing-lan Yang; Hai-Yan Xu; Cheng-Bin Shan; Ri-hua Xu; Chao-Mei Ma (Archives of Microbiology, 2025)

Harvesting rice straw management synergies for lifecycle environmental and economic sustainability - Suraj Negi; Yu-Chi Cheng; Shan-Li Wang; Shuay-Tsyr Ho; Shu-Yuan Pan (Science of The Total Environment, 2025)

NAT10 primes a post-transcriptional repertoire essential for the maintenance of spermatogonial homeostasis - Xiaoli Zhu; Caoling Xu; Xue Jiang; Jiaqi Zou; Wenqing Li; Xuemei Xing; Xiaoxiao Gao; Jiao Lei; Fei Meng; Xin Wang; Yuzhang Zhu; Yu Cheng; et al. (Science Bulletin, 2025)

Selective production of olefins from methanol over a heteroatomic SAPO-34 zeolite - Zhaodong Zhu; Mengtian Fan; Meng He; Bing An; Yinlin Chen; Shaojun Xu; Tianze Zhou; Alena M. Sheveleva; Meredydd Kippax-Jones; Lutong Shan; Yongqiang Cheng; Hamish Cavaye; et al. (Science Bulletin, 2025)

Synthesis of floral spherical porous carbon materials from heavy bio-oil for efficient green energy storage - Mao Chen; Chuan Yuan; Bin Cao; Sivakumar Esakkimuthu; Xiaoxue Cheng; Shan Zhong; Shuang Wang; Guosong Ni (Process Safety and Environmental Protection, 2025)

Voagafries A–E, undescribed indole alkaloids with anti-glioma activity from Voacanga africana - Cai-Feng Ding; Ma-Long Qin; Kun-Ying Zhao; Wen Gao; Shan-Ze Yin; Xian-Guang Hu; Gui-Guang Cheng; Rong-Ping Zhang; Wei-Yan Hu (Phytochemistry, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Enhancing NH3-SCR denitrification performance through synergistic A- and B-site effects via CeFe modification of LaMnO3 - Wei Zhang; Qiao Wu; Mengyao Dong; Kang Xie; Yanshan Yin; Yunhe Zhou; Jie Li; Yehao Fu; Yaocheng Liang; Quanbin Song; Min Ruan; Shan Cheng; et al. (Fuel, 2025)

Synthesis and characterization of fish gelatin hydrogels for enhanced biopolymer applications - Wen-Long Cheng; Shan Shan; Sheng Shu; Guang-Xian Liu; Lin-Feng Yuan; Xiao-Mei Sha; Zong-Cai Tu (Food and Bioproducts Processing, 2025)

Axial compressive behaviors of the curved steel-plate composite walls with small curvature radius-to-section thickness ratio - Lanhui Guo; Cheng Liu; Shan Gao; Yue Yu (Engineering Structures, 2025)

Highly selective ppb-level Cl2 sensor at room temperature based on ZIF-8 coated MIL-68(In)-derived hexagonal tubes - Sumin Wang; Rui Gao; Ming Zheng; Xianfa Zhang; Xiaoli Cheng; Yingming Xu; Shan Gao; Xin Zhou; Lihua Huo (Chemical Engineering Journal, 2025)

Lateral residual stress effect on the swelling pressure of compacted expansive soil and microscopic mechanism - Zhang-Jun Dai; Zi-Hang Liu; Ze-Cheng Chi; Wei Wang; Kang Huang; Shan-Xiong Chen (Bulletin of Engineering Geology and the Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Genetic Mechanism Analysis Related to Cold Tolerance of Red Swamp Crayfish, Procambarus clarkii - Jihu Zhang; Cheng-long Zhang; Hong Ju Chen; Xiang Shan Ji; Yan Zhao (Marine Biotechnology, 2025)

Correction: Associations Between Heavy Metal Exposure from Milk and Steroid Hormones in Mothers - Zheng Wang; Caixia Liang; Li Li Shi; Cheng-Sheng Zhu; Shenghang Wang; Shoji F. Nakayama; Teruhiko Kido; Xian Liang Sun; Jiancong Shan (Biological Trace Element Research, 2025)

Preparation of Carbon Dots with High Fluorescence Quantum Yields and its Detection of Hg2+ in Simulated Wastewater - Hui Wang; Li Han; Yan Gao; Xing Gao; Wen He; Chaoyue Shan; Weixi Fan; Yingkai Guo; Meng Gao; Haidi Cheng (Journal of Fluorescence, 2025)

Changes of Yancheng coastline near 20 years based on remote sensing technology - Yu Song; Shuang Yang; Dongxu Li; Yubao Shao; Jie Cheng; Xingxing Shan; Li Cao; Silong Li; Chao Xie; Li Shan; Delong Tian; Hao Wang; et al. (Marine Georesources & Geotechnology, 2025)

Challenges of quaternary ammonium antimicrobial agents: Mechanisms, resistance, persistence and impacts on the microecology - Jiaxin Zhang; Lei Cheng; Hao Li; Xi Chen; Lin Zhang; Tiantian Shan; Jiannan Wang; Ding Chen; Jiawei Shen; Xinxuan Zhou; Lichen Gou; Lixin Zhang; et al. (Science of The Total Environment, 2025)

Glycerophospholipid metabolic disorders and gender difference of cantharidin-induced hepatotoxicity in rats: Lipidomics and MALDI mass spectrometry imaging analysis - Qiyi Wang; Weina Cheng; Tianmu He; Shan Li; Jingwen Ao; Yanmei He; Cancan Duan; Xiaofei Li; Jianyong Zhang (Chemico-Biological Interactions, 2025)

Associations Between Heavy Metal Exposure from Milk and Steroid Hormones in Mothers - Zheng Wang; Caixia Liang; Li Li Shi; Cheng-Sheng Zhu; Shenghang Wang; Shoji F. Nakayama; Teruhiko Kido; Xian Liang Sun; Jiancong Shan (Biological Trace Element Research, 2024)

Regionalized ensemble estimation of wave periods for assessing wave energy resources across Canada. Part II: Wave-period and wave-energy analyses - Cong Dong; Gordon Huang; Guanhui Cheng; Yanpeng Cai; Jinxin Zhu; Shan Zhao (Ocean & Coastal Management, 2024)

Regionalized ensemble estimation of wave periods for assessing wave energy resources across Canada. Part I: Improved wave-period modelling methodology - Cong Dong; Gordon Huang; Guanhui Cheng; Yanpeng Cai; Jinxin Zhu; Shan Zhao (Ocean & Coastal Management, 2024)

Study on the effect of conditioner on NO precursor control behavior from sewage sludge pyrolysis: Focusing on conditioner assessments and in-situ fixation mechanism - Shan Cheng; Ting Yang; Jingchun Huang; Hong Tian; Wei Zhang; Feng Xin; Yu Qiao (Waste Management, 2024)

Evaluating the influence of alternating flooding and drainage on antimony speciation and translocation in a soil-rice system - Zhao Chen; Bingqing Xia; Yang Yang; Shiwen Hu; Kuan Cheng; Pengfei Cheng; Shan Wang; Guojun Chen; Qi Wang; Haibo Dong; Chao Guo; Yating Chen; et al. (Science of The Total Environment, 2024)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

Optimized model-free adaptive load mitigation control for offshore floating wind turbines using Bayesian techniques - Jiawang Yuan; Shan He; Zhijiang Cheng; Bing Hu; Chunyu Ai (Ocean Engineering, 2024)

Economic benefit analysis of the application of eco-friendly aquaculture technology in the farming of groupers and the fourfinger threadfin - Ann‐Chang Cheng; Tsung-Yu Yang; Chien-Hsiang Lai; Yi-Shan Li; Yu-Fang Luo; Hsiang-Chieh Chuang (Journal of Environmental Management, 2024)

Fabrication of high internal phase emulsions (HIPEs) using pea protein isolate-hyaluronic acid-tannic acid complexes: Application of curcumin-loaded HIPEs as edible inks for 3D food printing - Zhiying Li; Liwen Zhang; Yuehan Shan; Yue Zhao; Lei Dai; Yanfei Wang; Qingjie Sun; David Julian McClements; Yongqiang Cheng; Xingfeng Xu (Food Chemistry, 2024)

Perfluoroalkyl substances exposure and the risk of breast cancer: A nested case-control study in Jinchang Cohort - Qian Dou; Yana Bai; Yongjun Li; Shan Zheng; Minzhen Wang; Zhongge Wang; Jianyun Sun; Desheng Zhang; Chun Yin; Li Ma; Yongbin Lu; Lizhen Zhang; et al. (Environmental Research, 2024)

Vacancy and bonding engineering of rhenium (Re)-based dichalcogenides materials in photoelectrodes: From design and construction to properties - Ming-Kun Jiang; Yu-Xin Liu; Shan-Shan Kan; Shi-Xuan Deng; Zhe-Kun Ren; Xiao-Meng Jiang; Cheng-Bao Yao (Chemical Engineering Journal, 2024)

A comparative study on the stability of Fe(III) minerals formed by the nitrate/nitrite-reducing Fe(II) oxidation processes - Kuan Cheng; Zesheng Yang; Guojun Chen; Shiwen Hu; Chao Guo; Yang Yang; Shan Wang; Ying Wang; Haibo Dong; Milan Wang; Pengfei Cheng; Tongxu Liu (Chemical Geology, 2024)

Impact of acid washing and torrefaction on biomass pyrolysis characteristics and product distribution - Hong Tian; Xiaodie Zhang; Xiong Gao; Zhen Zhou; Shan Cheng; Chenyang Sun (Biomass and Bioenergy, 2024)

A comprehensive genome-based analysis identifies the anti-cancerous role of the anoikis-related gene ADH1A in modulating the pathogenesis of breast cancer - Cheng Chen; Shan Guo; Wenying Chai; Jun Yang; Ying Yang; Guimin Chen; Haishan Rao; Yun Ma; Song Bai (Molecular Genetics and Genomics, 2024)

Melatonin antagonizes oxidative stress-induced apoptosis in retinal ganglion cells through activating the thioredoxin-1 pathway - Shan Gao; Qiaochu Cheng; Yaguang Hu; Xiaojuan Fan; Chen Liang; Chen Niu; Qianyan Kang; Ting Wei (Molecular and Cellular Biochemistry, 2024)

Dedolomitization arises the knife-like structure of dolostone: insights from the oolitic dolostone of Cambrian Zhangxia formation, North China Craton - Zhe-Xin Cai; Shan-Shan Li; Yi-Ning He; Tao Cui; Xin-Yu Wu; Hao-Cheng Yu; Zhao-Liang Hou; Yu-Tian Tao; Da Wang; Kun-Feng Qiu (Carbonates and Evaporites, 2024)

Role of polylactic acid microplastics during anaerobic co-digestion of cow manure and Chinese cabbage waste enhanced by nanobubble - Peilin Guo; Tianfeng Wang; Jie Wang; Jiazi Niu; Cheng Peng; Jiabei Shan; Yu Zhang; Haizhou Huang; Jixiang Chen (Chemosphere, 2024)

Microplastics and biochar interactively affect nitrous oxide emissions from tobacco planting soil - Feier Wang; Hongguang Cheng; Shan Lin; Gratien Twagirayezu; Hengbin Xiao; Cai Gan; Jinli Hu; Yan Wang; Ronggui Hu (Science of The Total Environment, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

T cell senescence may contribute to immunothrombosis via Th17 immune transition in COVID-19 - Wenxing Li; Rui Qian; Zhaoming Zhou; Lei Wen; Quan Yin; Xiang Zhou; Xiaowei Li; Jie Cheng; Xinlu Zhang; Xin Zeng; Zhuoya Wang; Yingying Huang; et al. (Science Bulletin, 2024)

Mapping fine-scale carbon sequestration benefits and landscape spatial drivers of urban parks using high-resolution UAV data - Huishan Cheng; Yihan Wang; Liang Shan; Yu Chen; Kunyong Yu; Jian Liu (Journal of Environmental Management, 2024)

Biochar addition under straw return reduces carbon dioxide and nitrous oxide emissions in acidic tea field soil - Ziwei Yan; Shuirong Tang; Zhilong He; Hongguang Cheng; Gratien Twagirayezu; Jinsong Zhao; Rongbiao Xiang; Ronggui Hu; Shan Lin (Journal of Environmental Management, 2024)

Monoclonal antibody based colloidal gold immunochromatographic assay for the visual and rapid screening of profenofos - Ri-Sheng Chen; Jian-Cheng Yuan; Chong-Lan Luo; Yu Wang; Zi-Jian Chen; Ze-Shan Lin; Zhen-Lin Xu (Environmental Pollution, 2024)

Mycotoxin zearalenone induces multi-/trans-generational toxic effects and germline toxicity transmission via histone methyltransferase MES-4 in Caenorhabditis elegans - Yong-Shan Li; Chia-Cheng Wei (Environmental Pollution, 2024)

Pyrrole adducts mediated mitochondrial dysfunction activates SARM1-dependent axon degeneration in 2,5-hexanedione-induced neuropathy - Wenting Ni; Yihan Ye; Shuai Wang; Xianjie Li; Hui Li; Dong Cheng; Qiang Jia; Zhidan Liu; Shulin Shan; Yalong Qiang; Shihua Chao; Xiulan Zhao; et al. (Environmental Pollution, 2024)

Bioaerosols emission from source facilities in a wastewater treatment plant: Critical exposure time and sensitivity analysis - Yi-ning Hu; Wei-di Wan; Jun-ting Wu; Tian-nuo Lai; Wajid Ali; Shan-shan He; Sai Liu; Xiang Li; Zhe-ren Tang; Cheng-yun Wang; Cheng Yan (Environmental Pollution, 2024)

Metal-organic frameworks derived curled sheet-like Cu2O/CuO heterostructure: Low-power N2H4 sensing - Ting Li; Rui Gao; Xianfa Zhang; Xiaoli Cheng; Baosheng Li; Yingming Xu; Shan Gao; Lihua Huo (Chemical Engineering Journal, 2024)

Balancing bio-oil quality and yield during rapid pyrolysis of Miscanthus using ZSM-5 and metal oxides - Hong Tian; Huang Zhang; Zhangjun Huang; Xueliang Guo; Shan Cheng; Yang Yang; Yi Cheng; Jiawei Wang (Biomass and Bioenergy, 2024)

The single-cell transcriptomic landscape of the topological differences in mammalian auditory receptors - Xiangyu Ma; Xin Chen; Yuwei Che; Siyao Zhu; Xinlin Wang; Shan Gao; Jiheng Wu; Fanliang Kong; Cheng Cheng; Yunhao Wu; Jiamin Guo; Jieyu Qi; et al. (Science China Life Sciences, 2024)

Correction to: Effects of Long-term Climate Change on Typhoon Rainfall Associated with Southwesterly Monsoon Flow near Taiwan: Mindulle (2004) and Morakot (2009) - Chung-Chieh Wang; Li-Shan Tseng; Chien-Chang Huang; Pi-Yu Chuang; Nan-Chou Su; Cheng-Ta Chen; Shih-How Lo; Kazuhisa Tsuboki (Asia-Pacific Journal of Atmospheric Sciences, 2024)

Trifluoro-Icaritin Ameliorates Neuroinflammation Against Complete Freund’s Adjuvant-Induced Microglial Activation by Improving CB2 Receptor-Mediated IL-10/β-endorphin Signaling in the Spinal Cord of Rats - Guangsen Liu; Dandan Jia; Weiwei Li; Zhihua Huang; Reai Shan; Cheng Huang (Journal of Neuroimmune Pharmacology, 2024)

Ubiquity and ecological risks of conjugated steroids cannot be overlooked: First evidence from estuarine sediments - Fei Tian; Shan Liu; Ru Xu; Nian-Nian Wu; Shuang-Shuang Liu; Yuan-Yue Cheng; Qian Xiong; Zhen-Zhao Tang; Lin-Bao Zhang; Zhe Zhang; Hai-Gang Chen (Marine Pollution Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Stabilizing methyl ferulate with nanosystem enhances its antifungal activity against Alternaria alternata in vitro and in vivo - Saiqing Xu; Shuai Ge; Ying Xie; Jing Cheng; Ke Ding; Huan Li; Hua Huang; Zisheng Luo; Yang Shan; Shenghua Ding (Postharvest Biology and Technology, 2024)

Boosting peroxodisulfate activation by MIL-68(Fe) derived magnetic Fe3S4 nanosheets: Key role of sulfur vacancy - Feiyang Luo; Cheng Peng; Xinyu Chen; Wenjun Quan; Guohua Du; Jingjing Zhao; Xiaoxu Bo; Shaoyun Shan; Xinggen Yuan; Yanyan Deng; Tianding Hu (Journal of Environmental Chemical Engineering, 2024)

Cu inanchored MnO/carbonaceous frameworks trigger peroxymonosulfate activation for enrofloxacin degradation: ROS generation and pollutant attacking processes - Huai-Yuan Niu; Zheng-Tao Dong; Hai Guo; Ya-Ya Yang; Wen-Jie Yang; Ming Yan; Cheng-Gang Niu; Ji-Shan Li (Journal of Environmental Chemical Engineering, 2024)

Spur development and evolution: An update - Shuixian Li; Jiannan Fan; Cheng Xue; Hongyan Shan; Hongzhi Kong (Current Opinion in Plant Biology, 2024)

Mechanistic Insights and Potential Therapeutic Implications of NRF2 in Diabetic Encephalopathy - Xin Cheng; Yejun Tan; Hongli Li; Zhen Zhang; Shan Hui; Zheyu Zhang; Weijun Peng (Molecular Neurobiology, 2024)

Photoelectron‐promoted metabolism of sulphate‐reducing microorganisms in substrate‐depleted environments - Chao Zhong; Anhuai Lu; Hailiang Dong; Shan Huang; Liang Shi; Yanan Shen; Yangjian Cheng; Yiran Dong; Xiangzhen Li; Jie Xu; Jinren Ni; Michael F. Hochella; et al. (Environmental Microbiology, 2024)
Sulphate‐reducing microorganisms, or SRMs, are crucial to organic decomposition, the sulphur cycle, and the formation of pyrite. Despite their low energy‐yielding metabolism and intense competition with other microorganisms, their ability to thrive in natural habitats often lacking sufficient substrates remains an enigma. This study delves into how Desulfovibrio desulfuricans G20, a representative SRM, utilizes photoelectrons from extracellular sphalerite (ZnS), a semiconducting mineral that often coexists with SRMs, for its metabolism and energy production. Batch experiments with sphalerite reveal that the initial rate and extent of sulphate reduction by G20 increased by 3.6 and 3.2 times respectively under light conditions compared to darkness, when lactate was not added. Analyses of microbial photoelectrochemical, transcriptomic, and metabolomic data suggest that in the absence of lactate, G20 extracts photoelectrons from extracellular sphalerite through cytochromes, nanowires, and electron shuttles. Genes encoding movement and biofilm formation are upregulated, suggesting that G20 might sense redox potential gradients and migrate towards sphalerite to acquire photoelectrons. This process enhances the intracellular electron transfer activity, sulphur metabolism, and ATP production of G20, which becomes dominant under conditions of carbon starvation and extends cell viability in such environments. This mechanism could be a vital strategy for SRMs to survive in energy‐limited environments and contribute to sulphur cycling.

Study on the measurement and prediction of the ecological structure for water efficiency in China: from the perspective of “production-living-ecological” function - Yan Tang; Yunpei Cheng; Shan Gao; Xinzhi Wang (Environment, Development and Sustainability, 2024)

Cytotoxic xanthanolide sesquiterpenes from the fruits of Xanthium italicum Moretti - Yu-Tong Li; Cheng-Yong Tan; Jiang Fu; Hai-Qiang Wang; Yun-Bao Liu; Shuang-Gang Ma; Yong Li; Jing Qu; Shi-Shan Yu (Phytochemistry, 2024)

Wastewater-based epidemiology to monitor 68 NPS/conventional drug use in Taipei metropolitan area in Taiwan during and after COVID-19 pandemic - Te-Tien Ting; Pin-Chuan Chen; Ya-Chi Chang; Pin-Ju Chiang; Hsu-Cheng Li; Shih-Hsun Chen; Pei-Chieh Chen; Hai-Tien Chu; Ping-Yu Chuang; Yi-Hsin Liu; Pai-Shan Chen (Journal of Hazardous Materials, 2024)

Effects of biodegradable microplastics and straw addition on soil greenhouse gas emissions - Ziwei Yan; Shan Lin; Ronggui Hu; Hongguang Cheng; Rongbiao Xiang; Han Xu; Jinsong Zhao (Environmental Pollution, 2024)

Nontoxic and proteolytic-resistant self-assembled peptide dendrimer aggregates to combat multidrug-resistant gram-negative bacterial infections - Zhenheng Lai; Xiaojie Yuan; Guoyu Li; Hongyu Chen; Baojing Cheng; Anshan Shan (Chemical Engineering Journal, 2024)

Corrigendum to “Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots” [Chem. Eng. J. 486 (2024) 150196] - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Microplastics in Hong Kong's marine waters: Impact of rainfall and Pearl River discharge - Kai Zhang; Michael C.Y. Cheng; Mengyang Liu; Shaopeng Xu; Yue Ma; Hoi Shan Chau; Luoluo Chen; Yaru Cao; Meng Yan; Xiangrong Xu; Wai Thoe; Sunny W.C. Sun; et al. (Marine Pollution Bulletin, 2024)

Effects of low frequency ultrasound treatment on dissolved organic nitrogen removal by biological activated carbon: Critical insights into molecular characteristics, microbial traits, and metabolism - Congcong Li; Cheng Liu; Yiwen Shan; Tong Lan (Water Research, 2024)

The application of a high-density street-level air temperature observation network (HiSAN): Spatial and temporal variations of thermal and wind condition in different climatic condition types - Yu-Cheng Chen; Kai-Shan Hou; Yu-Jie Liao; Tsuyoshi Honjo; Fang-Yi Cheng; Tzu-Ping Lin (Sustainable Cities and Society, 2024)

A review of amendments for simultaneously reducing Cd and As availability in paddy soils and rice grain based on meta-analysis - Frank Stephano Mabagala; Ting Zhang; Xibai Zeng; Chao He; Hong Shan; Cheng Qiu; Xue Gao; Nan Zhang; Shiming Su (Journal of Environmental Management, 2024)

Rapid pretreatment strategy to control nanofiltration membrane fouling in recycling of real textile wastewater: Comparison and mechanisms - Hai Tang; Meng Shan; Qiyao Cheng; Ruiting Wen; Shasha Liu; Haiao Zeng; Jingfu Yu; Jianquan Luo (Chemical Engineering Journal, 2024)

In-situ controllable preparation of ZIF-8-wrapped ZnO heterojunction nanorods array for ppb-level Cl2 detection operated at near room temperature - Xiaoqian Meng; Rui Gao; Ming Zheng; Xin Zhou; Xianfa Zhang; Xiaoli Cheng; Yingming Xu; Shan Gao; Lihua Huo (Chemical Engineering Journal, 2024)

DENND1A desensitizes granulosa cells to FSH by arresting intracellular FSHR transportation - Yunde Dou; Rusong Zhao; Han Wu; Zhiheng Yu; Changjian Yin; Jie Yang; Chaoyan Yang; Xiaohua Luan; Yixiao Cheng; Tao Huang; Yuehong Bian; Shan Han; et al. (Science China Life Sciences, 2024)

Hexavalent chromium transformation during transport of L − cysteine modified nano − zero − valent iron supported by biochar via green synthesis in water and soil systems - Congcong Cheng; Haijun Chen; Nan Xu; Shan Zhang (Journal of Soils and Sediments, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

High coking resistance of Ni/A2Ti2O7 catalysts via modulating the A site of A2Ti2O7 (A = La, Gd) for dry reforming of methane - Zheng Liu; Lu-Yang Qiao; Zhang-Feng Zhou; Shan-Shan Zong; Xin-Yi Cao; Jian-Kai Cheng; Yuan-Gen Yao (Fuel, 2024)

Molten salts coupled Ni/Al2O3 for hydrogen from CH4 pyrolysis at mild temperature in bubble-cap reactor - Cheng Wang; Fengsheng Zhan; Shan Wang; Yi Wei; Jianbing Ji (Fuel, 2024)

Gelation of crocodile myofibrillar protein – κ-carrageenan mixtures in two low-NaCl solution - Qiu Qin Zhang; Jing Tang; Ying Feng Wu; Cheng Yu Qian; Shan Qin; Zi Hang Cai; Hui Wang; Hong Mei Xiao (Food Chemistry, 2024)

Recycling of expired cow milk for constructing multifunctional biomass nonfluorinated chromatic paint with superhydrophobicity - Cheng Chen; Chenchen Gao; Kaige Lin; Jing Zhang; Zhiwei Zhang; Yifan Jing; Yuanshu Xiao; Guohua Shan; Cheng Xie (Chemical Engineering Journal, 2024)

Optimization of straw supply chain considering carbon emissions, supply uncertainty and facility disruption risk - Jia Mao; Yanzhi Zhou; Lijie Shan; Jinyuan Cheng (Environment, Development and Sustainability, 2024)

The Type Strain of Bifidobacterium indicum Scardovi and Trovatelli 1969 (Approved Lists 1980) is ATCC 25912, not DSM 20214, and Rejection to Reclassify Bifidobacterium coryneforme as Bifidobacterium indicum - Cheng-Shan Jiang; Chun Yan Li; Chun Tao Gu (Current Microbiology, 2024)

Comparative analysis of the growth performance, vitality, body chemical composition and economic efficiency of the main cultivated strains of Pacific white shrimp (Litopenaeus vannamei) in coastal areas of China - Cheng Zhang; Chun-Yang Guo; Kai-He Shu; Shan-Liang Xu; Dan-Li Wang (Aquaculture, 2024)

CD200R promotes high glucose-induced oxidative stress and damage in human retinal pigment epithelial cells by activating the mTOR signaling pathway - Yaguang Hu; Ting Wei; Shan Gao; Ning Gao; Li Chen; Qiaochu Cheng (Tissue and Cell, 2024)

Testing the moderated mediation effect of recreation safety climate on the interrelationship of serious leisure, recreation involvement, and flow experience - Tien-Ming Cheng; Ching-Yi Hsu; Shan-Ni Li (Journal of Outdoor Recreation and Tourism, 2024)

Bioactive peptides in dry-cured ham: A comprehensive review of preparation methods, metabolic stability, safety, health benefits, and regulatory frameworks - Yao-yao Hu; Shan Xiao; Gui-cheng Zhou; Xuan Chen; Bo Wang; Ji-hui Wang (Food Research International, 2024)

The effects of repeated freezing and thawing on bovine sperm morphometry and function - Chang-Guo Min; Xin Ma; Yu-Chan Wang; Cheng-Kun Zhong; Chong-shan Yuan; Kai-Yan Zhang; Cheng-Lin Zhan; Sheng-Kui Hou; Xin-Hai Wang; Jun Wang; Jing Zhao; Yi Fang; et al. (Cryobiology, 2024)

A freestanding rotating triboelectric nanogenerator with large area and high efficiency for triboelectric plasma CO2 reduction - Hongjie Cao; Qinglong Ru; Dongyang Fang; Sumin Li; Nannan Liu; Wei Jiang; Hui Hu; Yongcui Yang; Guangqin Gu; Bao Zhang; Gang Cheng; Sanjun Yang; et al. (Chemical Engineering Journal, 2024)

Effects of Long-term Climate Change on Typhoon Rainfall Associated with Southwesterly Monsoon Flow near Taiwan: Mindulle (2004) and Morakot (2009) - Chung-Chieh Wang; Li-Shan Tseng; Chien-Chang Huang; Pi-Yu Chuang; Nan-Chou Su; Cheng-Ta Chen; Shih-How Lo; Kazuhisa Tsuboki (Asia-Pacific Journal of Atmospheric Sciences, 2024)

A Review on Submarine Geological Risks and Secondary Disaster Issues during Natural Gas Hydrate Depressurization Production - Xianzhuang Ma; Yujing Jiang; Peng Yan; Hengjie Luan; Changsheng Wang; Qinglin Shan; Xianzhen Cheng (Journal of Marine Science and Engineering, 2024)
The safe and efficient production of marine natural gas hydrates faces the challenges of seabed geological risk issues. Geological risk issues can be categorized from weak to strong threats in four aspects: sand production, wellbore instability, seafloor subsidence, and submarine landslides, with the potential risk of natural gas leakage, and the geological risk problems that can cause secondary disasters dominated by gas eruptions and seawater intrusion. If the gas in a reservoir is not discharged in a smooth and timely manner during production, it can build up inside the formation to form super pore pressure leading to a sudden gas eruption when the overburden is damaged. There is a high risk of overburden destabilization around production wells, and reservoirs are prone to forming a connection with the seafloor resulting in seawater intrusion under osmotic pressure. This paper summarizes the application of field observation, experimental research, and numerical simulation methods in evaluating the stability problem of the seafloor surface. The theoretical model of multi-field coupling can be used to describe and evaluate the seafloor geologic risk issues during depressurization production, and the controlling equations accurately describing the characteristics of the reservoir are the key theoretical basis for evaluating the stability of the seafloor geomechanics. It is necessary to seek a balance between submarine formation stability and reservoir production efficiency in order to assess the optimal production and predict the region of plastic damage in the reservoir. Prediction and assessment allow measures to be taken at fixed points to improve reservoir mechanical stability with the numerical simulation method. Hydrate reservoirs need to be filled with gravel to enhance mechanical strength and permeability, and overburden need to be grouted to reinforce stability.

Remediation of cadmium-contaminated soil using modified activated carbon fiber combined with electrodynamic remediation technology - Dao-lin Zhou; Yue Cheng; Yu-shan Wan (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)

Material and microbial perspectives on understanding the role of biochar in mitigating ammonia inhibition during anaerobic digestion - Zhi-Jun Zhao; Xiao-Li Liu; Yi-Xuan Wang; Yan-Shan Wang; Jin-You Shen; Zhi-Cheng Pan; Yang Mu (Water Research, 2024)

Peroxymonosulfate activation by tin(IV) phosphate supported cobalt composite for acetaminophen degradation: Performance and mechanism - Shisi Deng; Zezhong Shan; Haojie Zhang; Jing Guo; Cheng Chen; Ying Li; Yeqing Lan (Journal of Water Process Engineering, 2024)

Adsorption of perfluoroalkyl substances on deep eutectic solvent-based amorphous metal-organic framework: Structure and mechanism - Yaqi Yin; Chen Fan; Linru Cheng; Yuwei Shan (Environmental Research, 2024)

Simulated solar light-driven degradation of micropollutant in water by biochar-based metal-free catalyst: Regulation strategies for electronic structure and morphology engineering - Ya-Ni Zang; Shan-Shan Yang; Cheng-Xin Chen; Jia-Xiu Liu; Lan Ding; Ji-Wei Pang; Chuan-Dong Wu; Peng Liu; Lu-Yan Zhang; Nan-Qi Ren; Jie Ding (Chemical Engineering Journal, 2024)

Modulating ultrafast carrier dynamics behavior via vacancy engineering of ReSe2 with Se vacancy for efficient electrochemical activity - Ming-Kun Jiang; Yu-Xin Liu; Shan-Shan Kan; Shi-Xuan Deng; Zhe-Kun Ren; Xiao-Meng Jiang; Cheng-Bao Yao (Chemical Engineering Journal, 2024)

Novel insights into the protective effects of leonurine against acute kidney injury: Inhibition of ER stress-associated ferroptosis via regulating ATF4/CHOP/ACSL4 pathway - Ran Cheng; Xiaowan Wang; Lihua Huang; Zhisheng Lu; Aijun Wu; Shan Guo; Chuang Li; Wei Mao; Ying Xie; Peng Xu; Ruimin Tian (Chemico-Biological Interactions, 2024)

Serum indoleamine 2, 3-dioxygenase and tryptophan-2, 3-dioxygenase: potential biomarkers for the diagnosis of major depressive disorder - Jun Liang; Zhuo-Yu Cheng; Feng Shan; Yin Cao; Qing-Rong Xia (Psychopharmacology, 2024)

Correction to: Melatonin antagonizes oxidative stress-induced apoptosis in retinal ganglion cells through activating the thioredoxin-1 pathway - Shan Gao; Qiaochu Cheng; Yaguang Hu; Xiaojuan Fan; Chen Liang; Chen Niu; Qianyan Kang; Ting Wei (Molecular and Cellular Biochemistry, 2024)

Taxonomic status of hares ( Lepus spp.) in Xinjiang, China (Lagomorpha: Leporidae): An integrative approach - Wen‐Juan Shan; Zu‐Rui Li; Hui‐Ying Dai; Peng‐Cheng Dong; Yu‐Cong Zhang (Zoologica Scripta, 2024)
The taxonomic status and interspecies relationships of hares (genus Lepus ) in Xinjiang, China, remain ambiguous owing to extremely similar external morphologies, introgressive hybridization between species and a lack of molecular genetic records. In this study, a total of 154 hare specimens were used to clarify their taxonomic status. Based on multiple lines of evidence, including observations and comparisons of external morphological characteristics, skull morphometrics and genome‐wide single nucleotide polymorphism (SNP) datasets, four hare species were recognised. Lepus yarkandensis and Lepus timidus , which have obvious morphological characteristics, were identified as two distinct species, as previously reported. Combining the integrated morphological and molecular datasets with the relevant literature, we proposed suggestions on the classification of the more controversial hares. Due to molecular and morphological similarities, hares in northern and central Xinjiang were divided into two subspecies of Lepus tolai , namely, Lepus tolai lehmanni and Lepus tolai centrasiaticus . Despite similar external morphological characters, hares in the southwest Pamir Plateau and its surroundings can be distinguished from L. tolai by differences in skull morphology and genetic divergence and were, therefore, considered a subspecies of Lepus tibetanus , Lepus tibetanus pamirensis . Furthermore, we found that hybridization and introgression occurred between sympatric or parapatric hares, especially between L. yarkandensis and L. tibetanus pamirensis , L. yarkandensis and L. tolai centrasiaticus , and L. tolai lehmanni and L. timidus .

Identification, distribution, bactericidal and immunoregulatory activities of NK-lysins in grass carp (Ctenopharyngodon idella) - Gai Ling Wang; En Zhong Li; Da Hong Li; Ming Cheng Wang; Shan Shan Sun; Run Yan Xiong; Chuan Feng Li; Bao Jian Sun; Hai Xia Xie (Aquaculture, 2024)

Overview of the recent advances in porcine epidemic diarrhea vaccines - Miao-Zhan Wei; Lan Chen; Rong Zhang; Ze Chen; Yan-Juan Shen; Bi-Jun Zhou; Kai-Gong Wang; Chun-Lan Shan; Er-Peng Zhu; Zhen-Tao Cheng (The Veterinary Journal, 2024)

Insights into simultaneous efficient removal of cationic and anionic dyes by nitrogen-rich seaweed carbon adsorbent - Xiaoxue Cheng; Hongping Li; Ding Jiang; Wanming Lu; Qifan Ling; Shan Zhong; Hao Chen; Bahram Barati; Xun Hu; Xun Gong; Shuang Wang (Process Safety and Environmental Protection, 2024)

Rapid full-field deformation measurements of tall buildings using UAV videos and deep learning - Jiazeng Shan; Peican Huang; Cheng Ning Loong; Mukun Liu (Engineering Structures, 2024)

An integrated constructed wetland-Microbial fuel cell system with sewage sludge-biochar to enhance treatment and energy recovery efficiencies - Fuhao Zhang; Cheng Shen; Yaqian Zhao; Shaochen Zhang; Yin Wang; Bin Ji; Ranbin Liu; Ming Hung Wong; Shengdao Shan; Jin Zhang (Chemical Engineering Journal, 2024)

Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Controlled assembly of novel Fe2O3/MgFe2O4 nanotubular array structures for rapid detection of dibutylamine - Baosheng Li; Junchao Yang; Guanyi Zhang; Ming Zheng; Rui Li; Yubao Kan; Jiahui Li; Tingting Wang; Qibin Huang; Xianfa Zhang; Lihua Huo; Shan Gao; et al. (Chemical Engineering Journal, 2024)

Tricarboxylic acid cycle metabolites: new players in macrophage - Ying Yang; Bing-Bing Cui; Jian Li; Jiao-Jiao Shan; Jun Xu; Cheng-Yong Zhang; Xiao-Tong Wei; Ri-Ran Zhu; Jing-Yi Wang (Inflammation Research, 2024)

Streamlining regular liquid chromatography with MALDI-TOF MS and NMR spectroscopy using automatic full-contact splitless spotting interface and flash-tap fractioning collection - Chi-Minh Truong; Yung-Cheng Jair; Hong-Po Chen; Wei-Chih Chen; Yi-Hsin Liu; Pin-Chuan Chen; Pai-Shan Chen (Analytica Chimica Acta, 2024)

Two undescribed benzopyran derivatives from Ranunculus sceleratus L. with their in vitro anti-inflammatory activity in lipopolysaccharide-activated RAW 264.7 cells - Zhen Shi; Si-jia Zhou; Qun-lin Zhang; Fu-cai Ren; Shan-shan Cao; Long-kang Cao; Ya-zhong Zhang; Wen-ming Cheng (Natural Product Research, 2024)

Microplastics removal mechanisms in constructed wetlands and their impacts on nutrient (nitrogen, phosphorus and carbon) removal: A critical review - Shaochen Zhang; Cheng Shen; Fuhao Zhang; Kejun Wei; Shengdao Shan; Yaqian Zhao; Yu Bon Man; Ming Hung Wong; Jin Zhang (Science of The Total Environment, 2024)

Nano‑selenium alleviates the pyroptosis of cardiovascular endothelial cells in chicken induced by decabromodiphenyl ether through ERS-TXNIP-NLRP3 pathway - Yangyang Jiang; Bowen Dong; Xing Jiao; Jianhua Shan; Cheng Fang; Kaixuan Zhang; Di Li; Chenchen Xu; Ziwei Zhang (Science of The Total Environment, 2024)

Per- and polyfluoroalkyl substances (PFASs) in Chinese surface water: Temporal trends and geographical distribution - Jie Wang; Cheng Shen; Jin Zhang; Guangyu Lou; Shengdao Shan; Yaqian Zhao; Yu Bon Man; Yuliang Li (Science of The Total Environment, 2024)

Biodegradation of polyethylene terephthalate by Tenebrio molitor: Insights for polymer chain size, gut metabolome and host genes - Lei He; Shan-Shan Yang; Jie Ding; Cheng-Xin Chen; Fan Yang; Zhi-Li He; Ji-Wei Pang; Bo-Yu Peng; Yalei Zhang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu (Journal of Hazardous Materials, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Quantitative health risk assessment of microbial hazards from water sources for community and self-supply drinking water systems - Cheng Yan; Wei-di Wan; Rui-ning Wang; Tian-nuo Lai; Wajid Ali; Shan-shan He; Sai Liu; Xiang Li; Zaheer Ahmad Nasir; Frederic Coulon (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Simultaneous determination of enantiomer residues of metalaxyl and its metabolite metalaxyl acid in animal muscle tissues by chiral liquid chromatography-tandem mass spectrometry - Hao Zhou; Qi Shan; Limin He; Meiyu Zhang; Cheng Zhao; Guangming Zheng; Lichun Li; Feng Xu; Lisha Ma; Yi Yin (Food Chemistry, 2024)

Unravelling hidden threats of water disinfection: Toxicity evaluation and toxic products identification during diclofenac degradation - Ding Pan; Cheng Zhang; Cai-Shan Wang; Peng Zhang; Xin-Yi Jiao; Qian-Ru Ma; Li-Ting Wang; Dai-Jun Li; Li-Ping Li (Environmental Pollution, 2024)

Long-Term Application of Chinese Milk Vetch Return to Soil Alters Phosphorus forms Associated with Aggregates - Hui Wang; Shan Tang; Shang Han; Wenlong Cheng; Rongyan Bu; Min Li; Wu Ji; Weidong Cao (Journal of Soil Science and Plant Nutrition, 2024)

Phthalate esters and nonylphenol concentrations correspond with microplastic distribution in anthropogenically polluted river sediments - Ming-Huang Wang; Chih-Feng Chen; Frank Paolo Jay B. Albarico; Shan-Lu Lin; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2024)

Methionine redox regulation of actin-interacting proteins primarily governs antioxidative signaling and response to the salvianolic acid B treatment in EA.hy926 cells - Ai-Cheng Wang; Xiao-Ming Qi; Qing-Fang Li; Yi-Jia Feng; Yuan-Lin Zhang; Hui-Zhi Wei; Jin-Shan Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2024)

Holocene pollen record from Lake Gahai, NE Tibetan Plateau and its implications for quantitative reconstruction of regional precipitation - Shan Zhou; Jiawu Zhang; Bo Cheng; Hainan Zhu; Jinxiu Lin (Quaternary Science Reviews, 2024)

Mechanistic study on levoglucosan condensation and decomposition in the condensed phase during cellulose pyrolysis - Erwei Leng; Li Yang; Tiantian Wang; Sijie Du; Hong Tian; Shan Cheng; Yun Yu (Fuel, 2024)

A NIR-II photothermal nanoplatform integrating intracellular Ca2+ elevation via TRPV1 activation for enhanced antitumor Therapy: A powerful combination of in situ tumor vaccination and vascular disruption - Yuanyuan Cheng; Zhanyin Qian; Xingkun Liu; Yinchao Zhang; Qian Chen; Tianhe Shan; Xiaoyu Jiang; Yuanyuan Liu; Yang Liu; Yinsong Wang (Chemical Engineering Journal, 2024)

Map-based cloning and functional analysis of a major quantitative trait locus, BolC.Pb9.1, controlling clubroot resistance in a wild Brassica relative (Brassica macrocarpa) - Xiaoli Zhang; Fengqing Han; Zhansheng Li; Zhenghua Wen; Wenjuan Cheng; Xiaozheng Shan; Deling Sun; Yumei Liu (Theoretical and Applied Genetics, 2024)

Erythropoietin alleviates astrocyte pyroptosis by targeting the miR-325-3p/Gsdmd axis in rat spinal cord injury - Wenshan Shan; Jiawei Wang; Rui Cheng; Yong Xuan; Zongsheng Yin (Inflammopharmacology, 2024)

Oncogenic and immunological roles of RACGAP1 in pan-cancer and its potential value in nasopharyngeal carcinoma - Cheng-shan Zheng; Wei-mei Huang; Hong-mei Xia; Jing-lin Mi; Yuan-qing Li; Hui-qing Liang; Li Zhou; Zhou-xue Lu; Fang Wu (Apoptosis, 2024)

Effects of field-aging on the impact of biochar on herbicide fate and microbial community structure in the soil environment - Hongguang Cheng; Dan Xing; Gratien Twagirayezu; Shan Lin; Shangyi Gu; Chenglong Tu; Paul W. Hill; David R. Chadwick; Davey L. Jones (Chemosphere, 2024)

Quantitative SARS-CoV-2 exposure assessment for workers in wastewater treatment plants using Monte-Carlo simulation - Cheng Yan; Yi-ning Hu; Zi-cheng Gui; Tian-nuo Lai; Wajid Ali; Nian-hong Wan; Shan-shan He; Sai Liu; Xiang Li; Ting-xu Jin; Zaheer Ahmad Nasir; Sonia Garcia Alcega; et al. (Water Research, 2024)

HUNK inhibits cargo uptake and lysosomal traffic in the caveolar pathway via the AGAP3/ARF6 - Siyuan Jiang; Xiaoqi Han; Tihui Liu; Ying He; Zidong Zhao; Tongfeng Liu; Shuwen Cheng; Jihang Zhang; Liqiang Duan; Yajuan Liu; Tianyou Cheng; Yong Liu; et al. (Science Bulletin, 2024)

Large particle size boosting the engineering application potential of functional biochar in ammonia nitrogen and phosphorus removal from biogas slurry - Haohao Bian; Minyan Wang; Junhao Huang; Ruting Liang; Jiada Du; Chaochu Fang; Cheng Shen; Yu Bon Man; Ming Hung Wong; Shengdao Shan; Jin Zhang (Journal of Water Process Engineering, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

Proposal to Reclassify Companilactobacillus futsaii subsp. chongqingensis as a Later Heterotypic Synonym of Companilactobacillus futsaii subsp. futsaii - Cheng-Shan Jiang; Chun Tao Gu (Current Microbiology, 2024)

Deciphering the role of particulate organic matter in soil nitrogen transformation in rice–rapeseed and rice–wheat rotation systems - Rongyan Bu; Shang Han; Wenlong Cheng; Yue Wu; Shan Tang; Min Li; Hui Wang; Zibing Ge; Ji Wu (Applied Soil Ecology, 2024)

The impact of climate change and human activities on the change in the net primary productivity of vegetation—taking Sichuan Province as an example - Tangrui Dai; Xiaoai Dai; Heng Lu; Tao He; Weile Li; Cheng Li; Shengqi Huang; Yiyang Huang; Chenbo Tong; Ge Qu; Yunfeng Shan; Shuneng Liang; et al. (Environmental Science and Pollution Research, 2023)

Electroacoustic performance online measurement under extreme pressure using an 11,000-m transceiver - Zhiguo Qu; Zhi Zhong; Dapeng Zou; Xinghui Cao; Mingguang Shan; Yongqiang Xie; Hui Cheng (Marine Georesources & Geotechnology, 2023)

Thickness-variation-insensitive near-infrared quantum dot LEDs - Wan-Shan Shen; Yang Liu; Luke Grater; So Min Park; Haoyue Wan; Yan-Jun Yu; Jia-Lin Pan; Fan-Cheng Kong; Qi-Sheng Tian; Dong-Ying Zhou; Zeke Liu; Wanli Ma; et al. (Science Bulletin, 2023)

The impact of business intelligence, big data analytics capability, and green knowledge management on sustainability performance - Jie Cheng; Harcharanjit Singh Mahinder Singh; Yi-Cheng Zhang; Shan-Yong Wang (Journal of Cleaner Production, 2023)

Effect of NaCl/MgCl2 on generation of NOx precursors during aspartic acid pyrolysis: A experimental and theoretical study - Shan Cheng; Hong Tian; Jingchun Huang; Yangyue Wei; Ting Yang; Yu Qiao (Fuel, 2023)

Integrated multi-omic analysis reveals the cytokinin and sucrose metabolism-mediated regulation of flavone glycoside biosynthesis by MeJA exposure in Ficus pandurata Hance - Bingxian Yang; Fupeng Pan; Farhat Yasmeen; Luhuizi Shan; Junjie Pan; Meng Zhang; Xinying Weng; Mengyu Wang; Mengxin Li; Qiaomei Wang; Kejun Cheng (Food Research International, 2023)

An in-situ cosolvent/electrokinetics/pumping (CEP) technique to remediate the groundwater site contaminated by tetrachloroethylene - Jih-Hsing Chang; Pei-Yu Yang; Cheng-Di Dong; Mohanraj Kumar; Shan-Yi Shen (Chemical Engineering Journal, 2023)

Mixotrophic culture of Chaetoceros sp. and the synergistic carbon and energy metabolism - Shengzhou Shan; Shanshan Wang; Xi Yan; Kang Chen; Li Liang; Xiaohui Li; Chengxu Zhou; Xiaojun Yan; Roger Ruan; Pengfei Cheng (Bioresource Technology, 2023)

Subsoil Tillage and Organic Fertilization Benefit Rice Root Growth and Yield by Ameliorating Soil Compaction and Fertility - Rongyan Bu; Min Li; Wenlong Cheng; Shang Han; Hui Wang; Shan Tang; Changai Lu; Ji Wu (Journal of Soil Science and Plant Nutrition, 2023)

Synthesis and evaluation of in vitro and in vivo anti -Toxoplasma gondii activity of tetraoxane-substituted ursolic acid derivatives - Ya-Lan Wang; Li-Li Jin; Xu Cheng; Wei-Feng Yan; Hao Deng; Qing-Kun Shen; Zhe-Shan Quan; Chun-Mei Jin; Chang-Hao Zhang (Natural Product Research, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Ecological Niche and Interspecific Association of the Main Fishes in the Coastal Waters of Hainan Island, China - Zhengli Luo; Yanbo Zhou; Ning Liu; Liangming Wang; Yan Liu; Binbin Shan; Manting Liu; Cheng Chen; Changping Yang; Dianrong Sun (Fishes, 2023)
This study explored the ecological niche and interspecific relationships among the main fish species in the coastal waters of Hainan Island based on data from fishery stock surveys conducted in the spring and autumn of 2022. The methods of chi-square test, percentage of co-occurrence (PC), association coefficient (AC), cluster analysis, and redundancy analysis were used to analyze the interspecific associations and influence of environmental factors on the ecological niches of fish communities. According to the cluster analysis of niche breadth, 20 main fishes could be divided into broad, medium, and narrow niche species. There were four and eight broad niche species in spring and autumn, respectively. The ranges of niche overlap values were 0.001–0.91 in spring and 0–0.87 in autumn, indicating that the species differed and were similar in their ability to utilize resources, survive in habitats, and prey. According to the variance ratio and statistic value W, the main fishes in spring showed a significant positive association, whereas those in autumn showed a positive association, but not at a significant level, indicating that the main fishes in spring were more closely associated with each other. There were 56 species pairs in the 2 seasons that were significantly associated (χ2 ≥ 3.841). AC and PC tests revealed that the interspecific association was strong and tended to be positive. According to the redundancy analysis, environmental factors such as surface temperature, water depth, and pH significantly affected the main fishes in spring, while environmental factors such as dissolved oxygen, bottom temperature, surface salinity, and pH significantly affected those in autumn.

Associating phthalate exposure during pregnancy with preschooler's FMI, ABSI and BRI trajectories via putative mechanism pathways - Hui Gao; Yi Zhang; Li-wen Chen; Hong Gan; Meng-juan Lu; Binbin Huang; Juan Tong; Meng-long Geng; Kun Huang; Cheng Zhang; Bei-bei Zhu; Shan-shan Shao; et al. (Chemosphere, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

Tanespimycin and rapamycin exhibit antifungal activity against Colletotrichum gloeosporioides and enhance mango resistance to anthracnose via differentially modulating heat shock response - Yu-Jung Cheng; Fang-Wei Lee; Yun-Shan Tsai; Yen-Chou Kuan (Postharvest Biology and Technology, 2023)

Preparation, properties and applications of porous hydrogels containing thiol groups for heavy metal removal - Huai-Yuan Niu; Jin-Cheng Li; Ji-Shan Li; Cong Yi; Cheng-Gang Niu (Journal of Environmental Chemical Engineering, 2023)

Effective removal of cesium by ammonium molybdophosphate–polyethylene glycol magnetic nanoparticles - Chengyun Fu; Zhaomin Tan; Jianfeng Cheng; Jingli Xie; Xuezhi Dai; Yinyuan Du; Shan Zhu; Shaoqing Wang; Minhao Yan (Journal of Environmental Chemical Engineering, 2023)

Effect and mechanism of induced crystallization softening treatment on water quality in drinking water distribution system with high hardness water source - Changgeng Li; Cheng Liu; Zhenhua Cao; Minggang Shan; Yan Bing (Journal of Environmental Chemical Engineering, 2023)

Removal of tar from waste textiles by molten carbonates pyrolysis in bubbling reactor - Yaohong He; Yanjun Hou; Cheng Wang; Shan Wang; Yi Wei (Fuel, 2023)

Effects of long-term substitution of chemical fertilizer with Chinese milk vetch on soil phosphorus availability and leaching risk in the double rice systems of Eastern China - Hui Wang; Shan Tang; Shang Han; Min Li; Wenlong Cheng; Rongyan Bu; Weidong Cao; Ji Wu (Field Crops Research, 2023)

Temperature-dependent NO2/diisopropylamine sensor based on SnO2 squama-wrapped tubes derived from waste bamboo shoot skin - Bao-Yu Song; Cong Chen; Ya-Nan Li; Xian-Fa Zhang; Xiao-Li Cheng; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2023)

Mixotrophy, a more promising culture mode: Multi-faceted elaboration of carbon and energy metabolism mechanisms to optimize microalgae culture - Shengzhou Shan; Artem Yurevich Manyakhin; Chun Wang; Baosheng Ge; Jichang Han; Xuezhi Zhang; Chengxu Zhou; Xiaojun Yan; Roger Ruan; Pengfei Cheng (Bioresource Technology, 2023)

The Mitochondrial-Derived Peptide (MOTS-c) Interacted with Nrf2 to Defend the Antioxidant System to Protect Dopaminergic Neurons Against Rotenone Exposure - Jingsong Xiao; Qifu Zhang; Yaohui Shan; Feng Ye; Xi Zhang; Jin Cheng; Xiaogang Wang; Yuanpeng Zhao; Guorong Dan; Mingliang Chen; Yan Sai (Molecular Neurobiology, 2023)

Managing microbial sulfur disproportionation for optimal sulfur autotrophic denitrification in a pilot-scale elemental sulfur packed-bed bioreactor - Yi-Lu Sun; Si-Yuan Zhai; Zhi-Min Qian; Shan Yi; Wei-Qin Zhuang; Hao-Yi Cheng; Xue-Ning Zhang; Ai-Jie Wang (Water Research, 2023)

Continuous Co-incorporation of Chinese Milk Vetch and Rice Straw with Reduced Chemical Fertilizer Maintains Rice Yield as a Consequence of Increased Carbon and Nitrogen Storage in Soil Aggregates - Rongyan Bu; Wenlong Cheng; Shang Han; Run Hu; Hui Wang; Shan Tang; Min Li; Qin Zhu; Ji Wu; Weidong Cao (Journal of Soil Science and Plant Nutrition, 2023)

Dietary factors and gestational diabetes mellitus: An umbrella review - Guochen Ma; Yujie Xu; Haoqi Li; Yaxian Zeng; Xiaoyu Wang; Shufang Shan; Jingyuan Xiong; Guo Cheng (Trends in Food Science & Technology, 2023)

Bidirectional crosstalk of the cAMP/ROS-dependent signaling pathways in inflammatory macrophage: An activation of formononetin - Lan-Fang Zhang; Xiao-Yan Zhang; Ai-Cheng Wang; Yi-Jia Feng; Xiao-Ming Qi; Yuan-Lin Zhang; Qing-Fang Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2023)

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

Design and operation insights concerning a pilot-scale S0-driven autotrophic denitrification packed-bed process - Yi-Lu Sun; Zhuo-Ran Li; Xue-Ning Zhang; Heng Dong; Zhi-Min Qian; Shan Yi; Wei-Qin Zhuang; Hao-Yi Cheng; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Effect of liver metastasis on the efficacy of immune checkpoint inhibitors in cancer patients: a systemic review and meta-analysis - Bao-Wen Tian; Cheng-Long Han; Han-Chao Wang; Lun-Jie Yan; Zi-Niu Ding; Hui Liu; Xin-Cheng Mao; Jin-Cheng Tian; Jun-Shuai Xue; Long-Shan Yang; Si-Yu Tan; Zhao-Ru Dong; et al. (Clinical & Experimental Metastasis, 2023)

Fabrication of magnetic cobalt‑iron composite moored on carbon derived from cigarette butts (CoFe@CCB) for peroxymonosulfate activation to efficiently degrade Rhodamine B - Zihao Wang; Lijiao Yang; Zezhong Shan; Lu Tang; Cheng Chen; Yeqing Lan; Wei Li (Journal of Water Process Engineering, 2023)

Preparation of P-doped biochar and its high-efficient removal of sulfamethoxazole from water: Adsorption mechanism, fixed-bed column and DFT study - Yizhen Cheng; Jingrui Yang; Jimin Shen; Pengwei Yan; Shan Liu; Jing Kang; Lanbo Bi; Binyuan Wang; Shengxin Zhao; Zhonglin Chen (Chemical Engineering Journal, 2023)

Comparative RNA-seq analysis and ceRNA network of genistein-treated GT1-7 neurons - Jingyuan Xiong; Ye Tian; Guochen Ma; Aru Ling; Shufang Shan; Guo Cheng (Molecular & Cellular Toxicology, 2023)

Identification of metabolites from edible mushroom Morchella sextelata and their biological evaluation - De-Xian Li; Xia Cheng; Fo-Pei Ma; Jie-Yu Chen; Yi-Ping Chen; Xiao-Shan Zhao; Qi Luo (Natural Product Research, 2023)

Impact of aged and virgin microplastics on sedimentary nitrogen cycling and microbial ecosystems in estuaries - Xiaodan Wang; Xiaoli Zhang; Cheng Yao; Encui Shan; Xiaojing Lv; Jia Teng; Jianmin Zhao; Qing Wang (Science of The Total Environment, 2023)

Fabrication of amorphous metal-organic framework in deep eutectic solvent for boosted organophosphorus pesticide adsorption - Yaqi Yin; Chen Fan; Yuwei Shan; Linru Cheng (Journal of Environmental Chemical Engineering, 2023)

Selective catalytic reduction of NO with NH3 over MnOx-CeO2 catalysts: The great synergy between CeO2 and crystalline phase of Mn3O4 - Lijun Cheng; Songil Sin; Jiawei Ji; Shan Yang; Chong Tan; Zhiwen Gu; Wang Song; Chunkai Huang; Chuanzhi Sun; Changjin Tang; Lin Dong (Fuel, 2023)

Root biomechanical features and wind erosion resistance of three native leguminous psammophytes for coastal dune restoration - Jung-Tai Lee; Cheng-Ying Shih; Yu-Shan Hsu (Ecological Engineering, 2023)

Dispersed Pd/alumina catalyst with finite iodine entry for boosted CO purification and dimethyl carbonate synthesis - Yun-Yun Zeng; Lu-Yang Qiao; Shan-Shan Zong; Rong Guo; Jian-Kai Cheng; Xin-Yi Cao; Zhang-Feng Zhou; Mao-Hong Fan; Yuan-Gen Yao (Chemical Engineering Journal, 2023)

Loss of ndrg2 Function Is Involved in Notch Activation in Neuromast Hair Cell Regeneration in Zebrafish - Xin Wang; Xiaodong Gu; Cheng Wang; Yingzi He; Dong Liu; Shan Sun; Huawei Li (Molecular Neurobiology, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Mixotrophic culture of Chaetoceros sp. and its response to circadian rhythm - Hongyu Chen; Shengzhou Shan; Chun Wang; Zorigto Namsaraev; Ivan Dubovskiy; Chengxu Zhou; Roger Ruan; Xiaojun Yan; Pengfei Cheng (Algal Research, 2023)

Pteris Faba and Pteris rubella , two new species in section Hypsopodium (Pteridaceae) - Yi‐Shan Chao; Cheng‐Wei Chen; Wen‐Liang Chiou; Fulgent P. Coritico; Yi‐Han Chang; Tsung‐Yu Aleck Yang (New Zealand Journal of Botany, 2023)
Pteris sect. Hypsopodium (Pteridaceae) was reported to contain about nine species. Here we describe two new species based on morphological and molecular evidence, namely Pteris faba Y.S.Chao sp. nov. from Papua New Guinea and the Philippines, and Pteris rubella Y.S.Chao & C.W.Chen sp. nov. from the Solomon Islands. We provide type information, voucher specimens used, distribution, details of habitats and photographs showing diagnostic characters for both species. With the two new species recognised in this study, and three other species newly resolved as members of Pteris section Hypsopodium ( Pteris mertensioides , P. polylepis , and P. quinquepartita ) the number of species in section Hypsopodium increases to 14, with most species distributed in Asia and Oceania. Pteris section Hypsopodium can be distinguished from other sections by having bipinnate laminae in combination with red‐brown rachises.

Study on the spatio-temporal evolution and influencing factors of farmland abandonment on a county scale - Cheng Wang; Yue Su; Shan He; Yan Xie; Panpan Xia; Yanglin Cui (Environmental Science and Pollution Research, 2023)

Climatic Trend of Wind Energy Resource in the Antarctic - Kai-Shan Wang; Di Wu; Tao Zhang; Kai Wu; Chong-Wei Zheng; Cheng-Tao Yi; Yue Yu (Journal of Marine Science and Engineering, 2023)
Wind energy resource is an important support for the sustainable development of Antarctica. The evaluation of wind energy potential determines the feasibility and economy of wind power generation in Antarctica, among which mastering the variation rule of wind energy resource is the key to realizing the effective utilization of polar wind energy. Based on the 6-h ERA-5 reanalysis data of ECMWF from January 1981 to December 2020, this paper systematically analyzed the long-term variation trend of Antarctic wind energy resource by using the climate statistical analysis method and the least square fitting, with the comprehensive consideration of a series of key indicators such as Wind Power Density, Effective Wind Speed Occurrence, Energy Level Occurrence, and Stability. The results show that it indicates a positive trend for wind power density (0.5~2 W × m−2 × a−1), effective wind speed occurrence (2~3%/a), energy level occurrence (0.1~0.2%/a), and coefficient of variation (−0.005/a) in the South Pole—Kunlun station and the central region of Queen Maud land. The westerly belt exhibits a decreasing index (−0.5%/a) in terms of stability trend, indicating a positive potential. Kemp Land, the Ross Island—Balleny Islands waters show shortages in all indicators. The wind power density in the Antarctic region is stronger in spring and summer than in autumn and winter, with the weakest in autumn. Based on the above indicators, the variation trend in the East Antarctic coast, Wilhelm II Land—Wilkes Land, the South Pole—Kunlun station, and the westerlies is generally superior.

MgFe-LDH@biochars for removing ammonia nitrogen and phosphorus from biogas slurry: Synthesis routes, composite performance, and adsorption mechanisms - Haohao Bian; Minyan Wang; Jialin Han; Xiaopiao Hu; Honglei Xia; Lei Wang; Chaochu Fang; Cheng Shen; Yu Bon Man; Ming Hung Wong; Shengdao Shan; Jin Zhang (Chemosphere, 2023)

Ethnic disparities in ambient air and traffic-related pollution exposure and ethnic-specific impacts on clinical biomarker levels - Ke Hao; Jushan Zhang; Antonio Di Narzo; Xingmin Zhang; Alice Hao; Mingxu Shan; Maya Deyssenroth; Jia Chen; Zhongyang Zhang; Haoxiang Cheng (Science of The Total Environment, 2023)

Pressure tuning of optical reflectivity in LuH2 - Xuan Zhao; Pengfei Shan; Ningning Wang; Yunliang Li; Yang Xu; Jinguang Cheng (Science Bulletin, 2023)

A unique suit of Wuchiapingian marine red beds in central China representing a specific paleogeography and paleoclimate association - Cheng Cheng; Zi'an Shan; Mingyu Shan; Zhonglai Zhou; Bingyan Ren; Yike Chu; Shuangying Li; Dan Wang; Hongzuo Wang; Xujie Shu; Peng Qian (Marine and Petroleum Geology, 2023)

Vulnerability of farmers and herdsmen households in Inner Mongolian plateau to arid climate disasters and their development model - Wenlong Li; Suocheng Dong; Haiying Lin; Fujia Li; Hao Cheng; Zhuang Jin; Shan Wang; Hasbaggen Zhang; Pengshen Hou; Bing Xia (Journal of Cleaner Production, 2023)

The catalytic effect of alkali and alkaline earth metals on the transformation of nitrogen during phenylalanine pyrolysis - Hong Tian; Jiang Zhu; Yang Yang; Shan Cheng; Yanshan Yin; Fuqiang Qin; Lei Liu (Fuel, 2023)

Synthesis and biological evaluation of esculetin derivatives as potential anti-HBV agents - Zhen Ye; Tong-Shi-Yao Zhao; Shan-Bin Li; Xian-Li Zhou; Qin Luo; Jiang-Ke Qin; Cheng-Qin Liang; Ping Wang; Guang-Bo Ge (Medicinal Chemistry Research, 2023)

ABAQUS Numerical Simulation Study on the Shear Instability of a Wellbore Induced by a Slip of the Natural Gas Hydrate Layer - Yujing Jiang; Baocheng Li; Changsheng Wang; Hengjie Luan; Sunhao Zhang; Qinglin Shan; Xianzhen Cheng (Journal of Marine Science and Engineering, 2023)
To study the shear deformation and failure characteristics of a wellbore and the interaction mechanism with its surrounding rocks induced by a layer slip during natural gas hydrates (NGHs) extraction, this paper conducted a numerical simulation study of wellbore shear induced by a layer slip using ABAQUS software and carried out a laboratory experiment of wellbore shear to verify the accuracy of the numerical model. The results show that the shear force–displacement curves obtained from the laboratory experiments and numerical simulations are consistent with five stages, including the compaction stage, linear stage, plastic stage, strain-softening stage and residual stage. The wellbore shows a “Z”-shaped deformation characteristic after its shear breakage. The shear force of the wellbore is maximum at the shear surface, and it is distributed in an approximate “M” shape along the shear surface. The axial force of the wellbore is small and uniformly distributed in the initial stage of the shear. The wellbore bending moment is minimum at the shear surface, with a value of 0, and it is distributed in a skew–symmetric wave shape along the shear surface. During the shearing, the evolution of the wellbore axial force and shear force can be classified into the distribution pattern along the radial direction on the shear surface and the pattern along the axial direction. The combination of the wellbore axial force and shear force causes the tensile–shear compound failure of the wellbore. During shearing, the wellbore and rock body gradually enter the plastic state with the increase in the shear displacement. When the entire cross-section of the wellbore is in the plastic state, a “necking” phenomenon of the wellbore begins to appear. During the shearing, the frictional dissipation energy and plastic dissipation energy increase constantly. In addition, the elastic strain energy increases to a peak and then decreases to a certain value, which remains unchanged along with the work conducted by the shear force.

Analysis of collaborative urban public crisis governance in complex system: A multi-agent stochastic evolutionary game approach - Shao-nan Shan; Zi-cheng Zhang; Wen-yan Ji; He Wang (Sustainable Cities and Society, 2023)

Preparation and characterization of carboxymethyl chitosan/pullulan composite film incorporated with eugenol and its application in the preservation of chilled meat - Zhen Zeng; Yu-Jing Yang; Qian Tu; Yu-Ying Jian; Da-Ming Xie; Ting Bai; Shan-Shan Li; Yun-Tao Liu; Cheng Li; Cai-Xia Wang; Ai-Ping Liu (Meat Science, 2023)

Manganese and copper additions differently reduced cadmium uptake and accumulation in dwarf Polish wheat (Triticum polonicum L.) - Xing Chen; Shan Yang; Jian Ma; Yiwen Huang; Yi Wang; Jian Zeng; Jun Li; Siyu Li; Dan Long; Xue Xiao; Lina Sha; Dandan Wu; et al. (Journal of Hazardous Materials, 2023)

Facile, time-saving cigarette butt-assisted combustion synthesis of modified CaO-based sorbents for high-temperature CO2 capture - Hewen Li; Jian Sun; Qiran Jiang; Hongqiang Xia; Shan Cheng; Zijian Zhou; Xinming Nie; Chuanwen Zhao (Fuel, 2023)

Brain Inflammatory Marker Abnormalities in Major Psychiatric Diseases: a Systematic Review of Postmortem Brain Studies - Yang-wen Ai; Yang Du; Lei Chen; Shu-Han Liu; Qing-shan Liu; Yong Cheng (Molecular Neurobiology, 2023)

Development of AIoT System for facility asparagus cultivation - Cheng-Ying Chou; Shan-Cheng Chang; Zi-Ping Zhong; Ming-Chi Guo; Ming-Hsien Hsieh; Jui-Chu Peng; Ling-Chieh Tai; Ping-Liang Chung; Jen-Cheng Wang; Joe-Air Jiang (Computers and Electronics in Agriculture, 2023)

Pharmacokinetics and residue elimination of metalaxyl enantiomers in snakehead (Channa argus) - Hao Zhou; Meiyu Zhang; Qi Shan; Heqing Huang; Meiling Zhang; Shugui Liu; Jiawei Lin; Lisha Ma; Guangming Zheng; Lichun Li; Cheng Zhao; Xiaoxin Dai; et al. (Aquaculture, 2023)

Molecular mechanism of anti-inflammatory effects of the proteasome inhibitor MG-132 on Con A-induced acute liver injury in mice - Chunlan Shan; Deyuan Ou; Yanling Xiong; Hongsong Cheng; Chun Song; Mei Li; Tian Fang; Zhentao Cheng; Fujun Miao (Research in Veterinary Science, 2023)

An improved method of MgFe-layered double hydroxide/ biochar composite synthesis - Haohao Bian; Cheng Shen; Wanpeng Liu; Yu Bon Man; Ming Hung Wong; Peter Christie; Shengdao Shan; Minyan Wang; Jin Zhang (Journal of Cleaner Production, 2023)

Can the marketization of urban land transfer improve energy efficiency? - Yanjun Yang; Rui Xue; Xiaoxi Zhang; Yutai Cheng; Yuli Shan (Journal of Environmental Management, 2023)

Late Neoarchean TTG and monzogranite in the northeastern North China Craton: Implications for partial melting of a thickened lower crust - Zhongshui Li; Xuanlong Shan; Jin Liu; Jian Zhang; Zhenghong Liu; Changquan Cheng; Zhigao Wang; Chen Zhao; Hongchao Yu (Gondwana Research, 2023)

Novel in-situ deposited V2O5 nanorods array film sensor with enhanced gas sensing performance to n-butylamine - Xuemei Sun; Rui Gao; Yuanyuan Wu; Xianfa Zhang; Xiaoli Cheng; Shan Gao; Yingming Xu; Lihua Huo (Chemical Engineering Journal, 2023)

Fine mapping and candidate gene analysis of CaFCD1 affecting cuticle biosynthesis in Capsicum annuum L. - Jin Wang; Qingyun Shan; Ting Yi; Yanqing Ma; Xiaoxun Zhou; Luzhao Pan; Wu Miao; Xuexiao Zou; Cheng Xiong; Feng Liu (Theoretical and Applied Genetics, 2023)

Fibroblast Growth Factor 2 Levels in Patients with Major Depressive Disorder: A Meta-analysis - Yan-Li Wang; Yang Du; Lei Chen; Qing-Shan Liu; Yong Cheng (Journal of Molecular Neuroscience, 2023)

Erratum to: Rigid block characteristics on subaerial landslide-tsunamis using a 3D coupled Eulerian-Lagrangian model - Yi-ding Bao; Jian-ping Chen; Li-jun Su; Xin Zhou; Cheng-shan Yin (Journal of Mountain Science, 2023)

The phylogeny and divergence time of Ophiocordyceps sinensis and its host insects based on elongation factor 1 alpha - Shan Li; Yunguo Zhu; Zixian Xu; Lingling Chen; Wenqian Wang; Zhou Cheng (Archives of Microbiology, 2023)

The nitrogen transformation and controlling mechanism of NH3 and HCN conversion during the catalytic pyrolysis of amino acid - Hong Tian; Yangyue Wei; Zhangjun Huang; Yingquan Chen; Obid Tursunov; Shan Cheng; Haiping Yang; Yang Yang (Fuel, 2023)

Expanded polystyrene buoys as an important source of hexabromocyclododecanes for aquatic ecosystem: Evidence from field exposure with different substrates - Yun-Feng Pan; Shan Liu; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Environmental Pollution, 2023)

DNAzymes-conjugated upconversion nanoamplicon for in-situ ultrasensitive detection and imaging of microRNA in vivo - Yi Zhang; Da Luo; Yin Zhang; Qi-Hai Zhang; Qing-Yuan Ji; Shi-Kang Zhou; Shan Huang; Li-li Li; Feng Lu; Wei-Feng Yao; Fang-Fang Cheng; Jun-Jie Zhu; et al. (Chemical Engineering Journal, 2023)

Extension of the Lifespan of a Mouse Model of Rett Syndrome by Intracerebroventricular Delivery of MECP2 - Kan Yang; Cheng Cheng; Yiting Yuan; Yuefang Zhang; Shifang Shan; Zilong Qiu (Neuroscience Bulletin, 2023)

Rigid block characteristics on subaerial landslide-tsunamis using a 3D coupled Eulerian-Lagrangian model - Yi-ding Bao; Jian-ping Chen; Li-jun Su; Xin Zhou; Cheng-shan Yin (Journal of Mountain Science, 2023)

Study of Walnut brown rot caused by Botryosphaeria dothidea in the Guizhou Province of China - Cheng Li; Manman Zhang; Shan Wei; Zaifu Yang; Xuejun Pan (Crop Protection, 2023)

Selective detection of trace carbon monoxide at room temperature based on CuO nanosheets exposed to (111) crystal facets - Yuanyuan Wu; Ji Li; Mingsong Lv; Xianfa Zhang; Rui Gao; Chuanyu Guo; Xiaoli Cheng; Xin Zhou; Yingming Xu; Shan Gao; Zoltán Major; Lihua Huo (Journal of Hazardous Materials, 2023)

Catalytic pyrolysis of spent bleaching clay for its regeneration and simultaneously producing aromatic hydrocarbons - Kai Li; Zhu-yu Li; Cheng-Bo Zhang; Jia-qi Zhao; Li Zhao; Ji Liu; Shan-wei Ma; Qiang Lu (Journal of Cleaner Production, 2023)

An agro-hydrological process-based export coefficient model for estimating monthly non-point source loads in a semiarid agricultural area - Shan Zhang; Guanhui Cheng; Qian Tan; Hang Zhao; Tong Zhang (Journal of Cleaner Production, 2023)

The interaction between temperature and citric acid treatment in the anaerobic fermentation of Chinese cabbage waste - Jiawei Li; Qingwei Meng; Cheng Wang; Chunsheng Song; Yinfeng Lyu; Jianping Li; Anshan Shan (Journal of Cleaner Production, 2023)

Experimental and theoretical study on the transformation of typical organic sulfur during hydrothermal carbonization of sludge - Shan Cheng; Jingchun Huang; Rui Luo; Hong Tian; Yanshan Yin; Yu Qiao (Fuel, 2023)

PGC-1α/NRF1-dependent cardiac mitochondrial biogenesis: A druggable pathway of calycosin against triptolide cardiotoxicity - Xiao-Ming Qi; Yuan-Biao Qiao; Yuan-Lin Zhang; Ai-Cheng Wang; Jin-Hong Ren; Hui-Zhi Wei; Qing-Shan Li (Food and Chemical Toxicology, 2023)

Soil phosphorus availability and utilization are mediated by plant facilitation via rhizosphere interactions in an intercropping system - Shuang-Guo Zhu; Zheng-Guo Cheng; Jing Wang; Dong-Shan Gong; Fazal Ullah; Hong-Yan Tao; Hao Zhu; Hai-Xia Duan; Yu-Miao Yang; You-Cai Xiong (European Journal of Agronomy, 2023)

Combined application of chemical fertilizer with green manure increased the stabilization of organic carbon in the organo-mineral complexes of paddy soil - Peidong Xu; Ji Wu; Hui Wang; Shan Tang; Wenlong Cheng; Min Li; Rongyan Bu; Shang Han; Mingjian Geng (Environmental Science and Pollution Research, 2023)

Exploration of long afterglow luminescent materials composited with graphitized carbon nitride for photocatalytic degradation of basic fuchsin - Shan-Shan Li; Min Liu; Li Wen; Zhou Xu; Yun-Hui Cheng; Mao-Long Chen (Environmental Science and Pollution Research, 2023)

The diversity and structure of diazotrophic communities in the rhizosphere of coastal saline plants is mainly affected by soil physicochemical factors but not host plant species - Yanjing Song; Lan Ma; Haiyang Zhang; Rao Fu; Xiaoyan Liang; Junlin Li; Jiajia Li; Meng Li; Yan Shan; Jieshan Cheng; Xiangyu Wang; Hongxia Zhang (Frontiers in Marine Science, 2022)
The diversity and community structure of rhizospheric microbes are largely affected by soil physicochemical properties and plant species. In this work, high throughput sequencing and quantitative real-time PCR targeting nifH gene were used to assess the abundance and diversity of diazotrophic community in the coastal saline soils of Yellow River Delta (YRD). We demonstrated that the copy number of nifH gene encoding the Fe protein subunit of the nitrogenase in the nitrogen fixation process was significantly affected by soil physiochemical factors, and the abundance of diazotrophs in the rhizospheric soil samples collected from different locations was positively related with soil physicochemical properties. Soil salinity ( P =0.003) and moisture ( P =0.003) were significantly co-varied with the OTU-based community composition of diazotrophs. Taxonomic analysis showed that most diazotrophs belonged to the Alphaproteobacteria , Gammaproteobacteria and Deltaproteobacteria . Linear discriminant analysis (LDA) effect size (LEfSe) and canonical correspondence analysis (CCA) showed that diazotrophic community structure significantly varied with soil salinity, moisture, pH and total nitrogen, carbon, sulphur and nitrite (NO 2 – N) content. Our findings provide direct evidence toward the understanding of different effects of soil physicochemical properties and host plant traits such as halophytes types, life span and cotyledon type, on the community composition of diazotrophic populations in the rhizosphere of plants grown in coastal saline soils.

Mesenchymal Stem Cell Secreted-Extracellular Vesicles are Involved in Chondrocyte Production and Reduce Adipogenesis during Stem Cell Differentiation - Yu-Chen Tsai; Tai-Shan Cheng; Hsiu-Jung Liao; Ming-Hsi Chuang; Hui-Ting Chen; Chun-Hung Chen; Kai-Ling Zhang; Chih-Hung Chang; Po-Cheng Lin; Chi-Ying F. Huang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Extracellular vesicles (EVs) are derived from internal cellular compartments, and have potential as a diagnostic and therapeutic tool in degenerative disease associated with aging. Mesenchymal stem cells (MSCs) have become a promising tool for functional EVs production. This study investigated the efficacy of EVs and its effect on differentiation capacity. Methods: The characteristics of MSCs were evaluated by flow cytometry and stem cell differentiation analysis, and a production mode of functional EVs was scaled from MSCs. The concentration and size of EVs were quantitated by Nanoparticle Tracking Analysis (NTA). Western blot analysis was used to assess the protein expression of exosome-specific markers. The effects of MSC-derived EVs were assessed by chondrogenic and adipogenic differentiation analyses and histological observation. Results: The range of the particle size of adipose-derived stem cells (ADSCs)- and Wharton’s jelly -MSCs-derived EVs were from 130 to 150 nm as measured by NTA, which showed positive expression of exosomal markers. The chondrogenic induction ability was weakened in the absence of EVs in vitro . Interestingly, after EV administration, type II collagen, a major component in the cartilage extracellular matrix, was upregulated compared to the EV-free condition. Moreover, EVs decreased the lipid accumulation rate during adipogenic induction. Conclusion: The results indicated that the production model could facilitate production of effective EVs and further demonstrated the role of MSC-derived EVs in cell differentiation. MSC-derived EVs could be successfully used in cell-free therapy to guide chondrogenic differentiation of ADSC for future clinical applications in cartilage regeneration.

FAT1 downregulation enhances stemness and cisplatin resistance in esophageal squamous cell carcinoma - Yuanfang Zhai; Chengyuan Shan; Haoyu Zhang; Pengzhou Kong; Ling Zhang; Yanqiang Wang; Xiaoling Hu; Xiaolong Cheng (Molecular and Cellular Biochemistry, 2022)

Developmental Exposure to Bisphenol a Degrades Auditory Cortical Processing in Rats - Binliang Tang; Kailin Li; Yuan Cheng; Guimin Zhang; Pengying An; Yutian Sun; Yue Fang; Hui Liu; Yang Shen; Yifan Zhang; Ye Shan; Étienne de Villers-Sidani; et al. (Neuroscience Bulletin, 2022)

Trimethylamine N-oxide facilitates the progression of atrial fibrillation in rats with type 2 diabetes by aggravating cardiac inflammation and connexin remodeling - Wan-Ying Jiang; Jun-Yu Huo; Sheng-Chan Wang; Yan-Di Cheng; Yi-Ting Lyu; Zhi-Xin Jiang; Qi-Jun Shan (Journal of Physiology and Biochemistry, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Improving language model of human genome for DNA–protein binding prediction based on task-specific pre-training - Hanyu Luo; Wenyu Shan; Cheng Chen; Pingjian Ding; Lingyun Luo (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Bamboo cellulose–derived activated carbon aerogel with controllable mesoporous structure as an effective adsorbent for tetracycline hydrochloride - Ce Cui; Mengyuan Yang; Jianyu Zhai; Wenhao Bai; Lanling Dai; Li Liu; Shan Jiang; Weijie Wang; Erhui Ren; Cheng Cheng; Ronghui Guo (Environmental Science and Pollution Research, 2022)

Contact toxicity and repellence of essential oil from Senecio scandens and its major components against three stored product insects - Fang He; Jing-Yu Liu; Li-Jiang Chen; Zi-Qian Cheng; Meng-Qi Cheng; Shu-Shan Du; Yu-Li Sang; Yan-Jun Hao (Natural Product Research, 2022)

Triphenylpyrazoline ketone chlorophenols as potential candidate compounds against Parkinson’s disease: design, synthesis, and biological evaluation - Ning Ning Cheng; Le Hua Zhang; Rui Ge; Xiu E. Feng; Qing Shan Li (Medicinal Chemistry Research, 2022)

An enhanced method for estimating snow water equivalent in the central part of the Tibetan Plateau using raster segmentation and eigenvector spatial filtering regression model - Qi-shan Cheng; Yu-min Chen; Jia-xin Yang; Yue-jun Chen; Zhe-xin Xiong; An-nan Zhou (Journal of Mountain Science, 2022)

Basin structure and multiresource potential based on high-precision airborne gravity and magnetic data - Yan-Xu Liu; Wen-Yong Li; An-Qi Cao; Shan Gao; Ning Wang; Li-Jie Wang; Cheng Yang (Applied Geophysics, 2022)

Nanoscale storage encryption: data storage in synthetic DNA using a cryptosystem with a neural network - Yue Teng; Shan Yang; Liyan Liu; Ruicun Liu; Yaofeng Chen; Jinyu Li; Qian Yang; Tuoyu Liu; Yujun Cui; Peng Cheng; Shengqi Wang (Science China Life Sciences, 2022)

Association between secondhand smoke and peripheral arterial disease: a meta-analysis of cross-sectional studies - Chih-Wei Wu; Hung-Yi Chuang; Kazuhiro Watanabe; Pei-Shan Wu; Hui-Chen Pan; Chao-Ling Wang; Chen-Cheng Yang; Chih-Hsing Hung; Chia-Yen Dai; Chi-Kung Ho; Norito Kawakami (International Archives of Occupational and Environmental Health, 2022)

Application of Bone Marrow Mesenchymal Stem Cells Effectively Eliminates Endotoxemia to Protect Rat from Acute Liver Failure Induced by Thioacetamide - Ting Jiang; Geng Xia; Bo Yang; Hong-wei Zhang; Yue-shan Yin; Cheng-wei Tang; Jin-hui Yang (Tissue Engineering and Regenerative Medicine, 2022)
Background: Endotoxemia is related to worse clinical outcomes in acute liver failure (ALF), but its management remains unsatisfactory. In this study, we aimed to assess whether the application of bone marrow mesenchymal stem cells (BMSCs) could eliminate endotoxemia and protect rats against ALF induced by thioacetamide (TAA). Methods: BMSCs were isolated from rats and identified by the specific morphology, differentiation potential, and surface markers. The optimal dose of TAA for this study was explored and TAA-induced ALF rats were randomized to three groups: the normal control group (Saline), ALF group (TAA + Saline), and BMSCs-treated group (TAA + BMSCs). The intestinal migration and differentiation of BMSCs was tracked in vivo , and intestinal permeability, endotoxin and inflammatory cytokines, histology, and mortality were analyzed. Moreover, we added the inhibitor of the PI3K/AKT/mTOR signaling pathway into the co-culture system of BMSCs with enterocytes and then performed CK and Villin expression experiments to assess the role of PI3K/AKT/mTOR signal pathway in the intestinal differentiation of BMSCs. Results: BMSCs migrated to the intestinal injury sites and differentiated into enterocytes, intestinal permeability was decreased compared with the ALF group. The higher expression of endotoxin and inflammatory cytokines were reversed after BMSCs transplantation in rats with ALF. Mortality and intestinal lesion were significantly decreased. Blocking the PI3K/AKT/mTOR signal pathway inhibited BMSCs’ intestinal differentiation in vitro . Conclusion: BMSCs can eliminate endotoxemia and reduce mortality in rats with ALF, and the PI3K/AKT/mTOR signal pathway is involved in intestinal differentiation. BMSCs transplantation could be a potential candidate for the treatment of endotoxemia in ALF.

Morphologic changes of simple star dunes during the growth process in Dunhuang, China - Zhi-shan An; Ke-cun Zhang; Li-hai Tan; Qing-he Niu; Ben-li Liu; Bai-cheng Niu (Journal of Mountain Science, 2022)

Photocatalytic degradation of imidacloprid by optimized Bi2WO6/NH2-MIL-88B(Fe) composite under visible light - Mao-Long Chen; Tian-Hui Lu; Shan-Shan Li; Li Wen; Zhou Xu; Yun-Hui Cheng (Environmental Science and Pollution Research, 2022)

Correction to: Clinical profile of children with parechovirus meningitis in Singapore - Jessica Hui Yin Tan; Chew Thye Choong; Nancy Wen Sim Tee; Chia Yin Chong; Koh Cheng Thoon; Matthias Maiwald; Elis Yue Xian Lee; Melody Si Shan Tan; Natalie Woon Hui Tan (Journal of NeuroVirology, 2022)

Clinical profile of children with parechovirus meningitis in Singapore - Jessica Hui Yin Tan; Chew Thye Choong; Nancy Wen Sim Tee; Chia Yin Chong; Koh Cheng Thoon; Matthias Maiwald; Elis Yue Xian Lee; Melody Si Shan Tan; Natalie Woon Hui Tan (Journal of NeuroVirology, 2022)

Global Rainstorm Disaster Risk Monitoring Based on Satellite Remote Sensing - Suling Ren; Xiuzhen Han; Jun Yang; Shihao Tang; Yang Zhang; Tianchan Shan; Cheng Liu (Journal of Meteorological Research, 2022)

Chemical constituents from the fruits of Piper longum L. and their vascular relaxation effect on rat mesenteric arteries - Dan Li; Rui Wang; Xiaohan Cheng; Jianfeng Yang; Yihui Yang; Huichong Qu; Sen Li; Shan Lin; Donghua Wei; Yuhua Bai; Xiaodong Zheng (Natural Product Research, 2022)

Study on the Pyrolysis Characteristics, Kinetics and Mineral Transformation of Paper Sludge - Yanshan Yin; Huixia Yin; Zihan Yuan; Zihua Wu; Wei Zhang; Hong Tian; Leihua Feng; Shan Cheng; Mengxia Qing; Quanbin Song (BioEnergy Research, 2021)

Nisaea sediminum sp. nov., a heavy metal resistant bacterium isolated from marine sediment in the East China Sea - Suting Zhu; Yuping Cheng; Chaobo Guo; Feilu Xie; Dawoon Jung; Weiyan Zhang; Shan He (Antonie van Leeuwenhoek, 2021)

Study on synthesis and anticancer activity of 17beta-estradiol-phenol/aniline nitrogen mustard derivatives - Yu-dong Yin; Jing-jing Liu; Wen-fei Liao; Xian-kun Guo; Li-shan Zhang; Wei-bin Mo; Ke-guang Cheng (Medicinal Chemistry Research, 2021)

Patient Confidential Information Transmission Using the Integration of PSO-Based Biomedical Signal Steganography and Threshold-Based Compression - Shih-Ying Chen; Shan-Ju Lin; Ming-Cheng Tsai; Ming-Dar Tsai; Yih-Jing Tang; Shuo-Tsung Chen; Li-Hsiang Wang (Journal of Medical and Biological Engineering, 2021)

Concentration-dependent Differences in Urinary Iodine Measurements Between Inductively Coupled Plasma Mass Spectrometry and the Sandell-Kolthoff Method - Yongze Li; Shuangning Ding; Cheng Han; Aihua Liu; Zhongyan Shan; Weiping Teng; Jinyuan Mao (Biological Trace Element Research, 2021)
A large amount of historical data regarding urinary iodine concentration (UIC) were measured with the Sandell-Kolthoff (S-K) method for iodine nutrition surveillance. The congruence in urinary iodine measurements between inductively coupled plasma mass spectrometry (ICP-MS) and the S-K method has been debated. A total of 2064 adult urine samples were included in the present study. The UIC measurement results obtained simultaneously by standardized ICP-MS and the S-K method were analyzed. The UIC obtained with ICP-MS was significantly higher than that obtained with the S-K method (158 μg/L vs. 148 μg/L, p < 0.001). The Bland-Altman difference plot showed a small but significant mean difference of 6.12 μg/L between the two methods. The stratified analysis showed that the correlation coefficient was higher in the UIC < 300 μg/L group than the UIC ≥ 300 μg/L group (0.93 vs. 0.88, p = 0.0001). The mean difference between the S-K and ICP-MS methods was positively correlated with the UIC. The ICP-MS and S-K methods were comparable when the UIC was less than 300 μg/L; however, UIC values between 300 and 600 μg/L should be compared with caution after considering the research objective. We do not suggest comparing UICs obtained from the ICP-MS and S-K methods in iodine monitoring studies if the UIC is greater than 600 μg/L.

Microbulbifer hainanensis sp. nov., a moderately halopilic bacterium isolated from mangrove sediment - Yuping Cheng; Suting Zhu; Chaobo Guo; Feilu Xie; Dawoon Jung; Shengying Li; Weiyan Zhang; Shan He (Antonie van Leeuwenhoek, 2021)

Detection of Vestibular Schwannoma on Triple-parametric Magnetic Resonance Images Using Convolutional Neural Networks - Tzu-Hsuan Huang; Wei-Kai Lee; Chih-Chun Wu; Cheng-Chia Lee; Chia-Feng Lu; Huai-Che Yang; Chun-Yi Lin; Wen-Yuh Chung; Po-Shan Wang; Yen-Ling Chen; Hsiu-Mei Wu; Wan-You Guo; et al. (Journal of Medical and Biological Engineering, 2021)
Purpose The first step in typical treatment of vestibular schwannoma (VS) is to localize the tumor region, which is time-consuming and subjective because it relies on repeatedly reviewing different parametric magnetic resonance (MR) images. A reliable, automatic VS detection method can streamline the process. Methods A convolutional neural network architecture, namely YOLO-v2 with a residual network as a backbone, was used to detect VS tumors from MR images. To heighten performance, T1-weighted–contrast-enhanced, T2-weighted, and T1-weighted images were combined into triple-channel images for feature learning. The triple-channel images were cropped into three sizes to serve as input images of YOLO-v2. The VS detection effectiveness levels were evaluated for two backbone residual networks that downsampled the inputs by 16 and 32. Results The results demonstrated the VS detection capability of YOLO-v2 with a residual network as a backbone model. The average precision was 0.7953 for a model with 416 × 416-pixel input images and 16 instances of downsampling, when both the thresholds of confidence score and intersection-over-union were set to 0.5. In addition, under an appropriate threshold of confidence score, a high average precision, namely 0.8171, was attained by using a model with 448 × 448-pixel input images and 16 instances of downsampling. Conclusion We demonstrated successful VS tumor detection by using a YOLO-v2 with a residual network as a backbone model on resized triple-parametric MR images. The results indicated the influence of image size, downsampling strategy, and confidence score threshold on VS tumor detection.

Building change detection in very high-resolution remote sensing image based on pseudo-orthorectification - Hui Chen; Ka Zhang; Wen Xiao; Yehua Sheng; Liang Cheng; Wei Zhou; Pengbo Wang; Dong Su; Longjie Ye; Shan Zhang (International Journal of Remote Sensing, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

New cytotoxic biflavones from Selaginella doederleinii - Li-Fei Liu; Hui-Hui Sun; Jian-Bing Tan; Qi Huang; Fei Cheng; Kang-Ping Xu; Zhen-Xing Zou; Gui-Shan Tan (Natural Product Research, 2021)

Polybrominated diphenyl ethers in soils from Tianjin, North China: distribution, health risk, and temporal trends - Yu Han; Jiali Cheng; Lei He; Minna Zhang; Shan Ren; Jiazheng Sun; Xiangyang Xing; Zhenwu Tang (Environmental Geochemistry and Health, 2021)

Assisted selection of eating quality progeny of indica (O. sativa L. ssp. indica) and japonica (O. sativa L. ssp. japonica) hybrids using rice starch properties - Ting Mao; Zhan Zhang; Shan Jun Ni; Yi Zhou Zhao; Xin Li; Li Li Zhang; Yan Liu; Cheng Shun Zhong; He Huang; Shao Lin Wang; Xu Li (Genetic Resources and Crop Evolution, 2021)

Sustained effects of one-time sewage sludge addition on rice yield and heavy metals accumulation in salt-affected mudflat soil - Wengang Zuo; Yanchao Bai; Ming Lv; Zehui Tang; Cheng Ding; Chuanhui Gu; Yuhua Shan; Qigen Dai; Min Li (Environmental Science and Pollution Research, 2021)

Effects of Low Temperature Stress on the Morphology and hsp70 and hsp90 Gene Expression of Phascolosoma esculenta - Weiliang Shen; Cheng Liu; Jie Ni; Xinming Gao; Junjie Ni; Jianping Wang; Shan Jin; Congcong Hou; Xiongfei Wu; Junquan Zhu (Journal of Ocean University of China, 2021)

A New Endoplasmic Reticulum (ER)-Targeting Fluorescent Probe for the Imaging of Cysteine in Living Cells - Lei Zhou; Yunxia Li; Aiqin Zhou; Guanghui Zhang; Zhi-Qiang Cheng; Yong-Xi Ge; Shan-Kui Liu; Ricardo Bentes Azevedo; Juan Zhang; Shenglin Jiang; Cheng-Shi Jiang (Journal of Fluorescence, 2020)

Chemical constituents from common vetch ( Vicia sativa L.) and their antioxidant and cytotoxic activities - Li-Fang Liu; Wen-Hai Li; Man-Yu Li; Xiao-Zhen Wu; Fan Yang; Jia-Nan Xu; Cheng-Shan Yuan (Natural Product Research, 2020)

Physiological and transcriptional response to heat stress in heat-resistant and heat-sensitive maize (Zea mays L.) inbred lines at seedling stage - De-Chuan Wu; Jia-Fei Zhu; Zhong-Ze Shu; Wei Wang; Cheng Yan; Shan-Bin Xu; De-Xiang Wu; Cheng-Yu Wang; Zhao-rong Dong; Genlou Sun (Protoplasma, 2020)

A Comparative Study of Associated Microbiota Between Pig Farm and Pig Slaughterhouse in Guangdong, China - Jian-Yong Wu; Yan-Shan Zhu; Cheng Guo; Yao Xia; Zhong-Min Guo; Qian-Lin Li; Jia-Hai Lu (Current Microbiology, 2020)

Functional Analysis of a Fibronectin Binding Protein of Streptococcus parasanguinis FW213 - Yi-Ywan M. Chen; Pei-Shan Lu; Pei-Hua Tsai; Cheng-Hsun Chiu (Current Microbiology, 2020)

Isopimarane-type diterpenoids from Croton laevigatus - Man-Yu Li; Zheng-Zhi Han; Li-Fang Liu; Xiao-Zhen Wu; Wen-Jun Huang; Kai Wang; Fan Yang; Cheng-Shan Yuan (Natural Product Research, 2020)

Two new anthraquinone derivatives and one new triarylbenzophenone analog from Selaginella tamariscina - Rui Liu; Hui Zou; Zhen-Xing Zou; Fei Cheng; Xia Yu; Ping-Sheng Xu; Xiao-Min Li; Dai Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

The completed macronuclear genome of a model ciliate Tetrahymena thermophila and its application in genome scrambling and copy number analyses - Yalan Sheng; Lili Duan; Ting Cheng; Yu Qiao; Naomi A. Stover; Shan Gao (Science China Life Sciences, 2020)

Effects of fungus–host associations on nucleoside differences among Ophiocordyceps sinensis populations on the Qinghai–Tibet Plateau of China - Zixian Xu; Shan Li; Lingling Chen; Yunguo Zhu; Lingyan Xuan; Zhou Cheng (Archives of Microbiology, 2020)

Blood and Cerebrospinal Fluid Autoantibody to Aβ Levels in Patients with Alzheimer’s Disease: a Meta-Analysis Study - Xiao-Wan Li; Xi-Xi Li; Qing-Shan Liu; Yong Cheng (Journal of Molecular Neuroscience, 2020)

A special symptom of olfactory dysfunction in coronavirus disease 2019: report of three cases - Chen Chen; Moxian Chen; Cong Cheng; Yun Chi; Zhiliang Hu; Yuan Liu; Shan Huang; Yanling Lv; Chongfeng Liang; Damin Jiao; Yongxiang Yi; Xia Zhang; et al. (Journal of NeuroVirology, 2020)

Baicalein attenuates caspase-independent cells death via inhibiting PARP-1 activation and AIF nuclear translocation in cerebral ischemia/reperfusion rats - Wei-Han Li; Ying-Lin Yang; Xiao Cheng; Man Liu; Shan-Shan Zhang; Yue-Hua Wang; Guan-Hua Du (Apoptosis, 2020)

Pictalignans D-F, three new neolignan derivatives from Selaginella picta - Fei Cheng; Zhen-Xing Zou; Ping-Sheng Xu; Shui-Han Zhang; Yan Zhang; Cai-Ping Yao; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

Correction to: Galangin inhibits hypertrophic scar formation via ALK5/Smad2/3 signaling pathway - Yifan Zhang; Shengzhou Shan; Jing Wang; Xinyu Cheng; Bo Yi; Jia Zhou; Qingfeng Li (Molecular and Cellular Biochemistry, 2020)

Dynamic Alterations of Brain Injury, Functional Recovery, and Metabolites Profile after Cerebral Ischemia/Reperfusion in Rats Contributes to Potential Biomarkers - Xiao Cheng; Ying-Lin Yang; Wei-Han Li; Man Liu; Shan-Shan Zhang; Yue-Hua Wang; Guan-Hua Du (Journal of Molecular Neuroscience, 2020)

Comparison of two typical regeneration methods to the spent biological activated carbon in drinking water - Cheng Liu; Congcong Li; Yiwen Shan; Zhehao Sun; Wei Chen (Environmental Science and Pollution Research, 2020)

Vertical variation and temporal trends of extreme precipitation indices in a complex topographical watershed in the Hengduan Mountain Region, China - Qiankun Guo; Shiyue Cheng; Wei Qin; Duihu Ning; Zhijie Shan; Zhe Yin (International Journal of Climatology, 2020)
Spatial–temporal trends of extreme precipitation have great impacts on disaster risks, and relevant studies usually receive much attention. In China, spatial–temporal trends have been analysed in numerous studies based on daily rainfall data; however, the densities of rain gauges in many studies were relatively low, and the effects of complex topography on extreme precipitation were usually not considered, which have lowered the reliability and accuracy of the reported results. In this study, several widely used extreme precipitation indices were chosen, and the spatial–temporal trends of a typical watershed in the Hengduan Mountain Region in Southwest China, the Longchuanjiang watershed, were analysed using the Mann–Kendall trend analysis based on daily rainfall data. The effect of elevation on the extreme precipitation indices based on the high‐intensity rain gauges and the effect of elevation on the temporal trends of extreme precipitation indices were analysed, which have rarely been reported. The results indicated that: (a) significant positive correlations with elevation were reported for annual precipitation and most of the extreme precipitation indices, including PRCPTOT, Rx5day, R95P, R99P, RD, SDII, and CWD, while significant negative correlations were reported for CDD; the relationships between SDII and Rx1day were not significant with elevation; (b) the density of rain gauges in the regions with complex topography can have great impacts on the results; and (c) no significant correlation between the elevation and the temporal trends of extreme precipitation indices were reported. This study highlights the effects of the density of rain gauges and elevation, or topographical factors on the spatial distribution and temporal trends of extreme precipitation indices, which has rarely been reported in previous studies, implying that such effects should be fully taken into consideration in the relevant studies in the future.

Coupled modeling using PRZM/RICEWQ and SWAT for the North Tiaoxi Watershed - Yan Cheng; Junying Zhou; Jianhua Liao; Dazhi Mao; Wenlin Chen; Zhengjun Shan (Environmental Science and Pollution Research, 2020)

Dryland agricultural environment and sustainable productivity - Gou-Xia Li; Bing-Cheng Xu; Li-Na Yin; Shi-Wen Wang; Sui-Qi Zhang; Lun Shan; Sang-Soo Kwak; Qingbo Ke; Xi-Ping Deng (Plant Biotechnology Reports, 2020)

Insights into non-symbiotic plant growth promotion bacteria associated with nodules of Sphaerophysa salsula growing in northwestern China - Zhen-Shan Deng; Zhao-Yu Kong; Bao-Cheng Zhang; Long-Fei Zhao (Archives of Microbiology, 2020)

The giant Zaozigou Au-Sb deposit in West Qinling, China: magmatic- or metamorphic-hydrothermal origin? - Kun-Feng Qiu; Hao-Cheng Yu; Jun Deng; Duncan McIntire; Zong-Yang Gou; Jian-Zhen Geng; Zhao-Shan Chang; Rui Zhu; Kang-Ning Li; Richard Goldfarb (Mineralium Deposita, 2020)

Interaction between CA repeat microsatellites and HIF1α regulated the transcriptional activity of porcine IGF1 promoter - Hongwei Geng; Linlin Hao; Yunyun Cheng; Chunli Wang; Shan Huang; Wenzhen Wei; Rui Yang; Haoyang Li; Songcai Liu; Hao Yu; Huayi Lu (Journal of Applied Genetics, 2020)

Bioavailable phosphorus distribution in alpine meadow soil is affected by topography in the Tian Shan Mountains - Fa-Yong Li; Cheng-yu Yuan; Zi-Qiang Yuan; Yong-jun You; Xue-fei Hu; Shan Wang; Guo-yu Li (Journal of Mountain Science, 2020)

Leveraging complementary computational models for prioritizing chemicals of developmental and reproductive toxicity concern: an example of food contact materials - Chun-Wei Tung; Hsien-Jen Cheng; Chia-Chi Wang; Shan-Shan Wang; Pinpin Lin (Archives of Toxicology, 2020)

Development of a Two-Compartment System In vitro Dissolution Test and Correlation with In vivo Pharmacokinetic Studies for Celecoxib - Shan Jiang; Guoqing Zhang; Lei Wang; Ye Zeng; Wenjie Liu; Zeneng Cheng (AAPS PharmSciTech, 2020)

A challenge in anaerobic digestion of swine wastewater: recalcitrance and enhanced-degradation of dietary fibres - Zhuo Zeng; Ping Zheng; Cheng Shi; Meng Zhang; Yiyu Li; Wudi Zhang; Shengdao Shan (Biodegradation, 2019)

Our recent progress in epigenetic research using the model ciliate, Tetrahymena thermophila - Ting Cheng; Yuanyuan Wang; Jie Huang; Xiao Chen; Xiaolu Zhao; Shan Gao; Weibo Song (Marine Life Science & Technology, 2019)
Epigenetic research focuses on heritable changes beyond the DNA sequence, which has led to a revolution in biological studies and benefits in many other fields. The well-known model ciliate, Tetrahymena thermophila offers a unique system for epigenetic studies due to its nuclear dimorphism and special mode of sexual reproduction (conjugation), as well as abundant genomic resources and genetic tools. In this paper, we summarize recent progress made by our research team and collaborators in understanding epigenetic mechanisms using Tetrahymena. This includes: (1) providing the first genome-wide base pair-resolution map of DNA N 6 -methyladenine (6mA) and revealed it as an integral part of the chromatin landscape; (2) dissecting the relative contribution of cis - and trans - elements to nucleosome distribution by exploring the unique nuclear dimorphism of Tetrahymena ; (3) demonstrating the epigenetic controls of RNAi-dependent Polycomb repression pathways on transposable elements, and (4) identifying a new histone monomethyltransferase, TXR1 ( Tetrahymena Trithorax 1), that facilitates replication elongation through its substrate histone H3 lysine 27 monomethylation (H3K27me1).

Anti-angiogenic and anti-inflammatory effects of CD200–CD200R1 axis in oxygen-induced retinopathy mice model - Yaguang Hu; Ting Wei; Shan Gao; Qiaochu Cheng (Inflammation Research, 2019)

The origin of high hydrocarbon groundwater in shallow aquifer: experimental evidences from water-rock interaction - Shan Liu; Shihua Qi; Zhaohui Luo; Harold Wilson T. Mapoma; Zhihua Chen; Shenggao Cheng (Environmental Science and Pollution Research, 2019)

Design and Experiment of a Plateau Data-Gathering AUV - Hao Xu; Guo-Cheng Zhang; Yu-Shan Sun; Shuo Pang; Xiang-Rui Ran; Xiang-Bin Wang (Journal of Marine Science and Engineering, 2019)
The design, control, and implementation of an autonomous underwater vehicle (AUV) for collecting hydrological information from plateau rivers and lakes are presented in this paper. The hardware and software structures of the control system were previously described. A novel sliding mode controller (SMC) with combinational reaching law of vertical hovering motion is proposed to improve the robustness and stability. The S-plane control, a nonlinear controller with little parameters, is used in the horizontal motion. Besides, the navigation strategy based on the dead-reckoning algorithm, a path tracking based on the light-of-sight (LOS) algorithm, and a control allocation strategy considering saturation are present. Finally, experiments were performed in a tank and in a river in the Qinghai–Tibet Plateau to prove the feasibility and reliability of the AUV system.

Molecular Screening of Behaviorally Active Compounds with CmedOBP14 from the Rice Leaf Folder Cnaphalocrocis medinalis - Shuang-Feng Sun; Fang-Fang Zeng; Shan-Cheng Yi; Man-Qun Wang (Journal of Chemical Ecology, 2019)

New adenine analogues and a pyrrole alkaloid from Selaginella delicatula - Cai-Ping Yao; Zhen-Xing Zou; Yan Zhang; Jing Li; Fei Cheng; Ping-Sheng Xu; Gan Zhou; Xiao-Min Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2019)

How much of Typhoon Morakot's extreme rainfall is attributable to anthropogenic climate change? - Chung‐Chieh Wang; Li‐Shan Tseng; Chien‐Chang Huang; Shih‐How Lo; Cheng‐Ta Chen; Pi‐Yu Chuang; Nan‐Chou Su; K. Tsuboki (International Journal of Climatology, 2019)
Typhoon Morakot (2009), which made landfall in Taiwan during August 7–9, 2009, produced the highest rainfall and became the deadliest typhoon ever recorded in Taiwan since 1958. To assess the role of anthropogenic climate change in the typhoon‐related torrent, we compare the water budget between a pair of cloud‐resolving sensitivity experiments. The pair consists of a control simulation that reproduces Typhoon Morakot (2009) in current climate and a sensitivity simulation in which the same storm is placed in a slightly different climate background where the late 20th century anthropogenic climate change signal is removed. The anthropogenic signal is estimated with the CMIP5 experiments of 18 models for the period of 1985–2005, during which the global warming trend is discernible. In climate states that differ merely by a 20‐year mean anthropogenic change, Morakot (2009) yields 3.4–3.6% more total rainfall in the control experiment than its sensitivity counterpart within a radius of 300–500 km from the storm centre. Water budget analysis indicates that the increase in typhoon rainfall is mainly resulted from the enhanced convergence of vapour flux. The enhancement is, in turn, contributed by the increased tropospheric moisture due to global warming and, to a lesser extent, by a more active secondary circulation in the storm that is associated with the anthropogenic climate change.

Giant Submarine Landslide in the South China Sea: Evidence, Causes, and Implications - Chaoqi Zhu; Sheng Cheng; Qingping Li; Hongxian Shan; Jing’an Lu; Zhicong Shen; Xiaolei Liu; Yonggang Jia (Journal of Marine Science and Engineering, 2019)
Submarine landslides can be tremendous in scale. They are one of the most important processes for global sediment fluxes and tsunami generation. However, studies of prodigious submarine landslides remain insufficient. In this review paper, we compile, summarize, and reanalyze the results of previous studies. Based on this reanalysis, we discover the giant Baiyun–Liwan submarine slide in the Pearl River Mouth Basin, South China Sea. We describe three concurrent pieces of evidence from ~23 Ma to 24 Ma, the Oligocene–Miocene boundary, for this landslide: the shoreward shift of the shelf break in the Baiyun Sag, the slump deposition to the southeast, and the abrupt decrease in the accumulation rate on the lower continental slope. This landslide extends for over 250 km, and the total affected area of the slide is up to ~35,000–40,000 km2. The scale of the landslide is similar to that of the Storegga slide, which has long been considered to be the largest landslide on earth. We suggest that strike–slip movement along the Red River Fault and ridge jump of the South China Sea caused the coeval Baiyun–Liwan submarine slide. The identification of the giant landslide will promote the understanding of not only its associated geohazards but also the steep rise of the Himalayan orogeny and marine engineering. More attention needs to be paid to areas with repeated submarine landslides and offshore installations.

First identification of cucumber mosaic virus infecting six fruit crops in China - Cheng-Ming Yu; Guo-Wei Geng; Xin-Ran Cao; Chen Yang; Zhe Qi; Shan-Shan Liu; Chang-Xiang Zhu; Xue-Feng Yuan (Journal of Plant Pathology, 2019)

A miR-511-binding site SNP in the 3′UTR of IGF-1 gene is associated with proliferation and apoptosis of PK-15 cells - Wenzhen Wei; Gang Wang; Yunyun Cheng; Rui Yang; Jie Song; Shan Huang; Haoyang Li; Hongwei Geng; Hao Yu; Songcai Liu; Linlin Hao (In Vitro Cellular & Developmental Biology - Animal, 2019)

Bazedoxifene protects cerebral autoregulation after traumatic brain injury and attenuates impairments in blood–brain barrier damage: involvement of anti-inflammatory pathways by blocking MAPK signaling - Yu-Long Lan; Xun Wang; Yu-Jie Zou; Jin-Shan Xing; Jia-Cheng Lou; Shuang Zou; Bin-Bin Ma; Yan Ding; Bo Zhang (Inflammation Research, 2019)

Characterization and risk assessment of heavy metals in road dust from a developing city with good air quality and from Shanghai, China - Xiaojia Chen; Meixiu Guo; Jingjing Feng; Shan Liang; Deming Han; Jinping Cheng (Environmental Science and Pollution Research, 2019)

Moringa Isothiocyanate Activates Nrf2: Potential Role in Diabetic Nephropathy - David Cheng; Linbo Gao; Shan Su; Davit Sargsyan; Renyi Wu; Ilya Raskin; Ah-Ng Kong (The AAPS Journal, 2019)

Gallic acid activates hippocampal BDNF-Akt-mTOR signaling in chronic mild stress - Ji-Xiao Zhu; Jia-Ling Shan; Wei-Qiong Hu; Jin-Xiang Zeng; Ji-Cheng Shu (Metabolic Brain Disease, 2019)

Functional analysis of the UL24 protein of suid herpesvirus 1 - Chao Ye; Jing Chen; Xuefei Cheng; Shasha Zhou; Shan Jiang; Jingjing Xu; Hao Zheng; Wu Tong; Guoxin Li; Guangzhi Tong (Virus Genes, 2019)

Multi-year assessment of paralytic shellfish toxins in hard clam species along the coastline of Jiangsu Province, China - Xinzhi Wang; Hao Wu; Ying Cheng; Hongmei Wen; Rui Liu; Libao Wang; Chenxiao Shan; Chuan Chai (Acta Oceanologica Sinica, 2019)

Effects of long-term 4-nonylphenol dietary exposure on reproductive ability of Japanese quails (Coturnix japonica) - Yan Cheng; Zhengjun Shan; Junying Zhou; Yuanqing Bu; Pengfu Li; Shan Lu (Environmental Science and Pollution Research, 2019)

Coralloluteibacterium thermophilus sp. nov., A Gammaproteobacterium Isolated from an Oil Reservoir - Jing You; Shan Hong; Jiliang Yu; Lisha Duan; Bo Liu; Bozhong Mu; Cheng Zhou; Yanfen Xue (Current Microbiology, 2018)

Abnormal functional connectivity density in sleep-deprived subjects - Liu Yang; Yu Lei; Lubin Wang; Pinhong Chen; Shan Cheng; Shanshan Chen; Jicheng Sun; Yanyan Li; Yihan Wang; Wendong Hu; Zheng Yang (Brain Imaging and Behavior, 2018)

Water Resources and Farmland Management in the Songhua River Watershed under Interval and Fuzzy Uncertainties - Cong Dong; Gordon Huang; Guanhui Cheng; Shan Zhao (Water Resources Management, 2018)

Dune dynamics in the southern edge of Dunhuang Oasis and implications for the oasis protection - Zhi-shan An; Ke-cun Zhang; Li-hai Tan; Hu Zhang; Bai-cheng Niu (Journal of Mountain Science, 2018)

Surface Water Control for Mining Thick, Relatively Shallow Coal Seams in the Loess Area of Western China - Ge Zhu; Xiong Wu; Shan Yu; Cheng Qian; Yanyan Dong; Chaojun Zhang; Chu Wu (Mine Water and the Environment, 2018)

Mechanisms of Interaction Between an Arch Dam and Abutment Slope Using Physical Model Tests - Guanhua Sun; Shan Lin; Shengguo Cheng; Tan Sui; Chunguang Li; Hong Zheng (Rock Mechanics and Rock Engineering, 2018)

Impacts of a Compound Amendment on Cd Immobilization, Enzyme Activities and Crop Uptake in Acidic Cd-Contaminated Paddy Soils - Shiping Shan; Zhaohui Guo; Ping Lei; Wei Cheng; Minxi Wu; Zujiao Fu; Shandong Wu; Dongxia Du; Liyang Wu (Bulletin of Environmental Contamination and Toxicology, 2018)

pTAC10, an S1-domain-containing component of the transcriptionally active chromosome complex, is essential for plastid gene expression in Arabidopsis thaliana and is phosphorylated by chloroplast-targeted casein kinase II - Qing-Bo Yu; Tuan-Tuan Zhao; Lin-Shan Ye; Ling Cheng; Ying-Qian Wu; Chao Huang; Zhong-Nan Yang (Photosynthesis Research, 2018)

Linkage disequilibrium and functional analysis of PRE1 insertion together with SNPs in the promoter region of IGFBP7 gene in different pig breeds - Qingyan Wu; Hao Yu; Wenzhen Wei; Yunyun Cheng; Shan Huang; Hongyu Shi; Songcai Liu; Jichao Xia; Hongyao Jia; Linlin Hao (Journal of Applied Genetics, 2018)

Combination of High-Sensitivity C-Reactive Protein and Homocysteine Predicts the Post-Stroke Depression in Patients with Ischemic Stroke - Li-Shan Cheng; Wen-Jun Tu; Yuan Shen; Li-Jun Zhang; Kangxiang Ji (Molecular Neurobiology, 2018)

Epirubicin induces apoptosis in osteoblasts through death-receptor and mitochondrial pathways - Tzu-Ching Huang; Pu-Rong Chiu; Wen-Tsan Chang; Bau-Shan Hsieh; Yu-Ci Huang; Hsiao-Ling Cheng; Li-Wen Huang; Yu-Chen Hu; Kee-Lung Chang (Apoptosis, 2018)

A new aromatic glycoside and its anti-proliferative activities from the leaves of Bergenia purpurascens - Shan-Shan Zhang; Zhi-Xin Liao; Ri-Zhen Huang; Cheng-Cheng Gong; Lan-Ju Ji; Hong-Fa Sun (Natural Product Research, 2018)

In Situ Observation of Hard Surrounding Rock Displacement at 2400-m-Deep Tunnels - Xia-Ting Feng; Zhi-Bin Yao; Shao-Jun Li; Shi-Yong Wu; Cheng-Xiang Yang; Hao-Sen Guo; Shan Zhong (Rock Mechanics and Rock Engineering, 2018)

Neuroprotective Effect and Mechanism of Action of Tetramethylpyrazine Nitrone for Ischemic Stroke Therapy - Gaoxiao Zhang; Tao Zhang; Liangmiao Wu; Xinhua Zhou; Jianbo Gu; Cuimei Li; Wei Liu; Cheng Long; Xifei Yang; Luchen Shan; Lipeng Xu; Yuqiang Wang; et al. (NeuroMolecular Medicine, 2018)

The origin of high hydrocarbon groundwater in shallow Triassic aquifer in Northwest Guizhou, China - Shan Liu; Shihua Qi; Zhaohui Luo; Fangzhi Liu; Yang Ding; Huanfang Huang; Zhihua Chen; Shenggao Cheng (Environmental Geochemistry and Health, 2018)

Effects of liquid layers and distribution patterns on three-phase saturation and relative permeability relationships: a micromodel study - Jui-Pin Tsai; Liang-Cheng Chang; Shao-Yiu Hsu; Hsin-Yu Shan (Environmental Science and Pollution Research, 2017)

Structural Transformation Detection Contributes to Screening of Behaviorally Active Compounds: Dynamic Binding Process Analysis of DhelOBP21 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Guangqiang Yu; Shan-Cheng Yi; Yinan Zhang; De-Xin Kong; Man-Qun Wang (Journal of Chemical Ecology, 2017)

Ursolic acid activates the TGR5 receptor to enhance GLP-1 secretion in type 1-like diabetic rats - Shih-Hsiang Lo; Yingxiao Li; Kai Chun Cheng; Chiang-Shan Niu; Juei-Tang Cheng; Ho-Shan Niu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Municipal solid waste management planning for Xiamen City, China: a stochastic fractional inventory-theory-based approach - Xiujuan Chen; Guohe Huang; Shan Zhao; Guanhui Cheng; Yinghui Wu; Hua Zhu (Environmental Science and Pollution Research, 2017)

Shading effect on survival, growth, and contents of secondary metabolites in micropropagated Anoectochilus plantlets - Changli Chen; Xiahong Luo; Guanrong Jin; Zhou Cheng; Xiaoyun Pan; Guanlin Zhu; Shan Li; Yunguo Zhu; Nannan Tang (Brazilian Journal of Botany, 2017)

The potential roles of dopamine in malignant glioma - Yu-Long Lan; Xun Wang; Jin-Shan Xing; Jia-Cheng Lou; Xiao-Chi Ma; Bo Zhang (Acta Neurologica Belgica, 2017)

Automatic Measurement of Cane Crushing Capacity Using a Nuclear-Free Online System Based on Angle Sensor and Distributed Control System - Dian-Zhi Hou; Yuan-Yuan Pu; Xiao-Mai Yao; Cheng Huang; Yan-Guang Zhu; Shan Chen (Sugar Tech, 2017)

Cell-culture derived fowl adenovirus serotype 4 inactivated vaccine provides complete protection for virus infection on SPF chickens - Dongying Du; Pantao Zhang; Xiangdong Li; Hui Tian; Yi Cheng; Dongbei Sheng; Xueying Han; Yihong Shan; Xuefeng Li; Yue Yuan; Haiyang Zhang; Jingjing Xue; et al. (VirusDisease, 2017)

Effects of fasting, temperature, and photoperiod on preproghrelin mRNA expression in Chinese perch - Yi Song; Cheng Zhao; Xu-fang Liang; Shan He; Changxu Tian; Xiaoyan Cheng; Xiaochen Yuan; Liyuan Lv; Wenjie Guo; Min Xue; Ya-Xiong Tao (Fish Physiology and Biochemistry, 2017)

Removal of nitrogen from wastewaters by anaerobic ammonium oxidation (ANAMMOX) using granules in upflow reactors - Chong-Jian Tang; Cheng-Shan Duan; Cheng Yu; Yu-Xia Song; Li-Yuan Chai; Ruiyang Xiao; Zongsu Wei; Xiao-Bo Min (Environmental Chemistry Letters, 2017)

Repellence of the main components from the essential oil of Glycosmis lucida Wall. ex Huang against two stored product insects - Shan-Shan Guo; Wen-Juan Zhang; Kai Yang; Jun-Yu Liang; Chun-Xue You; Cheng-Fang Wang; Yin-Ping Li; Zhu-Feng Geng; Zhi-Wei Deng; Shu-Shan Du (Natural Product Research, 2017)

Ginsenoside Rg1 promotes neural differentiation of mouse adipose-derived stem cells via the miRNA-124 signaling pathway - Juan Dong; Guo Zhu; Tian-cheng Wang; Fu-shan Shi (Journal of Zhejiang University-SCIENCE B, 2017)

ApoA-I/SR-BI modulates S1P/S1PR2-mediated inflammation through the PI3K/Akt signaling pathway in HUVECs - Kun Ren; Yan-Ju Lu; Zhong-Cheng Mo; Xing -Liu; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Li Li; Qing-Hai Zhang; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2017)

Influenza A virus upregulates PRPF8 gene expression to increase virus production - Chee-Hing Yang; Hui-Chun Li; Yu-Ling Shiu; Tzu-Shan Ku; Chia-Wen Wang; Yi-Shuan Tu; Hung-Ling Chen; Cheng-Hao Wu; Shih-Yen Lo (Archives of Virology, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

Lifetime regular exercise affects the incident of different arrhythmias and improves organismal health in aging female Drosophila melanogaster - Lan Zheng; Qiu Fang Li; Liu Ni; Hui Wang; Xiang Cheng Ruan; Xiu Shan Wu (Biogerontology, 2017)

ApoA-I induces S1P release from endothelial cells through ABCA1 and SR-BI in a positive feedback manner - Xing Liu; Kun Ren; Rong Suo; Sheng-Lin Xiong; Qing-Hai Zhang; Zhong-Cheng Mo; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2016)

Effect of Prolonged Iodine Overdose on Type 2 Iodothyronine Deiodinase Ubiquitination-Related Enzymes in the Rat Pituitary - Xiaowen Zhang; Yaqiu Jiang; Wenqing Han; Aihua Liu; Xiaochen Xie; Cheng Han; Chenling Fan; Hong Wang; Hongmei Zhang; Shuangning Ding; Zhongyan Shan; Weiping Teng (Biological Trace Element Research, 2016)

Amarogentin ameliorates diabetic disorders in animal models - Ho-Shan Niu; Pin-Chun Chao; Po-Ming Ku; Chiang-Shan Niu; Kung-Shing Lee; Juei-Tang Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Baseline sensitivity and control efficacy of pyrisoxazole against Botrytis cinerea - He Zhu; Cheng-Tian Huang; Ming-Shan Ji (European Journal of Plant Pathology, 2016)

The Role of MAPT in Neurodegenerative Diseases: Genetics, Mechanisms and Therapy - Cheng-Cheng Zhang; Ang Xing; Meng-Shan Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Adoptive therapy with CAR redirected T cells for hematological malignancies - Shiqi Li; Zhi Yang; Junjie Shen; Juanjuan Shan; Cheng Qian (Science China Life Sciences, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Review of studies on land use and land cover change in Nepal - Basanta Paudel; Yi-li Zhang; Shi-cheng Li; Lin-shan Liu; Xue Wu; Narendra Raj Khanal (Journal of Mountain Science, 2016)

Galangin inhibits hypertrophic scar formation via ALK5/Smad2/3 signaling pathway - Yifan Zhang; Shengzhou Shan; Jing Wang; Xinyu Cheng; Bo Yi; Jia Zhou; Qingfeng Li (Molecular and Cellular Biochemistry, 2016)

One-step Real-time Food Quality Analysis by Simultaneous DSC–FTIR Microspectroscopy - Shan-Yang Lin; Chih-Cheng Lin (Critical Reviews in Food Science and Nutrition, 2016)

Low-Dose Topical 5-Aminolevulinic Acid Photodynamic Therapy in the Treatment of Different Severity of Acne Vulgaris - Shi-qin Tao; Fei Li; Lei Cao; Ru-shan Xia; Hua Fan; Ying Fan; Hui Sun; Cheng Jing; Li-jia Yang (Cell Biochemistry and Biophysics, 2015)

Analysis of Mineral Elements, Metabolism, and Inflammation Indexes in the Plasma of Dairy Cows Suffering from Different Degrees of Lameness - Dongbo Sun; Chunqiu Li; Cheng Gu; Jianfei Chen; Yongli Qu; Xinyu Wang; Jing Gao; Shan Wei; Jianfa Wang; Rui Wu; Donghua Guo (Biological Trace Element Research, 2015)

The Optimum Level of Sevoflurane in Pediatric Echocardiography - Fan Conghai; Zhang Fengchao; Shan Chengjing; Wen Cheng; Wang Yunji; Li Xiaobo (Cell Biochemistry and Biophysics, 2015)

Ecotoxicity of two organophosphate pesticides chlorpyrifos and dichlorvos on non-targeting cyanobacteria Microcystis wesenbergii - Kai-Feng Sun; Xiang-Rong Xu; Shun-Shan Duan; You-Shao Wang; Hao Cheng; Zai-Wang Zhang; Guang-Jie Zhou; Yi-Guo Hong (Ecotoxicology, 2015)

Development of a Fluorescence-Linked Immunosorbent Assay for Baicalin - Wenchao Shan; Jinjun Cheng; Baoping Qu; Jiayang Sai; Hui Kong; Huihua Qu; Yan Zhao; Qingguo Wang (Journal of Fluorescence, 2015)

Flavobacterium notoginsengisoli sp. nov., isolated from the rhizosphere of Panax notoginseng - Meng-Yue Zhang; Huan Xu; Tian-Yuan Zhang; Jun Xie; Juan Cheng; Salam Nimaichand; Shan-Hui Li; Wen-Jun Li; Yi-Xuan Zhang (Antonie van Leeuwenhoek, 2015)

Cytotoxicity of benzophenanthridine alkaloids from the roots of Zanthoxylum nitidum (Roxb.) DC. var. fastuosum How ex Huang - Cheng-Fang Wang; Li Fan; Mei Tian; Shu-Shan Du; Zhi-Wei Deng; Jiang-Bin Feng; Yong-Yan Wang; Xu Su (Natural Product Research, 2015)

Loss of Egr-1 sensitizes pancreatic β-cells to palmitate-induced ER stress and apoptosis - Mun-Wai Cheong; Li-Hua Kuo; Yi-Ning Cheng; Pei-Jane Tsai; Li-Chun Ho; Haw-Chih Tai; Wen-Tai Chiu; Shun-Hua Chen; Pei-Jung Lu; Yan-Shen Shan; Lee-Ming Chuang; Yau-Sheng Tsai (Journal of Molecular Medicine, 2015)

Memantine Alleviates Brain Injury and Neurobehavioral Deficits after Experimental Subarachnoid Hemorrhage - Chih-Yuan Huang; Liang-Chao Wang; Hao-Kuang Wang; Chia-Hsin Pan; Ya-Yun Cheng; Yan-Shen Shan; Chung-Ching Chio; Kuen-Jer Tsai (Molecular Neurobiology, 2015)

A New Detection Method of Volcanic Ash Cloud Based on MODIS Image - Jing-Yuan Yin; Jiang-Shan Dong; Cheng-Fan Li; Jun-Juan Zhao (Journal of the Indian Society of Remote Sensing, 2015)

Sevoflurane Used for Color Doppler Ultrasound Examination in Children - Conghai Fan; Fengchao Zhang; Xiaomei Huang; Cheng Wen; Chengjing Shan (Cell Biochemistry and Biophysics, 2015)

Oxidative stress and histopathological alterations in liver of Cyprinus carpio L. induced by intraperitoneal injection of microcystin-LR - Yue Shi; Jinlin Jiang; Zhengjun Shan; Yuanqing Bu; Zhengdong Deng; Yan Cheng (Ecotoxicology, 2015)

Planococcus dechangensis sp. nov., a moderately halophilic bacterium isolated from saline and alkaline soils in Dechang Township, Zhaodong City, China - Kaibiao Wang; Lei Zhang; Jianying Li; Yuanyuan Pan; Lin Meng; Tong Xu; Cheng Zhang; Henan Liu; Shan Hong; Haipeng Huang; Juquan Jiang (Antonie van Leeuwenhoek, 2015)

Gamma-Aminobutyric Acid Induces Tumor Cells Apoptosis via GABABR1·β-Arrestins·JNKs Signaling Module - Hui Tian; Jin-Xia Wu; Feng-Xiao Shan; Shang-Nuan Zhang; Qian Cheng; Jun-Nian Zheng; Dong-Sheng Pei (Cell Biochemistry and Biophysics, 2015)

Novel Rare Earth Tungstoarsenate Heteropolyoxometalates K11[Ln(AsW11O39)2]·xH2O (Ln = La, Nd, Sm) Binding to Bovine Serum Albumin: Spectroscopic Approach - Shan Jiang; Li-Yang Cheng; Ai-Min Bai; Shu Zhou; Yan-Jun Hu (Biological Trace Element Research, 2015)

Late Permian–Triassic siliciclastic provenance, palaeogeography, and crustal growth of the Songpan terrane, eastern Tibetan Plateau: evidence from U–Pb ages, trace elements, and Hf isotopes of detrital zircons - Yu-Xiu Zhang; Lu Zeng; Zhi-Wu Li; Cheng-Shan Wang; Kai-Jun Zhang; Wen-Guang Yang; Tong-Lou Guo (International Geology Review, 2015)

Cancer risks and long-term community-level exposure to pentachlorophenol in contaminated areas, China - Pan Cheng; Qinghe Zhang; Xiaomei Shan; Denghui Shen; Bingshuang Wang; Zhenhai Tang; Yu Jin; Chi Zhang; Fen Huang (Environmental Science and Pollution Research, 2015)

Biotransformation of 1,3-propanediol cyclic sulfate and its derivatives to diols by Rhodococcus sp. - Yu-Cai He; Zhi-Cheng Tao; Dan-Ping Zhang; Zhen-Xing Yang; Shan Gao; Cui-Luan Ma (Biotechnology Letters, 2015)

mTOR ATP-competitive inhibitor INK128 inhibits neuroblastoma growth via blocking mTORC signaling - Huiyuan Zhang; Jun Dou; Yang Yu; Yanling Zhao; Yihui Fan; Jin Cheng; Xin Xu; Wei Liu; Shan Guan; Zhenghu Chen; Yan shi; Roma Patel; et al. (Apoptosis, 2015)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

One new alkaloid from Chelidonium majus L. - Wen-Juan Zhang; Chun-Xue You; Cheng-Fang Wang; Li Fan; Ying Wang; Yang Su; Zhi-Wei Deng; Shu-Shan Du (Natural Product Research, 2014)

Erratum to: Biotransformation of 1,3-propanediol cyclic sulfate and its derivatives to diols by Rhodococcus sp. - Yu-Cai He; Zhi-Cheng Tao; Dan-Ping Zhang; Zhen-Xing Yang; Shan Gao; Cui-Luan Ma (Biotechnology Letters, 2014)

Monitoring of urban heat island in Shanghai, China, from 1981 to 2010 with satellite data - Cheng-fan Li; Di Shen; Jiang-shan Dong; Jing-yuan Yin; Jun-juan Zhao; Dan Xue (Arabian Journal of Geosciences, 2014)

Sinomonas notoginsengisoli sp. nov., isolated from the rhizosphere of Panax notoginseng - Meng-Yue Zhang; Jun Xie; Tian-Yuan Zhang; Huan Xu; Juan Cheng; Shan-Hui Li; Wen-Jun Li; Yi-Xuan Zhang (Antonie van Leeuwenhoek, 2014)

Gordonia jinhuaensis sp. nov., a novel actinobacterium, isolated from a VBNC (viable but non-culturable) state in pharmaceutical wastewater - Shan-Hui Li; Yi Jin; Juan Cheng; Dong-Jin Park; Chang-Jin Kim; Wael N. Hozzein; Mohammed A. M. Wadaan; Wen-Sheng Shu; Lin-Xian Ding; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Salinity improves chilling resistance in Suaeda salsa - Shan Cheng; Zhen Yang; Mingjie Wang; Jie Song; Na Sui; Hai Fan (Acta Physiologiae Plantarum, 2014)

Isolation and characterization of 57 novel polynucleotide microsatellites from yellow catfish (Pelteobagrus fulvidraco) genome for genetic analysis - Yun-Jing Shan; Cui-Yun Lu; Chao Li; Lei Cheng; Xiao-Wen Sun (Conservation Genetics Resources, 2014)

Late Palaeozoic and early Mesozoic tectonic and palaeogeographic evolution of central China: evidence from U–Pb and Lu–Hf isotope systematics of detrital zircons from the western Qinling region - Yu-Xiu Zhang; Lu Zeng; Kai-Jun Zhang; Zhi-Wu Li; Cheng-Shan Wang; Tong-Lou Guo (International Geology Review, 2014)

A new benzopyran derivative from Pseuduvaria indochinensis Merr. - Cai-Gui Zhao; Ming-Jun Yao; Jin-Wei Yang; Ya-Lin Chai; Xiao-Dong Sun; Cheng-Shan Yuan (Natural Product Research, 2014)

Cyclooxygenase-2 Genetic Polymorphism and Stroke Subtypes in Chinese - Guo-zhong Chen; Xiao-yun Shan; Gan-ping Cheng; Hong-miao Tao (Journal of Molecular Neuroscience, 2013)

Cyclooxygenase 2 Genetic Polymorphism May Increase the Risk of Developing Leukoaraiosis in Chinese - Xiao-yun Shan; Guo-zhong Chen; Gan-ping Cheng; Hong-miao Tao (Journal of Molecular Neuroscience, 2013)

Effectiveness of Maifanite in Reducing the Detrimental Effects of Cadmium on Growth Performance, Cadmium Residue, Hematological Parameters, Serum Biochemistry, and the Activities of Antioxidant Enzymes in Pigs - J. Du; S. Y. Cheng; W. X. Hou; B. M. Shi; A. S. Shan (Biological Trace Element Research, 2013)

Analysis of artificial corner reflector’s radar cross section: a physical optics perspective - Xin-Jian Shan; Jing-Yuan Yin; Dan-Lin Yu; Cheng-Fan Li; Jun-Juan Zhao; Gui-Fang Zhang (Arabian Journal of Geosciences, 2013)

High prevalence of torque teno sus virus in China and genetic diversity of the 5’ non-coding region - Shao-Lun Zhai; Jin-Xue Long; Wen-Kang Wei; Qin-Ling Chen; Man-Lin Luo; Dian-Hong Lv; Da-Cheng Wu; Fei Gao; Shi-Shan Yuan; Guang-Zhi Tong; Zu-Zhang Wei (Archives of Virology, 2013)

Suppression of 12-O-Tetradecanoylphorbol-13-Acetate-Induced MCF-7 Breast Adenocarcinoma Cells Invasion/Migration by α-Tomatine Through Activating PKCα/ERK/NF-κB-Dependent MMP-2/MMP-9 Expressions - Min-Der Shi; Yuan-Wei Shih; Ya-Shan Lee; Yueh-Feng Cheng; Li-Yu Tsai (Cell Biochemistry and Biophysics, 2013)

Structural Characterization and Property Analysis of Surface-Active Substance Accumulated During Biodegradation of Hydrophobic α-Pinene by Pseudomonas fluorescens - Zhuo-Wei Cheng; Jian-Meng Chen; Jian-ming Yu; Shan-Shan Li; Yi-Feng Jiang (Water, Air, & Soil Pollution, 2013)

Composition and Distribution of Elements and Ultrastructural Topography of a Human Cardiac Calculus - Ching-Li Cheng; Hsiao-Huang Chang; Pei-Jung Huang; Yu-Ting Chu; Shan-Yang Lin (Biological Trace Element Research, 2013)

The antidepressant effect of secoisolariciresinol, a lignan-type phytoestrogen constituent of flaxseed, on ovariectomized mice - Ying-Feng Wang; Zhi-Kun Xu; Dong-Hui Yang; Hai-Yan Yao; Bao-Shan Ku; Xiao-Qing Ma; Cheng-Zhi Wang; Shu-Lin Liu; Shao-Qing Cai (Journal of Natural Medicines, 2013)

Isolation and characterization of a stress responsive small GTP-binding protein AhRabG3b in peanut (Arachis hypogaea L.) - Jiong-Ming Sui; Rui Li; Qian-Cheng Fan; Lin Song; Chun-Hua Zheng; Jing-Shan Wang; Li-Xian Qiao; Shan-Lin Yu (Euphytica, 2013)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

Demonstration of an Olfactory Bulb–Brain Translocation Pathway for ZnO Nanoparticles in Rodent Cells In Vitro and In Vivo - Yi-Yun Kao; Tsun-Jen Cheng; De-Ming Yang; Chin-Tien Wang; Yin-Mei Chiung; Pei-Shan Liu (Journal of Molecular Neuroscience, 2012)

Carbohydrate-based cancer vaccines: target cancer with sugar bullets - Chang-Cheng Liu; Xin-Shan Ye (Glycoconjugate Journal, 2012)

Dissection of genetic overlap of drought and low-temperature tolerance QTLs at the germination stage using backcross introgression lines in soybean - Wen Bo Zhang; Peng Cheng Qiu; Hong Wei Jiang; Chun Yan Liu; Da Wei Xin; Can Dong Li; Guo Hua Hu; Qing Shan Chen (Molecular Biology Reports, 2012)

Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2012)

Polycyclic aromatic hydrocarbons in household dust near diesel transport routes - Chung-Yih Kuo; Heng-Chun Chen; Fang-Ching Cheng; Li-Ru Huang; Po-Shan Chien; Jing-Ya Wang (Environmental Geochemistry and Health, 2012)

Chronic alcohol intake-induced oxidative stress and apoptosis: role of CYP2E1 and calpain-1 in alcoholic cardiomyopathy - Ling Jing; Cheng-mei Jin; Shan-shan Li; Feng-min Zhang; Lin Yuan; Wei-min Li; Ying Sang; Shuang Li; Li-jun Zhou (Molecular and Cellular Biochemistry, 2012)

Characterization of an enantioselective amidase with potential application to asymmetric hydrolysis of (R, S)-2, 2-dimethylcyclopropane carboxamide - Yuan-Shan Wang; Feng Cheng; Ren-Chao Zheng; Ya-Jun Wang; Yu-Guo Zheng (World Journal of Microbiology and Biotechnology, 2011)

Phytotoxicity and uptake of chlorpyrifos in cabbage - Zhi-Yong Zhang; Wei-Li Shan; Wen-Cheng Song; Yong Gong; Xian-Jin Liu (Environmental Chemistry Letters, 2011)

Synthesis and antidepressant-like action of N-(2-hydroxyethyl) cinnamamide derivatives in mice - Xian-Qing Deng; Di Wu; Cheng-Xi Wei; Zhe-Shan Quan (Medicinal Chemistry Research, 2011)

A new iridoid compound from Patrinia rupestris (Pall.) Juss. - Dong-Feng Qiu; Xiu-Ping Yang; Yang-Jun Xu; Xiao-Qing Liu; Hong-Li Liu; Cheng-Shan Yuan (Natural Product Research, 2011)

Synthesis and evaluation of 7-substituted-3,4-dihydrobenzo[f][1,4]oxazepin-5(2H)-ones as anticonvulsant and hypnotic agents - Xian-Qing Deng; Ming-Xia Song; Cheng-Xi Wei; Zhi-Gang Sun; Zhe-Shan Quan (Medicinal Chemistry Research, 2011)

Genetic diversity and differentiation of cultivated ginseng (Panax ginseng C. A. Meyer) populations in North-east China revealed by inter-simple sequence repeat (ISSR) markers - Shan Li; Jing Li; Xiao-Ling Yang; Zhou Cheng; Wen-Ju Zhang (Genetic Resources and Crop Evolution, 2011)

Polyclonal rabbit anti-murine plasmacytoma cell globulins induce myeloma cells apoptosis and inhibit tumour growth in mice - Bo Mu; Jin-liang Yang; Lan-tu Gou; Yu-qin Yao; Yan Zhou; Zhi-hui Cheng; Hua-shan Shi; Zhi-yong Li; Yuan Wen; Fei Leng; Feng-yu Cui; Tian-tai Ma; et al. (Apoptosis, 2011)

Establishment of a transgene expression system for the marine microalga Schizochytrium by 18S rDNA-targeted homologous recombination - Ru-Bin Cheng; Xiang-Zhi Lin; Zhao-Kai Wang; Shan-Jun Yang; Hui Rong; Yong Ma (World Journal of Microbiology and Biotechnology, 2011)

PTEN status is related to cell proliferation and self-renewal independent of CD133 phenotype in the glioma-initiating cells - Ru-Bin Cheng; Rui-Juan Ma; Zhao-Kai Wang; Shan-Jun Yang; Xiang-Zhi Lin; Hui Rong; Yong Ma (Molecular and Cellular Biochemistry, 2011)

Phylogeny of Arachis based on internal transcribed spacer sequences - Chuan Tang Wang; Xiu Zhen Wang; Yue Yi Tang; Dian Xu Chen; Feng Gao Cui; Jian Cheng Zhang; Shan Lin Yu (Genetic Resources and Crop Evolution, 2011)

Molecular characterization of a phenylalanine ammonia-lyase gene (BoPAL1) from Bambusa oldhamii - Lu-Sheng Hsieh; Yi-Lin Hsieh; Chuan-Shan Yeh; Chieh-Yang Cheng; Chien-Chih Yang; Ping-Du Lee (Molecular Biology Reports, 2011)

Expression of GDF-9, BMP-15 and their receptors in mammalian ovary follicles - R. Z. Sun; L. Lei; L. Cheng; Z. F. Jin; S. J. Zu; Z. Y. Shan; Z. D. Wang; J. X. Zhang; Z. H. Liu (Journal of Molecular Histology, 2010)

Synthesis of 6-(3-substituted-4H-1,2,4-triazol-4-yl)-2-phenylbenzo[d]oxazoles as potential anticonvulsant agents - Cheng-Xi Wei; Di Wu; Zhi-Gang Sun; Kyu-Yun Chai; Zhe-Shan Quan (Medicinal Chemistry Research, 2010)

Effect of CYP2C19 genotypes on the pharmacokinetic/pharmacodynamic relationship of rabeprazole after a single oral dose in healthy Chinese volunteers - Yu-Cheng Sheng; Kun Wang; Ying-Chun He; Juan Yang; Qing-Shan Zheng (European Journal of Clinical Pharmacology, 2010)

Chemical constituents of Gentiana macrophylla Pall. - Zhi-Bo Jiang; Hong-Li Liu; Xiao-Qing Liu; Ji-Ning Shang; Jia-Rui Zhao; Cheng-Shan Yuan (Natural Product Research, 2010)

Lowland rainforests in southern Taiwan and Lanyu, at the northern border of Paleotropics and under the influence of monsoon wind - Wei-Chun Chao; Guo-Zhang M. Song; Kuo-Jung Chao; Chi-Cheng Liao; Su-Wei Fan; Shan-Huah Wu; Tsung-Hsin Hsieh; I-Fang Sun; Yau-Lun Kuo; Chang-Fu Hsieh (Plant Ecology, 2010)

Cancer risks from betel quid chewing beyond oral cancer: a multiple-site carcinogen when acting with smoking - Chi Pang Wen; Min Kuang Tsai; Wen Shen Isabella Chung; Hui Ling Hsu; Yen Chen Chang; Hui Ting Chan; Po Huang Chiang; Ting-Yuan David Cheng; Shan Pou Tsai (Cancer Causes & Control, 2010)

Cytokinin and auxin regulates WUS induction and inflorescence regeneration in vitro in Arabidopsis - Zhi Juan Cheng; Shan Shan Zhu; Xin Qi Gao; Xian Sheng Zhang (Plant Cell Reports, 2010)

Analysis of the Surface Ozone During Summer and Autumn at a Coastal Site in East China - Yongquan Yin; Wenpo Shan; Xia Ji; Xingyan Deng; Jian’an Cheng; Laimin Li (Bulletin of Environmental Contamination and Toxicology, 2010)

A novel normonoterpenoid from the stems of Cinnamomum reticulatum Hay - Ming-Jen Cheng; Wen-Li Lo; Wan-Shan Tseng; Hung-Chun Yeh; Chung-Yi Chen (Natural Product Research, 2010)

Characterization of a new dehydration responsive element binding factor in central arctic cowberry - Qing-Ju Wang; Kuan-Yong Xu; Zhao-Guo Tong; San-Hong Wang; Zhi-Hong Gao; Ji-Yu Zhang; Cheng-Wen Zong; Yu-Shan Qiao; Zhen Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Proteomic analysis of differentially expressed proteins in mice with concanavalin A-induced hepatitis - Xu-fei Tan; Feng Chen; Shan-shan Wu; Yu Shi; Dong-cheng Liu; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2010)

Expression and Purification of an Antimicrobial Peptide, Bovine Lactoferricin Derivative LfcinB-W10 in Escherichia coli - Xingjun Feng; Chunlong Liu; Jiayin Guo; Chongpeng Bi; Baojing Cheng; Zhongyu Li; Anshan Shan; Zhongqiu Li (Current Microbiology, 2010)

Analysis of genome expression in the response of Oryza granulata to Xanthomonas oryzae pv oryzae - Yu Luo; Guang-Lei Lv; Wen-Ting Wu; Shan-Na Chen; Zai-Quan Cheng (Molecular Biology Reports, 2010)

Cytocompatibility of regenerated silk fibroin film: a medical biomaterial applicable to wound healing - Tie-lian Liu; Jing-cheng Miao; Wei-hua Sheng; Yu-feng Xie; Quan Huang; Yun-bo Shan; Ji-cheng Yang (Journal of Zhejiang University-SCIENCE B, 2010)

Joint Impact of Scaling and Hysteresis on NAPL Flow Simulation - Hung-Hui Chen; Liang-Cheng Chang; Hsin-Yu Shan; Jui-Pin Tsai (Environmental Modeling & Assessment, 2009)

Synoptic weather typing and typhoon with an application to Chiayi, Taiwan: potential for future climate change impact analysis - Chad Shouquan Cheng; Pao-Shan Yu; Qian Li; Guilong Li; Jung-Lien Chu (Paddy and Water Environment, 2009)

Fabrication of a Novel Core-Shell Gene Delivery System Based on a Brush-Like Polycation of α, β–Poly (L-Aspartate-Graft-PEI) - Jia-Hui Yu; Ji-Shan Quan; Jung-Taek Kwon; Cheng-Xiong Xu; Bo Sun; Hu-Lin Jiang; Jae-Woon Nah; Eun-Mi Kim; Hwan-Jeong Jeong; Myung-Haing Cho; Chong-Su Cho (Pharmaceutical Research, 2009)

Blockade of HERG K+ channel by isoquinoline alkaloid neferine in the stable transfected HEK293 cells - Dong-fang Gu; Xue-lian Li; Zhi-ping Qi; Sha-shan Shi; Mei-qin Hu; Dong-min Liu; Cheng-bai She; Yan-jie Lv; Bao-xin Li; Bao-feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

Thermodynamics, Conformation and Active Sites of the Binding of Zn–Nd Hetero-bimetallic Schiff Base to Bovine Serum Albumin - Qi Xiao; Shan Huang; Yi Liu; Fang-fang Tian; Jun-cheng Zhu (Journal of Fluorescence, 2009)

Genetic diversity and phylogenetic analysis of Australian Grapevine Viroid (AGVd) isolated from different grapevines in China - Dongmei Jiang; Shan Peng; Zujian Wu; Zhuomin Cheng; Shifang Li (Virus Genes, 2009)

An age-dependent proliferation is involved in the postnatal development of interstitial cells of Cajal in the small intestine of mice - Feng Mei; Jiang Zhu; Sheng Guo; De-shan Zhou; Juan Han; Bin Yu; Shi-feng Li; Zhong-yong Jiang; Cheng-jie Xiong (Histochemistry and Cell Biology, 2009)

Altered gene expression of NIDD in dorsal root ganglia and spinal cord of rats with neuropathic or inflammatory pain - Meng-Ling Chen; Chun Cheng; Qing-Shan Lv; Zhi-Qin Guo; Ying Gao; Shang-Feng Gao; Xin Li; Shu-Qiong Niu; Shu-Xian Shi; Ai-Guo Shen (Journal of Molecular Histology, 2008)

Genetic analysis of a novel dominant rice dwarf mutant 986083D - Ruizhen Qin; Yang Qiu; Zhijun Cheng; Xueyan Shan; Xiuping Guo; Huqu Zhai; Jianmin Wan (Euphytica, 2008)

A novel trinorguaiane-type sesquiterpene from Dictamnus radicis - Pei-Hua Zhao; Xiu-Ping Yang; Cheng-Shan Yuan (Natural Product Research, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Incidental discovery of high systemic lupus erythematosus disease activity associated with cytomegalovirus viral activity - Ben Yu-Jih Su; Cheng-Yu Su; Shan-Fu Yu; Chung-Jen Chen (Medical Microbiology and Immunology, 2007)

Variation in two PPO genes associated with polyphenol oxidase activity in seeds of common wheat - Cheng Chang; Hai-Ping Zhang; Jie Xu; Ming-Shan You; Bao-Yun Li; Guang-Tian Liu (Euphytica, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Application of cDNA array for studying the gene expression profile of mature appressoria of Magnaporthe grisea - Qing-chao Jin; Hai-tao Dong; You-liang Peng; Bao-shan Chen; Jing Shao; Ye Deng; Cheng-en Dai; Yong-qi Fang; Yi-chun Lou; You-zhi Li; De-bao Li (Journal of Zhejiang University-SCIENCE B, 2007)

Two new chemical constituents from Daphne odora Thunb. var. marginata - W. Zhang; W. D. Zhang; R. H. Liu; Y. H. Shen; C. Zhang; H. S. Cheng; P. Fu; L. Shan (Natural Product Research, 2006)

Distribution of HCHs and DDTs in Soils from Beijing City, China - Xinghong Li; Youfeng Zhu; Xiufen Liu; Shan Fu; Xiaobai Xu; Hangxin Cheng (Archives of Environmental Contamination and Toxicology, 2006)

Cloning and Characterization of a Second form of the Rice Adenine Phosphoribosyl Transferase Gene (OsAPT2) and its Association with TGMS - Chun-Jiang Zhou; Jun Li; Ji-Cheng Zou; Feng-Shan Liang; Chun-Jiang Ye; De-Min Jin; Man-Li Weng; Bin Wang (Plant Molecular Biology, 2006)

MULTIPLE INITIAL CULTURE CONDITIONS ENHANCE THE ESTABLISHMENT OF CELL LINES FROM PRIMARY OVARIAN CANCER SPECIMENS - CARA C. BERTOZZI; CHENG-YI CHANG; SONYA JAIRAJ; XIAOCHUAN SHAN; JIA HUANG; BARBARA L. WEBER; CHRISTINA S. CHU; RICHARD G. CARROLL (In Vitro Cellular & Developmental Biology - Animal, 2006)

Multiple Initial Culture Conditions Enhance the Establishment of Cell Lines from Primary Ovarian Cancer Specimens - Cara C. Bertozzi; Cheng-Yi Chang; Sonya Jairaj; Xiaochuan Shan; Jia Huang; Babara L. Weber; Christina S. Chu; Richard G. Carroll (In Vitro Cellular & Developmental Biology - Animal, 2006)

Exogenous Application of Jasmonic Acid Induces Volatile Emissions in Rice and Enhances Parasitism of Nilaparvata lugens Eggs by theParasitoid Anagrus nilaparvatae - Yong-Gen Lou; Meng-Hao Du; Ted C. J. Turlings; Jia-An Cheng; Wei-Fang Shan (Journal of Chemical Ecology, 2005)

Safety analysis of water resources and eco-environment in Shiyang River Basin - Ji-shi Zhang; Yong-qiu Zhang; Rui-feng Pu; Ren-sheng Chen; Zhong-shan Cheng; Ming-quan Wang (Chinese Geographical Science, 2005)

Isolation and characterization of a new carbendazim-degrading Ralstonia sp. strain - Gui-Shan Zhang; Xiao-Ming Jia; Tian-Fan Cheng; Xiao-Hang Ma; Yu-Hua Zhao (World Journal of Microbiology and Biotechnology, 2005)

Using a Set of Strategic Indicator Systems as a Decision-making Support Implement for Establishing a Recycling-oriented Society - A Taiwanese Case Study (16 pp) - I-Cheng Chang; Li-Teh Lu; Shiann-Shan Lin (Environmental Science and Pollution Research, 2005)

Eudragit E Accelerated the Diketopiperazine Formation of Enalapril Maleate Determined by Thermal FTIR Microspectroscopic Technique - Shun-Li Wang; Shan-Yang Lin; Ting-Fang Chen; Wen-Ting Cheng (Pharmaceutical Research, 2004)

DNA extraction from archival formalin-fixed, paraffin-embedded tissues: heat-induced retrieval in alkaline solution - Shan-Rong Shi; Ram Datar; Cheng Liu; Lin Wu; Zina Zhang; Richard J. Cote; Clive R. Taylor (Histochemistry and Cell Biology, 2004)

Spatial and temporal dynamics of soil organic carbon in reserved desertification area - Shu-lan Cheng; Hua Ouyang; Hai-shan Niu; Lin Wang; Feng Zhang; Jun-qin Gao; Yu-qiang Tian (Chinese Geographical Science, 2004)

Microsatellite polymorphism in promoter of heme oxygenase-1 gene is associated with susceptibility to coronary artery disease in type 2 diabetic patients - Ying-Hwa Chen; Shing-Jong Lin; Ming-Wei Lin; Hui-Ling Tsai; San-San Kuo; Jaw-Wen Chen; Min-Ji Charng; Tao-Cheng Wu; Lung-Ching Chen; Philip Ding; Wen-Harn Pan; Yuh-Shan Jou; et al. (Human Genetics, 2002)

Cyanide-Induced Alterations to the Biophysical Conformations of the Isolated Fish Liver - Yih-Dih Cheng; Tsung-Yun Liu; Shan-Yang Lin (Ecotoxicology, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Percolation and Dispersion of Mass Transport in Saturated Fracture Networks - Bih-Shan Lin; Cheng-Haw Lee (Water Resources Management, 1998)

Synthesis, structure and anti-acetylcholinesterase activity of 4β-methoxymethyl-4β-demethyl territrem B - Fu-Chuo Peng; Jur-Shan Cheng (Mycopathologia, 1997)